Method for producing metal foil-clad laminate, resin composition, resin composite sheet, method for producing printed wiring board, and method for producing semiconductor device
By reducing the moisture and solvent content of the circuit substrate in the vacuum lamination method, and using a resin composite sheet containing a metal foil and a resin composition layer for heating and pressurization treatment, the problem of peeling between the resin composition layer and the metal foil in the metal foil laminated plate is solved, and efficient mass production and improved circuit reliability are achieved.
Patent Information
- Application Number
- CN202380057796.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-09
- Filing Date
- 2023-06-26
- Publication Date
- 2025-03-14
AI Technical Summary
When the metal foil laminated plate is manufactured by the vacuum lamination method, peeling is easily caused between the resin composition layer and the metal foil, resulting in insufficient circuit formation and reduced reliability.
The content of moisture and solvent is reduced on the circuit substrate and the resin composite sheet containing a metal foil and a resin composition layer is subjected to heating and pressurization treatment to inhibit peeling between the resin composition layer and the metal foil.
This method not only improves the mass-productivity of the laminated plate of metal foil, but also effectively suppresses the peeling between the resin composition layer and the metal foil, and improves the formation quality and reliability of the circuit.
Smart Images

Figure CN119631581A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for producing a metal foil-clad laminate, a resin composition, a resin composite sheet, a method for producing a printed wiring board, and a method for producing a semiconductor device. Background Art
[0002] In recent years, a technology for manufacturing a printed wiring board in which an insulating layer is provided on a conductor circuit layer of an inner wiring board has attracted attention.
[0003] For example, Patent Document 1 discloses a method for manufacturing a multilayer printed circuit board, wherein the resin composition layer of an adhesive film composed of a supporting base film and a resin composition layer laminated on the surface thereof is vacuum laminated on a circuit substrate under heating and pressurizing conditions, characterized in that the following steps are performed:
[0004] 1) a step of vacuum laminating the adhesive film on both sides of the circuit board by heating and pressurizing from the supporting base film side via a heat-resistant rubber; and
[0005] 2) A step of heating and pressing both surfaces of the circuit board on which the adhesive film is vacuum-laminated from the supporting base film side of the adhesive film using a pressing metal plate or a laminating metal roll to smooth the surface of the resin composition layer in contact with the supporting base film.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Publication No. 2009-105446 Summary of the invention
[0009] Problem that the invention aims to solve
[0010] Here, as a method for producing a printed wiring board, a vacuum heat pressing method and a vacuum lamination method are known.
[0011] The vacuum hot pressing method refers to a method of manufacturing a printed circuit board by batch processing, for example, a laminate of a circuit substrate and a resin sheet is placed in a vacuum hot pressing device and pressed and thermally cured under a reduced pressure or vacuum environment. This method is a useful method, but the lamination time is long, which has problems from the perspective of mass production.
[0012] The vacuum lamination method refers to a method for manufacturing a printed circuit board by continuous processing using a vacuum lamination device. Specifically, a laminate of a circuit substrate and a resin sheet is hot pressed under reduced pressure or vacuum, and then hot pressed using a pressing metal plate or a laminating metal roller, thereby continuously manufacturing a printed circuit board in a short time. For example, the method described in Patent Document 1 belongs to this method. The vacuum lamination method has advantages from the perspective of mass production.
[0013] However, the inventors have found out through research that when a metal foil-clad laminate is manufactured by vacuum lamination, if the resin sheet contains metal foil, peeling may occur between the resin composition layer and the metal foil of the obtained metal foil-clad laminate. Such peeling of the metal foil may cause insufficient circuit formation and reduced reliability when a conductor circuit is subsequently formed, for example.
[0014] The object of the present invention is to solve the above-mentioned problem, and the object is to provide a method for manufacturing a metal foil-clad laminate, which is a method for manufacturing a metal foil-clad laminate using a circuit substrate and a resin composite sheet comprising a metal foil and a resin composition layer, wherein the method has excellent mass productivity and the peeling between the resin composition layer and the metal foil is suppressed, as well as a resin composition used in the above-mentioned method for manufacturing a metal foil-clad laminate, a resin composite sheet, a method for manufacturing a printed circuit board, and a method for manufacturing a semiconductor device.
[0015] Solutions for solving problems
[0016] Based on the above problems, the inventors have studied and found that the water and solvent remaining in the circuit substrate may cause the peeling of the metal foil. In addition, the inventors have found that the above problems can be solved by reducing the water and solvent remaining in the circuit substrate before laminating the circuit substrate and the resin composite sheet and hot pressing under reduced pressure or vacuum.
[0017] Specifically, the above-mentioned problems are solved by the following means.
[0018] <1> A method for manufacturing a metal foil-clad laminate, which is a method for manufacturing a metal foil-clad laminate using a vacuum lamination device, wherein the metal foil-clad laminate is formed by laminating a resin composite sheet C on the surface of a circuit substrate A, the resin composite sheet C comprising a metal foil and a resin composition layer arranged on a single side of the aforementioned metal foil, and the circuit substrate A comprising an insulating layer and a conductor circuit layer.
[0019] Step 1: a step of reducing the content of water and / or solvent contained in the circuit substrate A to obtain the circuit substrate B;
[0020] Step 2: a step of arranging a resin composite sheet C including a metal foil and a resin composition layer arranged on one side of the metal foil on at least one surface of a circuit substrate B in such a manner that the resin composition layer side contacts the circuit substrate B, and applying pressure from the surface on the metal foil side under heating and reduced pressure or vacuum to obtain a laminated substrate D in which the resin composite sheet C is laminated on at least one surface of the circuit substrate B;
[0021] Step 3: A step of obtaining a laminated substrate E by heating and pressing the metal foil side surface of the laminated substrate D obtained in step 2 using a pressing metal plate or a laminating metal roller to smooth the surface of the resin composition layer of the laminated substrate D.
[0022] <2> The method for producing a metal foil-clad laminate according to <1>, further comprising the following step after the step 3:
[0023] Step 4: A step of heating the laminated substrate E obtained in the step 3 to cure the resin composition layer, thereby obtaining a cured substrate F.
[0024] <3> The method for producing a metal foil-clad laminate according to <2>, wherein a mass reduction rate of the laminated substrate E due to heating in the step 4 is 1.0 mass % or less.
[0025] <4> The method for producing a metal-clad laminate according to <2> or <3>, comprising repeating steps 2 to 4 on the cured substrate F.
[0026] <5> The method for producing a metal-clad laminate according to any one of <2> to <4>, wherein the heating in the step 4 is performed at 100 to 250°C.
[0027] <6> The method for producing a metal-clad laminate according to any one of <2> to <5>, wherein the heating in the step 4 is performed by stepwise temperature increase in two or more stages.
[0028] <7> The method for producing a metal foil-clad laminate according to any one of <2> to <6>, wherein the heating in the step 4 is performed at 100 to 180°C and then at a temperature higher than 180°C and lower than 250°C.
[0029] <8> The method for producing a metal foil-clad laminate according to any one of <1> to <7>, further comprising an operation of making the circuit board B obtained in the step 1 less likely to absorb moisture.
[0030] <9> The method for producing a metal foil-clad laminate according to any one of <1> to <8>, comprising performing the step 2 immediately after the step 1.
[0031] <10> The method for producing a metal foil-clad laminate according to any one of <1> to <9>, wherein the step 2 is performed after the circuit board B obtained in the step 1 is stored in an atmosphere that is less likely to absorb moisture.
[0032] <11> The method for producing a metal foil-clad laminate according to any one of <1> to <10>, comprising: in the step 1, obtaining a circuit board B in which the water content in the circuit board A is reduced.
[0033] <12> The method for producing a metal-clad laminate according to any one of <1> to <11>, wherein the heating in the step 1 is performed at 30 to 200°C.
[0034] <13> The method for producing a metal-clad laminate according to any one of <1> to <12>, wherein the heating in the step 2 is performed at a temperature of 80 to 190° C. and a pressure of 3 to 30 kgf / cm 2 Next proceed.
[0035] <14> The method for producing a metal-clad laminate according to any one of <1> to <13>, wherein the heating in the step 3 is performed at a temperature of 80 to 190° C. and a pressure of 3 to 30 kgf / cm 2 Next proceed.
[0036] <15> The method for producing a metal-clad laminate according to any one of <1> to <14>, wherein the metal foil is a copper foil.
[0037] <16> The method for producing a metal-clad laminate according to any one of <1> to <15>, wherein the resin composite sheet C includes a carrier substrate, the metal foil, and the resin composition layer in this order.
[0038] <17> The method for producing a metal-clad laminate according to any one of <1> to <16>, wherein the resin composition contains a thermosetting resin, and the content of the inorganic filler is 0 to 250 parts by mass relative to 100 parts by mass of resin solids contained in the resin composition.
[0039] <18> A resin composition for producing a metal-clad laminate by a method using a vacuum laminating apparatus and comprising the following steps, wherein the metal-clad laminate is formed by laminating a resin composite sheet C on a surface of a circuit substrate A, the resin composite sheet C comprising a metal foil and a resin composition layer disposed on one side of the metal foil, the circuit substrate A comprising an insulating layer and a conductor circuit layer, the resin composition comprising a thermosetting resin, and the content of an inorganic filler is 0 to 250 parts by mass relative to 100 parts by mass of a resin solid content contained in the resin composition;
[0040] Step 1: a step of reducing the content of water and / or solvent contained in the circuit substrate A to obtain the circuit substrate B;
[0041] Step 2: a step of arranging a resin composite sheet C comprising a metal foil and a resin composition layer arranged on one side of the metal foil on at least one surface of a circuit substrate B in such a manner that the resin composition layer side is in contact with the circuit substrate B, and applying pressure from the surface on the metal foil side under heating and reduced pressure or vacuum to obtain a laminated substrate D in which the resin composite sheet C is laminated on at least one surface of the circuit substrate B;
[0042] Step 3: A step of obtaining a laminated substrate E by heating and pressing the metal foil side surface of the laminated substrate D obtained in step 2 using a pressing metal plate or a laminating metal roller to smooth the surface of the resin composition layer of the laminated substrate D.
[0043] <19> The resin composition according to <18>, wherein the thermosetting resin comprises at least one selected from the group consisting of a polymer having a structural unit represented by formula (V), a polyphenylene ether compound having a carbon-carbon unsaturated double bond at the terminal, a maleimide compound, a cyanate compound, an epoxy compound, a phenol compound, an oxetane resin, a benzoxazine compound and an alkenyl-substituted nadic imide compound.
[0044]
[0045] (In formula (V), Ar represents an aromatic hydrocarbon linking group. * represents a bonding position.)
[0046] <20> The resin composition according to <18> or <19>, wherein the resin composition contains an inorganic filler.
[0047] The inorganic filler includes silicon dioxide.
[0048] <21> The resin composition according to any one of <18> to <20>, wherein the resin composition contains an inorganic filler
[0049] The inorganic filler has an average particle size D50 of 0.1 μm or more and 5 μm or less.
[0050] <22> A resin composite sheet for producing a metal foil-clad laminate by a method using a vacuum laminating apparatus and comprising the following steps, wherein the metal foil-clad laminate is formed by laminating a resin composite sheet on a surface of a circuit substrate A, the resin composite sheet comprising a metal foil and a resin composition layer disposed on one side of the metal foil, the circuit substrate A comprising an insulating layer and a conductor circuit layer,
[0051] The resin composition comprises a thermosetting resin, and the content of the inorganic filler is 0 to 250 parts by mass relative to 100 parts by mass of the resin solid content contained in the resin composition;
[0052] Step 1: a step of reducing the content of water and / or solvent contained in the circuit substrate A to obtain the circuit substrate B;
[0053] Step 2: a step of arranging a resin composite sheet including a metal foil and a resin composition layer arranged on one side of the metal foil on at least one surface of a circuit substrate B in such a manner that the resin composition layer side contacts the circuit substrate B, and applying pressure from the surface on the metal foil side under heating and reduced pressure or vacuum to obtain a laminated substrate D in which the resin composite sheet is laminated on at least one surface of the circuit substrate B;
[0054] Step 3: A step of obtaining a laminated substrate E by heating and pressing the metal foil side surface of the laminated substrate D obtained in step 2 using a pressing metal plate or a laminating metal roller to smooth the surface of the resin composition layer of the laminated substrate D.
[0055] <23> The resin composite sheet according to <22>, wherein the resin composite sheet includes a carrier substrate, the metal foil, and the resin composition layer in this order.
[0056] <24> The resin composite sheet according to <22> or <23>, wherein the metal foil is a copper foil.
[0057] <25> A resin composite sheet according to any one of <22> to <24>, wherein the thermosetting resin comprises at least one selected from the group consisting of a polymer having a structural unit represented by formula (V), a polyphenylene ether compound having a carbon-carbon unsaturated double bond at the terminal, a maleimide compound, a cyanate compound, an epoxy compound, a phenol compound, an oxetane resin, a benzoxazine compound and an alkenyl-substituted nadic imide compound.
[0058]
[0059] (In formula (V), Ar represents an aromatic hydrocarbon linking group. * represents a bonding position.)
[0060] <26> The resin composite sheet according to any one of <22> to <25>, wherein the resin composition contains an inorganic filler.
[0061] The inorganic filling material includes silicon dioxide.
[0062] <27> The resin composite sheet according to any one of <22> to <26>, wherein the resin composition contains an inorganic filler.
[0063] The inorganic filler has an average particle size D50 of 0.1 μm or more and 5 μm or less.
[0064] <28> A method for producing a printed wiring board, comprising the method for producing a metal foil-clad laminate according to any one of <1> to <17>.
[0065] <29> A method for manufacturing a semiconductor device, comprising the method for manufacturing a metal foil-clad laminate according to any one of <1> to <17>.
[0066] Effects of the Invention
[0067] According to the present invention, a method for manufacturing a metal foil-clad laminate can be provided, which is a method for manufacturing a metal foil-clad laminate using a circuit substrate and a resin composite sheet comprising a metal foil and a resin composition layer, the method having excellent mass productivity and in which peeling between the resin composition layer and the metal foil is suppressed, and a resin composition and resin composite sheet used in the aforementioned method for manufacturing a metal foil-clad laminate, a method for manufacturing a printed circuit board, and a method for manufacturing a semiconductor device can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0068] Figure 1 It is a schematic diagram showing each step of the method for producing the metal foil-clad laminate of the present invention.
[0069] Figure 2 The schematic diagram shows each step of a method for producing a metal foil-clad laminate using a conventional vacuum lamination method.
[0070] Figure 3 This is a schematic diagram showing an example of the layer structure of the metal foil-clad laminate of the present invention. DETAILED DESCRIPTION
[0071] Hereinafter, a mode for carrying out the present invention (hereinafter referred to as "this embodiment") will be described in detail. Note that the following this embodiment is an example for explaining the present invention, and the present invention is not limited to this embodiment.
[0072] In addition, in this specification, "to" is used to mean that the numerical values described before and after it are included as a lower limit and an upper limit.
[0073] In this specification, various physical property values and characteristic values are values at 23° C. unless otherwise specified.
[0074] In the description of the group (atomic group) in this specification, the expression that does not indicate substitution and unsubstituted includes the group (atomic group) without substitution and also includes the group (atomic group) with substitution. For example, "alkyl" includes not only the alkyl group without substitution (unsubstituted alkyl group) but also the alkyl group with substitution (substituted alkyl group). In this specification, the expression that does not indicate substitution and unsubstituted is preferably unsubstituted.
[0075] In this specification, the resin solid content refers to components other than fillers and solvents, and is a concept that includes thermosetting resins, elastomers, and other resin additive components (additives such as flame retardants, etc.).
[0076] In this specification, relative dielectric constant and dielectric constant are used as synonyms.
[0077] In this specification, the term "process" includes not only independent processes but also processes that cannot be clearly distinguished from other processes as long as the expected effects of the process can be achieved.
[0078] The measurement methods described in the standards shown in this specification may differ depending on the year, but unless otherwise specified, they are based on the standards as of January 1, 2022.
[0079] Figures 1 to 3 It is a schematic diagram, and sometimes the scale and other information may not be consistent with the actual situation.
[0080] The method for manufacturing a metal-clad laminated plate of the present embodiment is a method for manufacturing a metal-clad laminated plate using a vacuum laminating device, wherein the metal-clad laminated plate is formed by laminating a resin composite sheet C on the surface of a circuit substrate A, wherein the resin composite sheet C comprises a metal foil and a resin composition layer disposed on one side of the metal foil, and the circuit substrate A comprises an insulating layer and a conductor circuit layer, and the method for manufacturing a metal-clad laminated plate is characterized by comprising the following steps:
[0081] Step 1: a step of reducing the content of water and / or solvent contained in the circuit substrate A to obtain the circuit substrate B;
[0082] Step 2: a step of arranging a resin composite sheet C including a metal foil and a resin composition layer arranged on one side of the metal foil on at least one surface of a circuit substrate B in such a manner that the resin composition layer side contacts the circuit substrate B, and applying pressure from the metal foil side under heating and reduced pressure or vacuum to obtain a laminated substrate D in which the resin composite sheet C is laminated on at least one surface of the circuit substrate B;
[0083] Step 3: A step of obtaining a laminated substrate E by heating and pressing the metal foil side surface of the laminated substrate D obtained in step 2 using a pressing metal plate or a laminating metal roll to smooth the surface of the resin composition layer of the laminated substrate D.
[0084] By adopting such a configuration, it is possible to achieve excellent mass productivity and effectively suppress peeling between the resin composition layer and the metal foil. Furthermore, it is also possible to effectively suppress peeling and swelling at the interface between the circuit board and the resin composition layer.
[0085] Specifically, as described above, the conventional vacuum heat pressing method is a batch process and therefore is inferior in terms of mass productivity. Therefore, the use of the vacuum lamination method is considered.
[0086] Here, for reasons to be described later, in the vacuum heat pressing method, an operation of intentionally reducing the content of water and / or solvent contained in the circuit board of the laminated resin composite sheet is not performed. Figure 2 A schematic diagram showing each process when a metal foil-clad laminate is manufactured using a vacuum lamination method without including a process for reducing the content of water and / or solvent contained in a circuit substrate of a laminated resin composite sheet. Specifically, a schematic diagram showing each process of a method for manufacturing a metal foil-clad laminate without including a process for reducing the content of water and / or solvent contained in a circuit substrate A to obtain a circuit substrate B.
[0087] exist Figure 2 In step (2'), A is a circuit board, and C is a resin composite sheet comprising a metal foil and a resin composition layer disposed on one side of the metal foil. Figure 2 In the embodiment, a resin composite sheet C is arranged in a vacuum laminating device in such a manner as to sandwich the circuit substrate A, and hot pressing (heating and pressurizing) is performed under reduced pressure or vacuum, thereby obtaining a laminated substrate D'. The obtained laminated substrate D' is heated and pressurized from one side of the metal foil side using a pressing metal plate or a laminating metal roller to smooth the surface of the resin composition layer of the laminated substrate D', thereby obtaining a laminated substrate E' ( Figure 2 Step (3')). Furthermore, the laminated substrate E' is usually heated to cure the resin composition layer, thereby obtaining a cured substrate F' ( Figure 2 Step (4')).
[0088] Here, it is known that, when a resin film is laminated on the surface of a circuit substrate without using a metal foil as a support as described in Patent Document 1, there is no particular problem of peeling between the resin composition layer and the support. However, on the other hand, when a laminated substrate E' is obtained by using a resin composite sheet C having a metal foil, when the laminated substrate E' is further thermally cured to obtain a cured substrate F', peeling occurs between the resin composition layer and the metal foil ( Figure 2 (5')). Specifically, it is known that a portion of the metal foil will Figure 2 The metal foil has a bulge as shown by X. The bulge of the metal foil may have a diameter of several mm, and in the case of a larger diameter, may have a diameter of 10 cm or more.
[0089] The inventors of the present invention have studied the reason in detail and found that the reason is that the circuit substrate A contains water and solvent, and the water and solvent are vaporized by heating. In particular, the reason is that the process of further thermally curing the laminated substrate E' to obtain the cured substrate F' ( Figure 2 In the step (4') of further thermal curing of the laminated substrate E' to obtain the cured substrate F', gas will be vaporized by heating. That is, if the resin film is as described in Patent Document 1, the gas generated during the thermal curing process will pass through the resin film and be released to the outside of the laminated substrate, but the metal foil has excellent gas barrier properties, so the generated gas will not pass through. It is known that gas will remain inside the laminated substrate D' and / or E', mainly in the step ( Figure 2 In the step (4')), the gas remaining inside the above-mentioned will become bubbles X', causing the metal foil to bulge X. It is also known that similar bubbles will be formed between the circuit board A and the resin composite sheet C, sometimes causing peeling.
[0090] Therefore, the present invention can suppress the swelling of the metal foil and the peeling between the resin composition layer and the metal foil by reducing the content of water and / or solvent in the circuit board A before placing it in the vacuum laminator.
[0091] In addition, it was found that the above-mentioned peeling can be effectively suppressed by reducing the content of the inorganic filler in the resin composition layer. This is presumably because the inorganic filler easily absorbs moisture. It should be noted that the details of the resin composition are preferably those described in the section <Resin composition> described later.
[0092] On the other hand, the vacuum hot pressing method performs heat curing in a state pressed with a metal plate, so that physical bulging can be suppressed. In addition, the vacuum hot pressing method takes time to perform heat curing under a reduced pressure or vacuum environment, so the escape of the above-mentioned gas from the laminated substrate is promoted, thereby suppressing bulging. Therefore, in the vacuum hot pressing method, even if the content of moisture and / or solvent contained in the circuit substrate of the laminated resin composite sheet is not intentionally reduced, the metal foil laminate can be manufactured without problems. That is, the subject of the present embodiment is a unique subject when using a vacuum laminating device and a resin composite sheet containing a metal foil and a resin composition layer disposed on one side of the aforementioned metal foil. Furthermore, in the vacuum lamination method, the heat curing process (process 4) can be carried out in an unpressed state, and can also be carried out at atmospheric pressure, so that the gas is less likely to escape, and the gas is easily accumulated inside, and the metal foil is easily bulged.
[0093] Below, according to Figure 1 The details of this embodiment are described below. Of course, this embodiment is not limited to Figure 1 .
[0094] As described above, the manufacturing method of the present embodiment is a method for manufacturing a metal foil-clad laminate. In the metal foil-clad laminate in the present embodiment, a resin composite sheet C comprising a metal foil and a resin composition layer disposed on one side of the aforementioned metal foil is laminated on the surface of a circuit substrate A comprising an insulating layer and a conductor circuit layer. In the present embodiment, when such a metal foil-clad laminate is manufactured, a vacuum laminating device is used to improve mass production. By using a vacuum laminating device, it is possible to manufacture continuously, and the laminating process (the process of embedding the resin composition in the circuit substrate to make it close, mainly the time required in process 2 can be shortened, so mass production is excellent.
[0095] <Process 1>
[0096] Step 1 includes a step of reducing the content of water and / or solvent contained in circuit substrate A to obtain circuit substrate B ( Figure 1(1)). Circuit substrate A includes an insulating layer and a conductor circuit layer. The insulating layer usually contains organic matter, and contains water and residual solvent. In the present embodiment, for circuit substrate A, by obtaining circuit substrate B with a reduced content of water and / or solvent, the peeling caused by the bulging of the metal foil in the later-described step 4 can be effectively suppressed. That is, circuit substrate A will naturally absorb water or retain residual solvent. The moisture and / or solvent will evaporate in step 4 and become a gas. On the other hand, in the present embodiment, because the resin composite sheet stacked with the circuit substrate contains metal foil, the aforementioned gas is not easy to penetrate, thereby causing bulging and peeling of the metal foil and the resin composition layer of the resin composite sheet. In the present embodiment, by including a process of obtaining a circuit substrate B with a reduced content of water and / or solvent contained in circuit substrate A, such bulging can be effectively suppressed. In addition, the time of vacuum lamination can be shortened, thereby improving mass productivity.
[0097] In the present embodiment, the mass reduction rate of the circuit substrate B relative to the circuit substrate A is preferably 0.01% by mass or more, more preferably 0.05% by mass or more, and further preferably 0.10% by mass or more. By making the mass reduction rate above the lower limit, there is a tendency to effectively suppress the amount of gas generated from the circuit substrate B during heating (especially during the thermal curing process). In addition, the upper limit of the mass reduction rate of the circuit substrate B relative to the circuit substrate A is not particularly limited, but is preferably 5% or less, more preferably 3% or less, and further preferably 2% or less.
[0098] Here, the mass reduction rate of the circuit board B relative to the circuit board A is defined as [(mass of the circuit board A-mass of the circuit board B) / mass of the circuit board A]×100 (unit: mass %).
[0099] The total amount of water and solvent contained in the circuit board B is calculated based on the area of the circuit board B per 1 cm 2 The lower limit of the total amount of water and solvent contained in the circuit board B is not particularly limited, and the total amount of water and solvent contained in the circuit board B is preferably 0.25 mg or less, more preferably 0.15 mg or less, and further preferably 0.10 mg or less. 2 Specifically, for example, in the case of a substrate with a size of 515×415 mm, the total amount of water and solvent contained in the circuit substrate B is 0.001 mg or more per 1 cm area of the circuit substrate B. 2 , expressed as [actual mass of water content and solvent content (mg) / (51.5cm×41.5cm)].
[0100] Here, the total amount of water and solvent contained in the circuit board B is a value when the total amount of water and solvent after the circuit board A is heated at the heating temperature and heating time in step 4 is set to 0.
[0101] It should be noted that the resin composition layer included in the resin composite sheet may also contain water and / or solvent, but the inventors have found out through research that the amount of water and / or solvent from the resin composition layer is much less than that contained in the circuit substrate A. This is because the thickness of the resin composition layer is usually very thin. Therefore, it can be seen that the moisture content of the circuit substrate A has a great influence on the ridges.
[0102] The reason for this is presumably because the thickness of the resin composite sheet C is relatively thin and therefore the content of water and / or solvent is small.
[0103] In the present embodiment, it is preferable that the step 1 includes an operation of obtaining the circuit board B having a reduced water content in the circuit board A. The reason for this is that the water content in the circuit board A can be more easily affected.
[0104] As a method for obtaining a circuit substrate B with a reduced content of water and / or solvent contained in the circuit substrate A, heating under atmospheric pressure, drying under reduced pressure or vacuum, heating under reduced pressure or vacuum, drying using a desiccant, etc. are exemplified. In the present embodiment, heating under atmospheric pressure can be cited as an example.
[0105] In step 1, the temperature when the circuit substrate A is heated or dried is preferably 30°C or more, more preferably 50°C or more, further preferably 80°C or more, further preferably 90°C or more, further preferably 100°C or more, further preferably 110°C or more, and more preferably 120°C or more. By making the aforementioned temperature above the aforementioned lower limit, there is a tendency to more effectively reduce the content of water and / or solvent contained in the circuit substrate A. In addition, the temperature when the circuit substrate A is heated or dried under atmospheric pressure is preferably 200°C or less, more preferably 185°C or less, further preferably 170°C or less, and further preferably 155°C or less. By making the aforementioned temperature below the aforementioned upper limit, there is a tendency to effectively suppress the deterioration of the conductor circuit.
[0106] The temperature during heating or drying in step 1 may be a constant temperature, or may be increased and / or decreased during the process. In heating or drying in step 1, when the temperature is increased and / or decreased, it is preferred that the average value of each temperature is within the above range.
[0107] In step 1, the temperature and pressure during heating or drying are preferably substantially constant except at the beginning (e.g., when heating or drying starts) and the end (e.g., when heating or drying ends) of step 1. Substantially constant means that the fluctuation range of the temperature and pressure except at the beginning and the end is within ±10%.
[0108] The temperature during heating or drying in step 1 is preferably the same as or lower than the heating temperature in step 2. Specifically, the heating or drying temperature is preferably 5 to 40°C lower than the heating temperature in step 2. However, when step 1 is performed under a condition where the surface of the conductor circuit layer is difficult to oxidize, such as in a nitrogen atmosphere, the heating or drying in step 1 may be performed at a temperature higher than the heating temperature in step 2.
[0109] In addition, as the drying time when heating or drying at atmospheric pressure, it is preferably more than 30 minutes, more preferably more than 60 minutes, more preferably more than 120 minutes, more preferably more than 180 minutes, and more preferably more than 240 minutes. By making the aforementioned drying time more than the aforementioned lower limit, there is a tendency that the reduction effect of the content of the moisture and / or solvent contained in the circuit substrate A is more improved. In addition, as the drying time when drying at atmospheric pressure, it is preferably less than 600 minutes, more preferably less than 540 minutes, more preferably less than 480 minutes, more preferably less than 420 minutes, and more preferably less than 360 minutes. By making the aforementioned drying time less than the aforementioned upper limit, there is a tendency that the deterioration of the conductor circuit can be more effectively suppressed.
[0110] Furthermore, by performing step 1 under reduced pressure or vacuum, the drying time can be shortened.
[0111] In the present embodiment, it is preferable to further include an operation of making the circuit board B obtained in step 1 less likely to absorb moisture.
[0112] By making the circuit board B obtained in step 1 less likely to absorb moisture, the effect of the present embodiment can be more effectively exhibited.
[0113] As an operation to make the circuit board B obtained in step 1 less likely to absorb moisture, for example, step 2 is performed immediately after step 1. That is, the circuit board B may absorb moisture when stored after being obtained, but by performing step 2 immediately after obtaining the circuit board B, a metal foil-clad laminate can be manufactured before the circuit board absorbs moisture again, thereby effectively suppressing the peeling of the metal foil.
[0114] Here, "immediately after" means that after obtaining the circuit substrate B in step 1, the circuit substrate B is not stored and the process is continuously transferred to step 2. More specifically, for example, after obtaining the circuit substrate in step 1, the process is transferred to step 2 within 2 hours, further within 90 minutes, and particularly within 10 minutes.
[0115] In addition, as another example of the operation to make the circuit substrate B obtained in step 1 less likely to absorb moisture, for example, the circuit substrate B obtained in step 1 is stored in an atmosphere that is less likely to absorb moisture before performing step 2. This is useful in the case where the circuit substrate B cannot be immediately transferred to step 2 after obtaining it. As a method of storing the circuit substrate B in an atmosphere that is less likely to absorb moisture, for example, it can be stored in an atmosphere containing a desiccant.
[0116] <Process 2>
[0117] Step 2 includes the following operations: placing a resin composite sheet C including a metal foil and a resin composition layer disposed on one side of the metal foil on at least one surface of the circuit substrate B in such a manner that the resin composition layer side contacts the circuit substrate B, and applying pressure from the metal foil side under heating and reduced pressure or vacuum to obtain a laminated substrate D in which the resin composite sheet C is laminated on at least one surface of the circuit substrate B ( Figure 1 In this embodiment, step 2 is performed by a vacuum laminating device, so that the laminated substrate D can be obtained efficiently in a short time. The resin composite sheet C may be arranged on only one side of the circuit substrate B, but is preferably arranged on both sides of the circuit substrate B.
[0118] The step 2 includes, for example, a step also referred to as CIP (Cold Isostatic Press) or rubber press.
[0119] In step 2, the circuit board B and the resin composite sheet C are placed in a vacuum laminator and then pressurized under heating and reduced pressure or vacuum.
[0120] In step 2, lamination of the circuit board B and the resin composite sheet C is performed under reduced pressure or vacuum (for example, 5.0 hPa or less, further 1.0 hPa or less, or vacuum).
[0121] The heating temperature in step 2 is preferably 80°C or more, more preferably 90°C or more, further preferably 100°C or more, more preferably 110°C or more, and further preferably 120°C or more. By making the aforementioned heating temperature above the aforementioned lower limit, the embedding property of the resin composition between the conductor circuits can be further improved. The heating temperature in step 2 is preferably below 190°C, more preferably below 180°C, further preferably below 170°C, more preferably below 160°C, and further preferably below 150°C. By making the aforementioned heating temperature below the aforementioned upper limit, the effect of suppressing excessive flow of the resin composition tends to be further improved. Furthermore, it is also possible to effectively suppress the thinning of the thickness of the resin composition layer caused by the resin composition flowing out from the end of the laminate due to the decrease in the melt viscosity of the resin composition.
[0122] The heating temperature in step 2 may be a constant temperature, or may be increased and / or decreased in the middle of the step. In the heating in step 2, when the temperature is increased and / or decreased, it is preferred that the average value of each temperature is within the above range.
[0123] In step 2, pressure is applied from the metal foil side. The pressure at this time is preferably 3 kgf / cm 2 More preferably 7kgf / cm 2 More preferably, 9 kgf / cm 2 Above, 10kgf / cm 2 By making the pressure above the lower limit, the embedding property of the resin composition in the circuit tends to be further improved. In addition, the pressure is preferably 30 kgf / cm 2 Below, more preferably 25kgf / cm 2 Below, more preferably 20kgf / cm 2 Below, 15kgf / cm2 is also possible 2 When the pressure is set to be equal to or less than the upper limit value, there is a tendency that excessive flow of the resin composition can be effectively suppressed.
[0124] The time of heating and pressurizing in process 2 is preferably more than 5 seconds, more preferably more than 10 seconds, more preferably more than 15 seconds, more preferably more than 20 seconds, and more preferably more than 25 seconds. By making the aforementioned time above the aforementioned lower limit, there is a tendency for the embedding property of the resin composition to the circuit to be improved. In addition, the time of heating and pressurizing in process 2 is preferably less than 10 minutes, more preferably less than 7 minutes, more preferably less than 5 minutes, more preferably less than 3 minutes, and more preferably less than 60 seconds. By making the aforementioned time below the aforementioned upper limit, there is a tendency to more effectively suppress excessive flow of the resin composition.
[0125] The pressurization in step 2 may be constant, or the pressure may be varied during the step. When the pressure is varied in step 2, it is preferred that the average value of each pressure is within the above range.
[0126] In step 2, the temperature during heating and the pressure during pressurization are preferably substantially constant except at the beginning (e.g., when rubber pressing starts) and the end (e.g., when rubber pressing ends) of step 2. Substantially constant means that the fluctuation range of the temperature and pressure except at the beginning and the end is within ±10%.
[0127] <Process 3>
[0128] Step 3 includes the following operations: using a pressing metal plate or a laminating metal roller, heating and pressing the metal foil side surface of the laminated substrate D obtained in step 2 to smooth the surface of the resin composition layer of the laminated substrate D to obtain a laminated substrate E ( Figure 1 (3)).
[0129] In step 3, the resin composition of the resin composition layer is mainly semi-cured while being fully incorporated into the circuit board B, thereby smoothing the surface of the resin composition layer.
[0130] Step 3 includes, for example, a step called flat pressing.
[0131] In step 3, heating and pressurization may be performed while a protective film having a larger surface area than the resin composite sheet C and a smoother surface is further sandwiched between the pressing metal plate or the laminating metal roller. By setting such a configuration, contamination of the device can be effectively suppressed. In particular, by using a protective film, the circuit substrate can be appropriately conveyed, and contamination of the pressing metal plate or the metal roller can be effectively suppressed.
[0132] Step 3 may be performed under atmospheric pressure, or under reduced pressure or vacuum. In one embodiment, step 3 is performed under atmospheric pressure. In addition, when step 3 is performed under reduced pressure or vacuum, for example, it may be performed under 5.0 Pa or below, or further under 1.0 Pa, or it may be performed under vacuum.
[0133] The heating temperature in step 3 is preferably 80°C or more, more preferably 90°C or more, further preferably 100°C or more, more preferably 110°C or more, further preferably 120°C or more, and may be 130°C or more, or 140°C or more. By making the aforementioned heating temperature above the aforementioned lower limit, there is a tendency that the surface energy of the resin composition layer can be smoother. The heating temperature in step 3 is preferably 190°C or less, more preferably 180°C or less, further preferably 170°C or less, more preferably 160°C or less, further preferably 155°C or less, and may be 150°C or less. By making the aforementioned heating temperature below the aforementioned upper limit, there is a tendency that the excessive flow of the resin composition can be effectively suppressed.
[0134] The heating temperature in step 3 may be a constant temperature, or may be increased and / or decreased in the middle of the step. In the heating in step 3, when the temperature is increased and / or decreased, it is preferred that the average value of each temperature is within the above range.
[0135] The pressure in step 3 is preferably 3 kgf / cm 2 More preferably 7kgf / cm 2 More preferably, 9 kgf / cm 2Above, 10kgf / cm 2 By making the pressure above the lower limit value, there is a tendency to effectively smooth the surface of the resin composition layer. In addition, the pressure in step 3 is preferably 30 kgf / cm 2 Below, more preferably 25kgf / cm 2 Below, more preferably 20kgf / cm 2 Below, 15kgf / cm2 is also possible 2 By setting the pressure to be equal to or less than the upper limit value, there is a tendency that excessive flow of the resin composition can be effectively suppressed.
[0136] The pressurization in step 3 may be constant, or the pressure may be varied during the step. When the pressure is varied in step 3, it is preferred that the average value of each pressure is within the above range.
[0137] In step 3, the temperature during heating and the pressure during pressurization are preferably approximately constant except for the initial stage (for example, when the flat pressing starts) and the final stage (for example, when the flat pressing ends) of step 3. Approximately constant means that the fluctuation range of the temperature and pressure except for the initial stage and the final stage is within ±10%.
[0138] The time of heating and pressurizing in process 3 is preferably more than 5 seconds, more preferably more than 10 seconds, more preferably more than 15 seconds, more preferably more than 20 seconds, more preferably more than 25 seconds, and further, more than 35 seconds, more than 45 seconds, and more than 50 seconds. By making the aforementioned time above the aforementioned lower limit, there is a tendency to make the surface of the resin composition layer more effectively smoothed. In addition, the time of heating and pressurizing in process 3 is preferably less than 10 minutes, more preferably less than 5 minutes, and more preferably less than 3 minutes. By making the aforementioned time below the aforementioned upper limit, there is a tendency to effectively suppress the excessive flow of the resin composition.
[0139] The heating in step 3 may be constant heating, or the temperature may be varied during the step. In step 3, when the temperature is varied, it is preferred that the average value of each temperature is within the above range.
[0140] <Step 4>
[0141] In the method for producing a metal foil-clad laminate according to the present embodiment, in addition to the above-mentioned steps 1 to 3, it is preferred that the following step be performed after the above-mentioned step 3.
[0142] Step 4: A step of heating the laminated substrate E obtained in the step 3 to cure the resin composition layer, thereby obtaining a cured substrate F.
[0143] Step 4 is, for example, Figure 1The process shown in (4).
[0144] According to step 4, the semi-cured resin composition layer can be sufficiently cured.
[0145] Step 4 includes, for example, a step called post-baking.
[0146] In step 4, heating is usually performed using a dryer or the like.
[0147] The heating temperature in step 4 is preferably 100°C or more, more preferably 110°C or more, further preferably 120°C or more, more preferably 130°C or more, and further preferably 140°C or more. By making the heating temperature above the lower limit, the resin composition layer can be sufficiently cured. The heating temperature in step 4 is preferably 250°C or less, more preferably 240°C or less, further preferably 230°C or less, further preferably 225°C or less, and further preferably 220°C or less. By making the heating temperature below the upper limit, there is a tendency to suppress thermal damage to the circuit substrate.
[0148] The heating temperature in step 4 may be a constant temperature, or may be increased and / or decreased in the middle of the step. In the heating in step 4, when the temperature is increased and / or decreased, it is preferred that the average value of each temperature is within the above range.
[0149] The time of heating in operation 4 is preferably more than 15 minutes, more preferably more than 30 minutes, more preferably more than 60 minutes, more preferably more than 90 minutes, and more preferably more than 100 minutes. By setting it to more than the aforementioned lower limit, the resin composition layer can be fully cured. In addition, the time of heating and pressurization in operation 4 is preferably less than 10 hours, more preferably less than 7 hours, and more preferably less than 5 hours. By setting it to less than the aforementioned upper limit, the thermal damage to the circuit substrate can be further suppressed.
[0150] The heating in step 4 may be constant heating or may be varied in the middle of the step. In step 4, when the temperature is varied, it is preferred that the average value of each temperature is within the above range.
[0151] The heating in operation 4 is preferably carried out by heating up in stages (particularly divided into 2 stages or 3 stages, preferably divided into 2 stages). By being set to such a structure, the moisture and / or solvent in the circuit substrate B that cannot be removed in operation 1 can be fully vaporized in the first heating, and in addition, the moisture and / or solvent contained in the moisture of operation 2 and later hygroscopicity, the resin composition layer, etc. can also be effectively removed. And, the resin composition layer can be fully cured in the second heating. As a result, the protuberance of metal foil can be more effectively suppressed, and the peeling between the resin composition layer and the metal foil can also be effectively suppressed. In particular, the residual trace moisture, solvent can be more effectively suppressed to be violently vaporized to cause protuberance. In addition, the protuberance of the interface of circuit substrate and resin composition layer, the peeling accompanying this can also be effectively suppressed.
[0152] For example, when the content of the inorganic filler in the resin composition layer is high or when the water content in the resin composition layer is high, the swelling of the metal foil can be more effectively suppressed by performing step-by-step heating.
[0153] When the heating in step 4 is performed by stepwise temperature increase, the temperature of the first heating is preferably 100°C or more, more preferably 110°C or more, further preferably 120°C or more, more preferably 130°C or more, further preferably 140°C or more, and may be 145°C or more. By making the temperature of the first heating above the lower limit, there is a tendency to easily and slowly remove the moisture and / or solvent in the laminated substrate E. In addition, the temperature of the first heating is preferably 180°C or less, more preferably 170°C or less, further preferably 160°C or less, and more preferably 155°C or less. By making the temperature of the first heating below the upper limit, there is a tendency to easily and slowly remove the moisture and / or solvent in the laminated substrate E.
[0154] In addition, the time of the first heating is preferably more than 10 minutes, more preferably more than 20 minutes, more preferably more than 30 minutes, more preferably more than 40 minutes, and more preferably more than 50 minutes. In addition, the time of the first heating is preferably less than 5 hours, more preferably less than 4 hours, and more preferably less than 2 hours. By being set to below the aforementioned upper limit, there is a tendency that can effectively suppress the thermal damage to the circuit substrate.
[0155] When the heating in step 4 is performed by stepwise temperature increase, the temperature of the second heating is preferably higher than 180°C, more preferably higher than 190°C, further preferably higher than 200°C, more preferably higher than 210°C, and further preferably higher than 215°C. By making the temperature of the second heating higher than the aforementioned lower limit, the resin composition layer can be more fully cured. The temperature of the second heating is preferably lower than 250°C, more preferably lower than 240°C, further preferably lower than 230°C, and further preferably lower than 225°C. By making the temperature of the second heating lower than the aforementioned upper limit, there is a tendency to effectively suppress thermal damage to the circuit substrate.
[0156] In addition, the time of the first heating is preferably more than 20 minutes, more preferably more than 40 minutes, more preferably more than 60 minutes, more preferably more than 80 minutes, and more preferably more than 100 minutes. In addition, the time of the first heating is preferably less than 7 hours, more preferably less than 5 hours, and more preferably less than 3 hours. By making the time of the first heating be below the aforementioned upper limit, there is a tendency to effectively suppress the thermal damage to the circuit substrate.
[0157] In step 4, when the temperature is raised in stages, the temperature of the second heating is preferably higher than the temperature of the first heating, and more preferably 10°C or more higher than the temperature of the first heating. By making the temperature difference between the first heating and the second heating (the temperature of the second heating - the temperature of the first heating) be 10°C or more, the resin composition layer can be more fully cured. The temperature difference between the first heating and the second heating is further preferably 20°C or more, more preferably 35°C or more, more preferably 50°C or more, and more preferably 60°C or more. The upper limit of the temperature difference between the first heating and the second heating is preferably 110°C or less, more preferably 100°C or less, more preferably 90°C or less, more preferably 80°C or less, and more preferably 75°C or less. By setting it below the aforementioned upper limit, there is a tendency to effectively suppress thermal damage to the circuit substrate.
[0158] It should be noted that the first heating and the second heating in this embodiment are not necessarily the initial heating and the subsequent heating in step 4. For example, the case where preheating is further performed before the first heating, the case where the temperature is increased while heating between the first heating and the second heating, and the case where post-heating is further performed after the second heating are also included in this embodiment.
[0159] Step 4 is generally carried out under atmospheric pressure.
[0160] In addition, in the present embodiment, the mass reduction rate of the laminated substrate E based on heating in step 4 is preferably 1.0 mass% or less. As a method for reducing the amount of gas generated from the laminated substrate E in this way, the content of water and / or solvent contained in the circuit substrate A is reduced, and the circuit substrate B is arranged in a vacuum lamination device in a state where it is not easy to absorb moisture.
[0161] The mass reduction rate is more preferably 0.5 mass % or less, and further preferably 0.1 mass % or less, relative to the mass of the laminated substrate E before heating. By making the mass reduction rate below the upper limit, there is a tendency to effectively suppress peeling in step 4. It is ideal that the lower limit of the mass reduction rate is 0 mass %, but even if it is 0.01 mass % or more of the mass of the laminated substrate E, the necessary performance can be fully exhibited.
[0162] The mass reduction rate of the laminated substrate E due to heating in step 4 is defined as [(mass of the laminated substrate E before heating - mass of the laminated substrate E after heating) / mass of the laminated substrate E before heating]×100 (unit: mass %).
[0163] The mass reduction rate was calculated by measuring the mass before and after heating using an electronic balance.
[0164] <Other Process>
[0165] The method for manufacturing the metal foil-clad laminate of the present embodiment may further include repeating steps 2 to 4 on the aforementioned cured substrate F. By repeating steps 2 to 4, a printed circuit board with a multilayer structure can be obtained. In addition, when the resin composite sheet C has a carrier substrate as described in detail below, it is preferred to peel off the carrier substrate ( Figure 1 (5)) and then repeat steps 2 to 4. The number of times steps 2 to 4 are repeated can be determined according to the desired number of conductor circuit layers, for example, generally 2 to 10 times. In addition, for the aforementioned cured substrate F, the formation of a photoresist layer, etching, copper plating and other processes can be combined to form a conductor circuit layer. The formation of the conductor circuit layer can adopt a known method (for example: semi-additive method, etc.).
[0166] <Metal foil-clad laminate>
[0167] The metal foil-clad laminate obtained by the method of this embodiment is formed by laminating a resin composite sheet C on the surface of a circuit substrate A, wherein the resin composite sheet C comprises a metal foil and a resin composition layer disposed on one side of the metal foil, and the circuit substrate A comprises an insulating layer and a conductor circuit layer.
[0168] The following, based on Figure 3 The metal foil-clad laminate will be described. Figure 3: It is a cross-sectional schematic diagram showing the layer structure of the metal foil-clad laminate in the present embodiment, and resin composite sheets C / C are provided on both sides of the circuit substrate B. The circuit substrate B is provided with an insulating layer 11 and a conductor circuit layer 12 / 12 provided on both sides of the insulating layer 11. The insulating layer 11 is formed of an insulating material, usually an organic material containing a resin (preferably a thermosetting resin), and preferably more than 80% by mass of the insulating layer 11 is a thermosetting resin. The insulating layer 11 is an organic material, so the solvent used when the insulating layer is formed or the conductor circuit layer is formed is easy to remain or absorb moisture. The organic material is not particularly limited, and a composition for forming an insulating layer of a printed circuit board can generally be suitably used.
[0169] The thickness of the insulating layer 11 is, for example, not less than 30 μm and not more than 1000 μm.
[0170] On the other hand, the conductor circuit layer 12 is made of a conductive metal, such as copper. The thickness of the conductor circuit layer 12 (average thickness of a portion where the conductor circuit is provided) is, for example, not less than 1 μm and not more than 100 μm.
[0171] Insulation layer( Figure 3 The surface roughness of the insulating layer 11) in the insulation layer (specifically, the surface roughness of the surface in contact with the conductor circuit layer) is not particularly limited, and the roughness Rz of the insulating layer surface measured in accordance with JIS B0601:2013 is preferably adjusted to 0.2 to 7.0 μm. By making the roughness Rz of the insulating layer surface greater than 0.2 μm, the roughness of the insulating layer surface becomes a moderate size, and there is a tendency for the bonding strength between the conductor circuit layer and the insulating layer to be further improved. On the other hand, by making the roughness Rz of the insulating layer surface less than 7.0 μm, the roughness of the conductor circuit layer formed on the insulating layer becomes a moderate size, and there is a tendency for the transmission characteristics of the conductor circuit to be further improved. The roughness Rz of the insulating layer surface can be appropriately selected based on the balance of the bonding strength between the conductor circuit layer and the insulating layer and the transmission characteristics of the conductor circuit, so it is not particularly limited. It is more preferably above 0.5μm, further preferably above 0.6μm, and particularly preferably above 0.7μm. Depending on the purpose, etc., it can also be above 4.5μm, more preferably below 5.5μm, further preferably below 4.0μm, more preferably below 3.5μm, further preferably below 3.0μm, and particularly preferably below 2.0μm.
[0172] Then, a resin composite sheet C including a metal foil and a resin composition layer disposed on one side of the metal foil is provided on the surface of the circuit board B. Figure 3The resin composite sheet C shown includes a resin composition layer 13, a metal foil 14, and a carrier substrate 15 in this order from the side close to the circuit board B. The details of the resin composite sheet are preferably as described in the section <Resin composite sheet C> described later.
[0173] The total thickness of the metal foil laminate (after process 4) obtained in the present embodiment is preferably 50 μm or more, more preferably 80 μm or more, further preferably 100 μm or more, more preferably 120 μm or more, and further preferably 160 μm or more. By setting it to above the aforementioned lower limit, there is a tendency for good operability. In addition, the layer thickness of the metal foil laminate (after process 4) is preferably 2000 μm or less, more preferably 1800 μm or less, further preferably 1600 μm or less, more preferably 1400 μm or less, and further preferably 1200 μm or less. By setting it to below the aforementioned upper limit, there is a tendency to effectively reduce the residual moisture and solvent amount in the circuit substrate.
[0174] In addition, the total thickness of the metal foil laminate (after process 4, when the conductor circuit layer is 1 layer) obtained in the present embodiment, excluding the carrier substrate, is preferably 50 μm or more, more preferably 80 μm or more, further preferably 100 μm or more, more preferably 120 μm or more, and further preferably 140 μm or more. By setting it to above the aforementioned lower limit, there is a tendency to improve operability. In addition, the total thickness of the metal foil laminate (after process 4, when the conductor circuit layer is 1 layer) excluding the carrier substrate is preferably 2000 μm or less, more preferably 1800 μm or less, further preferably 1600 μm or less, more preferably 1400 μm or less, and further preferably 1200 μm or less. By setting it to below the aforementioned upper limit, there is a tendency to effectively reduce the amount of residual moisture and solvent in the circuit substrate.
[0175] <Resin composite sheet C>
[0176] In this embodiment, the resin composite sheet C may be composed of only a metal foil and a resin composition layer disposed on one side of the metal foil, or may have other layers. Figure 3 As shown in (1), the resin composition layer 13 and the metal foil 14 may be used alone. Figure 3 As shown in (2), in addition to the resin composition layer 13 and the metal foil 14, a carrier substrate 15 is also provided. In this embodiment, by providing the carrier substrate 15, there is a tendency for the operability to be improved. In addition, other layers (adhesive layer, roughening treatment layer, heat-resistant treatment layer, rust-proof treatment layer and silane coupling agent layer, etc.) may also be included between the metal foil 14 and the carrier substrate 15. In this embodiment, the resin composite sheet C preferably has a carrier substrate 15 in addition to the resin composition layer 13 and the metal foil 14.
[0177] That is, a preferred example of the present embodiment is a form in which the resin composite sheet C has a carrier substrate, a metal foil, and a resin composition layer in this order.
[0178] metal foil( Figure 3 The metal foil 14) in the above-mentioned embodiment can be a single-layer metal foil or a multi-layer metal foil, and is usually a single-layer metal foil. The metal foil is preferably thin. The thickness of the metal foil is, for example, 0.5 μm or more and 40 μm or less. By setting the thickness to be above the above-mentioned lower limit, there is a tendency for the operability to be improved. In addition, by setting the thickness to be below the above-mentioned upper limit, there is a tendency for the etching property to be further improved.
[0179] In particular, when the resin composite sheet C has a carrier substrate, the thickness of the metal foil is preferably 0.8 μm or more, more preferably 1.0 μm or more, and further preferably 1.2 μm or more. In addition, it is preferably 3 μm or less, more preferably 2.5 μm or less, and further preferably 2.0 μm or less. It can also be 1.8 μm or less. By setting it to be above the aforementioned lower limit, there is a tendency for the operability to be improved. In addition, by setting it to be below the aforementioned upper limit, there is a tendency for the etching property to be further improved.
[0180] On the other hand, when the resin composite sheet C does not have a carrier substrate, the thickness of the metal foil is preferably 7 μm or more, more preferably 9 μm or more, and preferably 40 μm or less, more preferably 36 μm or less. In particular, when the resin composite sheet C does not have a carrier substrate, by making the thickness of the metal foil 7 μm or more, the production management of the metal foil manufacturer tends to be easier, and the operability of the metal foil-clad laminate during further processing can be improved.
[0181] The surface roughness of the metal foil (specifically, the surface roughness of the surface in contact with the resin composition layer) is not particularly limited, but it is preferred to adjust the roughness Rz of the metal foil surface measured in accordance with JIS B0601:2013 to 0.2 to 7.0 μm. By making the roughness Rz of the metal foil surface 0.2 μm or more, the roughness of the metal foil surface becomes an appropriate size, and the metal foil peel strength tends to be further improved. On the other hand, by making the roughness Rz of the metal foil surface 7.0 μm or less, the roughness of the metal foil surface becomes an appropriate size, and the dielectric loss tangent characteristics of the obtained cured product tend to be further improved. The roughness Rz of the copper foil surface can be appropriately selected for the balance between the metal foil peel strength and the dielectric loss tangent characteristics, and is therefore not particularly limited, but is more preferably 0.5 μm or more, further preferably 0.6 μm or more, and particularly preferably 0.7 μm or more. Depending on the application, it may also be 4.5 μm or more. In addition, it is more preferably 5.5 μm or less, further preferably 4.0 μm or less, more preferably 3.5 μm or less, further preferably 3.0 μm or less, and particularly preferably 2.0 μm or less.
[0182] The metal foil is not particularly limited as long as it is a base material containing a metal that can become a wiring (conductor circuit) of a printed circuit board (hereinafter also referred to as a wiring board). For example, from the viewpoint of increasing the signal transmission speed, copper foil is preferably used as the metal foil. The aforementioned copper foil only needs to contain copper, and for example, a foil-shaped base material formed of copper or a copper alloy can be cited. As the aforementioned copper alloy, for example, an alloy containing copper and containing at least one selected from the group consisting of nickel, phosphorus, tungsten, arsenic, molybdenum, chromium, cobalt and zinc can be cited.
[0183] The aforementioned copper foil is not particularly limited, but from the viewpoint of being able to increase the transmission speed of the signal and the viewpoint of being able to reduce the transmission loss, the crystal grain size of copper or copper-containing alloy is preferably larger. Specifically, the copper foil preferably contains crystal grains with a maximum grain size of 5 μm or more of the crystal grain size of the copper or copper-containing alloy, and more preferably contains crystal grains of 10 μm or more. In addition, the area occupied by the crystal grains with a maximum grain size of 5 μm or more is preferably 20% by area, and more preferably 40% by area. In addition, here, the maximum grain size refers to the longest diameter (major axis diameter) of each of the crystal grains of copper or copper-containing alloy.
[0184] As a method for measuring the crystal grain size of the copper foil, reference may be made to the description in paragraph 0155 of International Publication No. 2021-079817, the contents of which are incorporated herein.
[0185] As described above, the metal foil is preferably copper foil. Generally speaking, the copper foil used for rigid substrates and the like is electrolytic copper foil, and the copper foil used for flexible substrates and the like is rolled copper foil. However, in recent years, especially with the booming market for flexible substrates, electrolytic copper foils with properties comparable to rolled copper foils have been developed. Currently, rolled copper foils and electrolytic copper foils can be used regardless of the type of substrate. Therefore, the copper foil used in this embodiment is not limited to rolled copper foil or electrolytic copper foil, and any copper foil can be used.
[0186] In the metal foil, various treatments may also be applied to a foil-shaped substrate (metal foil substrate) containing a metal that can become a wiring of a wiring board. Such treatments are not particularly limited as long as they are applied to the metal foil, and examples thereof include roughening treatment, heat-resistant treatment, rust-proof treatment, and silane coupling agent treatment. The metal foil 14 may be one that has been subjected to any treatment, or one that has been subjected to a combination of two or more treatments. In addition, when two or more of the aforementioned treatments are applied, it is preferred that the roughening treatment, heat-resistant treatment, rust-proof treatment, and silane coupling agent treatment be applied in this order.
[0187] That is, in one example of the embodiment of the resin composite sheet C in the present embodiment, in addition to the metal foil and the resin composition layer, the roughening treatment layer, the heat resistance treatment layer, the rust prevention treatment layer, and the silane coupling agent treatment layer are included.
[0188] The roughening treatment may be a roughening treatment generally performed when manufacturing metal foil, and is not particularly limited. For example, a treatment of forming roughening particles on the surface of the metal foil substrate as the object to be treated may be mentioned. Through such a roughening treatment, when the metal foil is copper foil, the surface of the copper foil will be covered with roughening particles containing copper or copper alloy.
[0189] As an example of a roughening layer, for example, one can cite a layer composed of fine metal particles with a particle size of 40 to 200 nm. More specifically, the content of copper particles with a particle size of 40 to 200 nm contained in the roughening layer is preferably 90% or more, and more preferably 95% or more. It should be noted that the particle size referred to here is observed at a magnification of 80,000 times using a field emission scanning electron microscope FE-SEM (JSM-7800F manufactured by JEOL Ltd.) with the sample stage tilted 40°, and the height of the observed metal particles is taken as the value of the particle size. For the particle size of the fine copper particles in the roughening layer, it is preferably observed by the above method, and the maximum value of the measurement range is 200 nm and the minimum value is 40 nm.
[0190] The roughening layer can be formed by electrolytic plating. The particle size of the fine copper particles is strongly affected by the composition of the plating bath and the electrolytic current density. For example, when the electrolytic current density is high, the particle size of the roughening particles tends to decrease, and conversely, when the electrolytic current density is low, the particle size of the roughening particles tends to increase. Therefore, in order to obtain roughening particles of the target particle size, it is preferred to appropriately set the electrolytic current density.
[0191] The bath composition and electrolysis conditions for forming the roughened copper layer can be referred to the description in paragraphs 0106 to 0108 of International Publication No. 2020-162056, the contents of which are incorporated into this specification.
[0192] The heat-resistant treatment mentioned above is not particularly limited as long as it is a heat-resistant treatment generally performed when manufacturing metal foil, and examples thereof include treatments for forming a heat-resistant treatment layer containing a single substance or an alloy of nickel, cobalt, copper, and zinc. Even if the region formed by such a heat-resistant treatment is not completely layered, it is also referred to as a heat-resistant treatment layer. The metal foil mentioned above may also be formed with a layer (heat-resistant treatment layer) formed by the heat-resistant treatment mentioned above.
[0193] More specifically, it is preferred that the heat-resistant treatment layer contains nickel or nickel and phosphorus, and the amount of nickel deposited in the heat-resistant treatment layer is 30 to 60 mg / m 2 .
[0194] By setting the nickel deposition amount to 30 to 60 mg / m 2 , which can more effectively improve the transmission characteristics and the above-mentioned basic characteristics. The more preferred range of nickel deposition amount is 40 to 50 mg / m 2 Here, "attachment amount" refers to the mass of nickel per unit area deposited by plating (e.g., electrolytic plating) on the roughening treatment layer side of the metal foil. The attachment amount can be measured by, for example, dissolving and diluting the treated copper foil with nitric acid or the like, and analyzing the nickel concentration using an ICP emission spectrometer.
[0195] The heat-resistant treatment layer is preferably composed of nickel (Ni), or nickel (Ni) and phosphorus (P).
[0196] More specifically, the heat-resistant treatment layer is a second surface treatment layer formed after the roughening treatment layer is formed, and can be formed by electrolytic plating. The amount of nickel deposited can be adjusted by the current conditions during the electrolytic plating.
[0197] For examples of bath composition and electrolysis conditions for forming a heat-resistant treatment layer composed of nickel and phosphorus, reference can be made to paragraphs 0115 to 0116 of International Publication No. 2020-162056, the contents of which are incorporated herein.
[0198] The above-mentioned rust-proof treatment may be a rust-proof treatment generally performed when manufacturing metal foil, and is not particularly limited, but is preferably a treatment for forming a rust-proof treatment layer containing nickel. In addition, as the above-mentioned rust-proof treatment, for example, chromate treatment may be cited. Even if the area formed by the rust-proof treatment is not completely layered, it is also called a rust-proof treatment layer. The metal foil 14 may also be formed with a layer (rust-proof treatment layer) formed by the rust-proof treatment.
[0199] More specifically, the rust-proof treatment layer is usually a surface treatment layer of the third layer formed after the above-mentioned heat-resistant treatment layer is formed, and can be formed by electrolytic plating. The bath composition for forming the rust-proof treatment layer can be a known composition, for example, a bath composition containing hexavalent chromium such as chromic acid, sodium dichromate, potassium dichromate, etc. It should be noted that the precipitation form of chromium after the rust-proof treatment layer is formed is a state mixed with Cr(OH)3 and Cr2O3, and it is not precipitated in the form of hexavalent chromium that has adverse effects on the human body but in the form of trivalent chromium. The chromic acid solution can be alkaline or acidic.
[0200] In addition, as the alkaline chromic acid solution, an alkaline zinc chromate solution containing zinc ions and hexavalent chromium ions disclosed in Japanese Patent Publication No. 58-15950 can be used. By using this chromic acid solution, the rust prevention property of the rust-proofing layer can be further improved than that formed by a chromic acid solution alone.
[0201] As for the electrolytic bath and electrolytic conditions for implementing the rust-proof treatment layer, for example, reference can be made to the description in paragraph 0122 of International Publication No. 2020-162056, the contents of which are incorporated into this specification.
[0202] The aforementioned silane coupling agent treatment can be a rust-proof treatment commonly performed when manufacturing metal foil, and is not particularly limited. For example, a treatment in which a silane coupling agent is applied to the surface of a metal foil substrate as a treated object, etc. can be cited. As a silane coupling agent treatment, it is also possible to dry or heat the silane coupling agent after applying the silane coupling agent. By treating with a silane coupling agent, the alkoxy group possessed by the silane coupling agent reacts and bonds with the metal constituting the treated object. The area formed by the bonded silane coupling agent is a silane coupling agent treatment layer. The metal foil 14 can also be a layer formed by a silane coupling agent treatment (silane coupling agent treatment layer).
[0203] More specifically, the silane coupling agent treatment layer is usually a surface treatment layer of the fourth layer formed after the above-mentioned rust-proof treatment layer is formed, and is a layer provided to further improve the adhesion between the resin composition layer and the metal foil. By further providing a silane coupling agent treatment layer, not only can the peel strength be improved, but also the degradation of the peel strength after a severe test can be suppressed, and further the rust resistance can be improved, thereby achieving a metal foil for circuit boards with excellent versatility.
[0204] The silane coupling agent treatment layer can be formed by adding an appropriate amount of silane coupling agent to water, etc., applying it in the form of an aqueous solution by dipping treatment or spraying treatment, washing with water, and drying. The silane coupling agent can be selected from a variety of groups such as epoxy, amino, mercapto, vinyl, methacryloxy, and styrene. However, since each has different characteristics and different compatibility with the substrate, it is necessary to select it appropriately.
[0205] Preferred examples of the silane coupling agent include, for example, a silane coupling agent having an amino group in the molecule and a silane coupling agent having a carbon-carbon unsaturated double bond in the molecule. For details of the silane coupling agent having an amino group in the molecule and the silane coupling agent having a carbon-carbon unsaturated double bond in the molecule, reference may be made to paragraphs 0165 to 0168 of International Publication No. 2021-079817, the contents of which are incorporated herein.
[0206] As a bath for forming a silane coupling agent treatment layer, for example, the composition and conditions shown below can be referred to the description in paragraph 0125 of International Publication No. 2020-162056, the contents of which are incorporated into this specification.
[0207] The resin composite sheet C comprising such a metal foil, a roughening treatment layer, a heat-resistant treatment layer, a rust-proof treatment layer, a silane coupling agent treatment layer and a resin composition layer can be manufactured, for example, with reference to the descriptions in paragraphs 0126 and 0127 of International Publication No. 2020-162056, the contents of which are incorporated into this specification.
[0208] As an embodiment of the resin composite sheet C in the present embodiment, the following method is illustrated: in the resin composite sheet C, the amount of the first nickel element measured by XPS in the surface (contact surface) of the metal foil (preferably copper foil) in contact with the resin composition layer is less than 4.5 atomic % relative to the total amount of elements measured by XPS, and when the surface in contact with the aforementioned resin composition layer is sputtered at a speed of 3 nm / minute in terms of SiO2 for 1 minute, the amount of the second nickel element in the surface measured by XPS is less than 4.5 atomic % relative to the total amount of elements measured by XPS.
[0209] It should be noted that the surface of the metal foil in contact with the resin composition layer refers to: the surface of the metal foil and the surface of the side in contact with the resin composition layer. Specifically, for the surface of the metal foil in contact with the resin composition layer, when the resin composite sheet C is manufactured by laminating the metal foil and the resin composition layer, it refers to the surface of the metal foil in contact with the resin composition layer and the surface before contacting the resin composition layer. The surface in contact with the resin composition layer is also referred to as the contact surface in this specification. In addition, the surface in contact with the resin composition layer is sputtered for 1 minute under the condition of a speed of 3nm / minute in terms of SiO2 conversion, which refers to the position of the sputtering from the contact surface before contacting the resin composition layer. That is, the surface in contact with the resin composition layer is sputtered for 1 minute under the condition of a speed of 3nm / minute in terms of SiO2 conversion, which refers to the position after sputtering from the contact surface for 1 minute under the condition of a speed of 3nm / minute in terms of SiO2 conversion, and is sometimes referred to as such below. It should be noted that the sputtering here is sputtering under vacuum. Therefore, the resin composite sheet C is preferably produced using a metal foil having nickel element amounts in the contact surface and the position measured by XPS within the above ranges as the metal foil.
[0210] As described above, in the aforementioned metal foil, the first nickel element amount measured by XPS in the aforementioned contact surface is usually 4.5 atomic % or less relative to the total element amount measured by XPS, preferably 3.5 atomic % or less, and more preferably 2.5 atomic % or less. In addition, as described above, the second nickel element amount measured by XPS in the position after sputtering for 1 minute under the condition of a speed of 3nm / minute calculated from the aforementioned contact surface in terms of SiO2 is 4.5 atomic % or less relative to the total element amount measured by XPS, preferably 4.0 atomic % or less, and more preferably 3.0 atomic % or less. In addition, the arithmetic mean of the aforementioned first nickel element amount and the aforementioned second nickel element amount is preferably 3.0 atomic % or less, more preferably 2.5 atomic % or less, and further preferably 2.0 atomic % or less. If the aforementioned first nickel element amount is too little or the aforementioned second nickel element amount is too little, the insulation reliability is reduced, and in the wiring board manufactured by the metal foil laminate, there is a tendency that the ion migration between adjacent wirings cannot be fully suppressed. Therefore, the first nickel element amount and the second nickel element amount are preferably as small as possible, but in fact, the limit is about 0.1 atomic % respectively. Therefore, it is preferred that the first nickel element amount and the second nickel element amount are 0.1 to 4.5 atomic % relative to the total element amount measured by XPS. In addition, the arithmetic mean of the first nickel element amount and the second nickel element amount is preferably 0.5 to 3.0 atomic %.
[0211] In addition, as XPS, a general X-ray photoelectron spectroscopy can be used for measurement. Specifically, PHI 5000 Versaprobe manufactured by ULVAC-PHI, Inc. can be used to irradiate a sample with X-rays in a vacuum and perform measurement.
[0212] The surface (contact surface) on the side in contact with the resin composition layer preferably contains nitrogen that can be confirmed by XPS. It should be noted that the nitrogen that can be confirmed by XPS means that the amount of nitrogen is above the detection limit of XPS, specifically, it is above 0.05 atomic %. In addition, in the contact surface, the amount of nitrogen measured by XPS is preferably above 2.0 atomic %, more preferably above 2.5 atomic %, and further preferably above 3.0 atomic % relative to the total amount of elements measured by XPS. If a compound containing the nitrogen element is present on the contact surface, the insulation reliability is higher. On the other hand, if the amount of nitrogen element is too small, there is a tendency that the effect of improving the insulation reliability due to the presence of the nitrogen element cannot be fully exerted. Therefore, although the amount of nitrogen element is as high as possible, in fact, about 7.0 atomic % is the limit. Therefore, the amount of nitrogen element is preferably 2.0 to 7.0 atomic %.
[0213] The aforementioned nitrogen element is preferably derived from a nitrogen atom contained in a compound having an amino group, and more preferably derived from a nitrogen atom contained in a silane coupling agent having an amino group. The aforementioned nitrogen element is derived from a nitrogen atom contained in a compound having an amino group, and it is considered that the compound containing the aforementioned nitrogen-containing element is a compound having an amino group. As such a metal foil, specifically, it is considered to be a metal foil having a layer treated with a silane coupling agent having an amino group in the molecule as a silane coupling agent layer. In addition, for the compound having an amino group, that is, a silane coupling agent having an amino group in the molecule, it is considered that the effect of improving insulation reliability can be more effectively exerted. Therefore, it is believed that a resin composite sheet C that can appropriately manufacture a wiring board with higher insulation reliability can be obtained.
[0214] In the surface (contact surface) on the side in contact with the resin composition layer, and in the position after sputtering for 1 minute under the condition of a speed of 3 nm / minute calculated from the contact surface in terms of SiO2, as an element that can be confirmed by XPS, in addition to nickel (Ni) element and nitrogen (N) element, there may also be one or more selected from copper (Cu) element, carbon (C) element, oxygen (O) element, silicon (Si) element, chromium (Cr) element, zinc (Zn) element and cobalt (Co) element, etc. The amount of each of these elements is preferably, for example, 0 to 90 atomic %, more preferably 0 to 80 atomic %, and further preferably 0 to 70 atomic % relative to the total amount of elements determined by XPS.
[0215] The first nickel element amount and the second nickel element amount can be adjusted by, for example, adjusting the rust-proof layer containing nickel in the coating layer, the thickness of the nickel-containing layer, the nickel concentration in the nickel-containing layer, and the like.
[0216] The nitrogen element may be present by using a layer containing a silane coupling agent having an amino group in its molecule as a silane coupling agent layer. Furthermore, the amount of nitrogen element (amount of nitrogen element) may be adjusted by adjusting the thickness of the layer containing a silane coupling agent having an amino group in its molecule as a silane coupling agent layer.
[0217] The average roughness of the surface (contact surface) on the side in contact with the resin composition layer is 2.0 μm or less, preferably 1.8 μm or less, and more preferably 1.5 μm or less, in terms of ten-point average roughness. When the surface roughness of the contact surface of the metal foil in contact with the resin composition layer is low, it is believed that the smoothness of the contact surface between the wiring and the resin composition layer is also higher, which is preferred from the perspective of being able to reduce the loss during signal transmission. Even if the surface roughness of the contact surface is low, a ten-point average roughness Rz of about 0.2 μm is more practical. In addition, if the surface roughness of the contact surface is too low, it is believed that the smoothness of the contact surface between the metal foil and the resin composition layer will become too high, and the adhesion between the metal foil and the resin composition layer tends to decrease. From this point of view, the surface roughness of the contact surface is preferably 0.2 μm or more in terms of ten-point average roughness Rz. Therefore, for the surface roughness of the contact surface, it is preferably 0.2 μm or more in terms of ten-point average roughness Rz, more preferably 0.5 μm or more, and further preferably 0.6 μm or more.
[0218] In the aforementioned metal foil, the surface with a large average roughness, i.e., the so-called M surface, is the surface on the side in contact with the aforementioned resin composition layer. That is, in the aforementioned metal foil, its M surface is the aforementioned contact surface. And, the M surface side may be formed with a coating layer as described above. The surface with a small average roughness, i.e., the so-called S surface, of the aforementioned copper foil may be formed with a coating layer as described above in the same manner as the M surface, but may also be formed with only the aforementioned antirust layer, or may not be formed with the aforementioned coating layer.
[0219] The details of the metal foil, roughening treatment layer, heat-resistant treatment layer, rust-proof treatment layer and silane coupling agent treatment layer, and other layers used in the resin composite sheet C of this embodiment, in addition to the above, as long as it does not depart from the subject matter of the present invention, can refer to the records of International Publication No. 2021 / 079819, International Publication No. 2021-079817, International Publication No. 2020-230870, and International Publication No. 2020-162056, and their contents are introduced into this specification.
[0220] Resin composition layer ( Figure 3The resin composition layer 13) is formed by a resin composition. The resin composition preferably contains a thermosetting resin, and the content of the inorganic filler is 0 to 250 parts by mass relative to 100 parts by mass of the resin solid content contained in the aforementioned resin composition. If a resin composition with a small content of inorganic filler or no inorganic filler is used, the proportion of the highly hygroscopic inorganic filler is reduced, thereby more effectively suppressing the peeling of the resin composition layer and the metal foil.
[0221] The details of the composition of the resin composition are preferably the same as those described in the section <Resin composition> described later.
[0222] The thickness of the resin composition layer is, for example, 5 μm or more, preferably 10 μm or more, more preferably 15 μm or more, further preferably 20 μm or more, more preferably 25 μm or more, and preferably 100 μm or less, more preferably 80 μm or less, further preferably 60 μm or less, further preferably 50 μm or less, more preferably 40 μm or less, and particularly preferably 35 μm or less. By setting it to above the lower limit, there is a tendency to improve insulation reliability. In addition, by setting it to below the upper limit, there is a tendency to reduce the thickness of the product.
[0223] As a carrier substrate ( Figure 3 The carrier substrate 15 in the embodiment of the present invention is exemplified by metal foil and resin film, preferably metal foil, more preferably copper foil. When the carrier substrate is copper foil, it is also often referred to as carrier copper foil. As the resin film, reference may be made to the description of paragraph 0031 of International Publication No. 2017 / 086418, the contents of which are incorporated into this specification.
[0224] The thickness of the carrier substrate is, for example, 5 μm or more, preferably 8 μm or more, and is 100 μm or less, preferably 50 μm or less, more preferably 30 μm or less, and further preferably 30 μm or less.
[0225] The total thickness of the resin composite sheet (before process 4) used in this embodiment is preferably 5 μm or more, more preferably 6 μm or more, further preferably 7 μm or more, more preferably 8 μm or more, and further preferably 9 μm or more. By setting it above the aforementioned lower limit, there is a tendency for the insulation reliability to be further improved. In addition, the total thickness of the resin composite sheet (before process 4) is preferably 30 μm or less, more preferably 25 μm or less, further preferably 20 μm or less, more preferably 15 μm or less, and further preferably 10 μm or less. By setting it below the aforementioned upper limit, there is a tendency to reduce the thickness of the product.
[0226] In addition, the total thickness of the resin composite sheet (before process 4) used in this embodiment, excluding the carrier substrate, can be appropriately determined according to the purpose. As an example, the total thickness of the resin composite sheet (before process 4) used in this embodiment, excluding the carrier substrate, is preferably 5 μm or more, more preferably 6 μm or more, further preferably 7 μm or more, more preferably 8 μm or more, and further preferably 9 μm or more. By setting it to above the aforementioned lower limit μm, there is a tendency for the insulation reliability to be further improved. In addition, the total thickness of the resin composite sheet (before process 4) used in this embodiment, excluding the carrier substrate, is preferably 30 μm or less, more preferably 25 μm or less, further preferably 20 μm or less, more preferably 15 μm or less, and further preferably 10 μm or less. By setting it to below the aforementioned upper limit μm, there is a tendency to reduce the thickness of the product.
[0227] <Resin composition>
[0228] The resin composition of this embodiment is used to manufacture a metal foil-clad laminate by a method using a vacuum lamination device and including the following steps, wherein the metal foil-clad laminate is formed by laminating a resin composite sheet C on the surface of a circuit substrate A, the resin composite sheet C includes a metal foil and a resin composition layer arranged on a single surface of the aforementioned metal foil, the circuit substrate A includes an insulating layer and a conductor circuit layer, the resin composition includes a thermosetting resin, and the content of the inorganic filler is 0 to 250 parts by mass relative to 100 parts by mass of the resin solid component contained in the aforementioned resin composition.
[0229] Step 1: a step of reducing the content of water and / or solvent contained in the circuit substrate A to obtain the circuit substrate B;
[0230] Step 2: a step of arranging a resin composite sheet C including a metal foil and a resin composition layer arranged on one side of the metal foil on at least one surface of a circuit substrate B in such a manner that the resin composition layer side is in contact with the circuit substrate B, and applying pressure from the metal foil side under heating and reduced pressure or vacuum to obtain a laminated substrate D in which the resin composite sheet C is laminated on at least one surface of the circuit substrate B;
[0231] Step 3: A step of obtaining a laminated substrate E by heating and pressing the metal foil side surface of the laminated substrate D obtained in step 2 using a pressing metal plate or a laminating metal roll to smooth the surface of the resin composition layer of the laminated substrate D.
[0232] That is, the resin composition in the present embodiment is preferably a resin composition used in the method for producing the metal-clad laminate. Therefore, the method for producing the metal-clad laminate has the same meaning as that described in the section "Method for producing the metal-clad laminate".
[0233] Hereinafter, the resin composition will be described in detail.
[0234] <<Thermosetting resin>>
[0235] The resin composition of the present embodiment usually contains a thermosetting resin. The thermosetting resin preferably contains at least one selected from the group consisting of a polymer having a structural unit represented by formula (V), a polyphenylene ether compound having a carbon-carbon unsaturated double bond at the terminal, a maleimide compound, a cyanate compound, an epoxy compound, a phenol compound, an oxetane resin, a benzoxazine compound, and an alkenyl-substituted nadic imide compound.
[0236]
[0237] (In formula (V), Ar represents an aromatic hydrocarbon linking group. * represents a bonding position.)
[0238] <<<Polymer having a structural unit represented by formula (V)>>>
[0239] The resin composition of this embodiment preferably contains a polymer having a structural unit represented by formula (V). By containing a polymer having a structural unit represented by formula (V), a resin composition excellent in low dielectric properties (low dielectric constant, low dielectric loss tangent) can be obtained.
[0240]
[0241] (In formula (V), Ar represents an aromatic hydrocarbon linking group. * represents a bonding position.)
[0242] The aromatic hydrocarbon linking group may refer to a group consisting only of an aromatic hydrocarbon optionally having a substituent, or may refer to a group consisting of a combination of an aromatic hydrocarbon optionally having a substituent and other linking groups, preferably a group consisting only of an aromatic hydrocarbon optionally having a substituent. It should be noted that the substituent optionally possessed by the aromatic hydrocarbon may include a substituent Z (e.g., an alkyl group having 1 to 6 carbon atoms, an alkenyl group having 2 to 6 carbon atoms, an alkynyl group having 2 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, a hydroxyl group, an amino group, a carboxyl group, a halogen atom, etc.). In addition, the above aromatic hydrocarbon is preferably unsubstituted.
[0243] The aromatic hydrocarbon linking group is usually a divalent linking group.
[0244] The aromatic hydrocarbon linking group specifically includes phenylene, naphthalene diyl, anthracene diyl, phenanthrene diyl, biphenyl diyl, and fluorene diyl, which may have a substituent, and among them, phenylene which may have a substituent is preferred. The substituent may be exemplified by the above-mentioned substituent Z, but the above-mentioned phenylene group is preferably unsubstituted.
[0245] The structural unit represented by formula (V) more preferably includes at least one of the structural unit represented by the following formula (V1), the structural unit represented by the following formula (V2), and the structural unit represented by the following formula (V3). It should be noted that the * in the following formula represents a bonding position. In addition, the structural units represented by formulas (V1) to (V3) are sometimes collectively referred to as "structural units (a)".
[0246]
[0247] In formulas (V1) to (V3), L 1 It is an aromatic hydrocarbon linking group (the carbon number is preferably 6 to 22, more preferably 6 to 18, and further preferably 6 to 10). Specifically, phenylene, naphthalene diyl, anthracene diyl, phenanthrene diyl, biphenyl diyl, and fluorene diyl, which may have a substituent, are listed, among which phenylene which may have a substituent is preferred. The substituent may be exemplified by the substituent Z mentioned above, but the phenylene group is preferably unsubstituted.
[0248] As the compound forming the structural unit (a), a divinyl aromatic compound is preferably used, and examples thereof include divinylbenzene, bis(1-methylvinyl)benzene, divinylnaphthalene, divinylanthracene, divinylbiphenyl, divinylphenanthrene, etc. Among them, divinylbenzene is particularly preferred. One of these divinyl aromatic compounds can be used, or two or more can be used as required.
[0249] As described above, the polymer having the structural unit represented by formula (V) may be a homopolymer of the structural unit (a) or a copolymer with a structural unit derived from other monomers.
[0250] When the polymer having the structural unit shown in formula (V) is a copolymer, for its copolymerization ratio, the structural unit (a) is preferably 3 mol% or more, more preferably 5 mol% or more, further preferably 10 mol% or more, and may be 15 mol% or more. As the upper limit, it is preferably 90 mol% or less, more preferably 85 mol% or less, further preferably 80 mol% or less, more preferably 70 mol% or less, further preferably 60 mol% or less, more preferably 50 mol% or less, further preferably 40 mol% or less, particularly preferably 30 mol% or less, further, it may be 25 mol% or less, 20 mol% or less.
[0251] As the structural unit derived from other monomers, there can be exemplified a structural unit (b) derived from an aromatic compound having one vinyl group (monovinyl aromatic compound).
[0252] The structural unit (b) derived from a monovinyl aromatic compound is preferably a structural unit represented by the following formula (V4).
[0253]
[0254] In formula (V4), L 2 is an aromatic hydrocarbon linking group, and preferred specific examples thereof include the above-mentioned L 1 Example.
[0255] R V1 R is a hydrogen atom or a hydrocarbon group having 1 to 12 carbon atoms (preferably an alkyl group). V1 When it is a hydrocarbon group, the carbon number is preferably 1 to 6, more preferably 1 to 3. V1 and L 2 It may have the above-mentioned substituent Z.
[0256] When the polymer having the structural unit represented by formula (V) is a copolymer containing the structural unit (b) derived from a monovinyl aromatic compound, examples of the monovinyl aromatic compound include: vinyl aromatic compounds such as styrene, vinyl naphthalene, and vinyl biphenyl; core alkyl-substituted vinyl aromatic compounds such as o-methylstyrene, m-methylstyrene, p-methylstyrene, o-, p-dimethylstyrene, o-ethylvinylbenzene, m-ethylvinylbenzene, p-ethylvinylbenzene, methylvinylbiphenyl, and ethylvinylbiphenyl. The monovinyl aromatic compound exemplified here may also have the above-mentioned appropriate substituent Z. In addition, these monovinyl aromatic compounds may be used alone or in combination of two or more.
[0257] When the polymer having the structural unit shown in formula (V) is a copolymer comprising structural unit (b), the copolymerization ratio of structural unit (b) is preferably 10 mol% or more, more preferably 15 mol% or more, further, it can be 20 mol% or more, 30 mol% or more, 40 mol% or more, 50 mol% or more, 60 mol% or more, 70 mol% or more, 75 mol% or more. As the upper limit, it is preferably 98 mol% or less, more preferably 90 mol% or less, and more preferably 85 mol% or less.
[0258] The polymer having the structural unit shown in formula (V) may also have other structural units other than structural unit (a) and structural unit (b). As other structural units, for example, structural unit (c) derived from cycloolefin compounds can be cited. As cycloolefin compounds, hydrocarbons having double bonds in the ring structure can be cited. Specifically, monocyclic cyclic olefins such as cyclobutene, cyclopentene, cyclohexene, and cyclooctene can be cited. In addition, compounds having a norbornene ring structure such as norbornene and dicyclopentadiene can also be cited; cycloolefin compounds formed by aromatic ring condensation such as indene and acenaphthene. As examples of norbornene compounds, the contents described in paragraphs 0037 to 0043 of Japanese Patent Publication No. 2018-39995 can be cited, and the contents are introduced into this specification. It should be noted that the cycloolefin compounds exemplified here may further have the above-mentioned substituent Z.
[0259] When the polymer having the structural unit shown in formula (V) is a copolymer comprising structural unit (c), the copolymerization ratio of structural unit (c) is preferably 10 mol% or more, more preferably 20 mol% or more, and further preferably 30 mol% or more. As the upper limit, it is preferably 90 mol% or less, more preferably 80 mol% or less, further preferably 70 mol% or less, and can be 50 mol% or less, or 30 mol% or less.
[0260] In the polymer having the structural unit represented by formula (V), a structural unit (d) derived from a different polymerizable compound (hereinafter, also referred to as other polymerizable compounds) may be further introduced. As other polymerizable compounds (monomers), for example, compounds containing three vinyl groups may be cited. Specifically, 1,3,5-trivinylbenzene, 1,3,5-trivinylnaphthalene, 1,2,4-trivinylcyclohexane may be cited. Alternatively, ethylene glycol diacrylate, butadiene, etc. may be cited. The copolymerization ratio of the structural unit (d) derived from other polymerizable compounds is preferably 30 mol% or less, more preferably 20 mol% or less, and further preferably 10 mol% or less.
[0261] As an embodiment of the polymer having the structural unit represented by formula (V), a polymer having structural unit (a) as an essential component and containing at least one of structural units (b) to (d) can be exemplified. Furthermore, a mode in which the total of structural units (a) to (d) accounts for 95 mol% or more of all structural units can be exemplified, and a mode in which the total of structural units (a) to (d) accounts for 98 mol% or more can be further exemplified.
[0262] As another embodiment of the polymer having the structural unit represented by formula (V), it is preferably a polymer having the structural unit (a) as an essential component and wherein the structural units containing aromatic rings account for 90 mol % or more of all the structural units except the terminal, more preferably a polymer containing 95 mol % or more of the structural units containing aromatic rings, and it may also be a polymer containing 100 mol % of the structural units containing aromatic rings.
[0263] When calculating the mol % relative to all structural units, one structural unit is derived from one molecule of a monomer (eg, a divinyl aromatic compound, a monovinyl aromatic compound, etc.) used in the production of a polymer having the structural unit represented by formula (V).
[0264] The method for producing the polymer having the structural unit shown in formula (V) is not particularly limited, and can be prepared according to a common method, for example, by polymerizing a raw material comprising a divinyl aromatic compound (a monovinyl aromatic compound, a cycloolefin compound, etc. may be coexisted as required) in the presence of a Lewis acid catalyst. As the Lewis acid catalyst, a metal fluoride such as boron trifluoride or a complex thereof may be used.
[0265] The structure of the chain end of the polymer having the structural unit represented by formula (V) is not particularly limited, but when explaining the group derived from the above-mentioned divinyl aromatic compound, the structure of the following formula (E1) can be cited. 1 The same as those defined in the above formula (V1). * indicates a bonding position.
[0266] *-CH=CH-L 1 -CH=CH2 (E1)
[0267] When the group derived from the monovinyl aromatic compound is a chain end, the structure of the following formula (E2) may be used. 2 and R V1 They have the same meanings as those defined in the aforementioned formula (V4). * indicates a bonding position.
[0268] *-CH=CH-L 2 -R V1 (E2)
[0269] The molecular weight of the polymer having the structural unit represented by formula (V) is preferably 300 or more, more preferably 500 or more, further preferably 1,000 or more, and even more preferably 1,500 or more in terms of number average molecular weight Mn. The upper limit is preferably 130,000 or less, more preferably 120,000 or less, further preferably 110,000 or less, and even more preferably 100,000 or less.
[0270] The molecular weight of the polymer having the structural unit shown in formula (V) is preferably 1,000 or more, more preferably 1,500 or more, more preferably 2,000 or more, more preferably 2,500 or more, further preferably 3,000 or more, and may also be 3,500 or more, 4,000 or more. By setting it to above the aforementioned lower limit, the excellent low dielectric properties of the polymer having the structural unit shown in formula (V), especially Df, the dielectric properties after moisture absorption can be more effectively exerted in the cured product of the resin composition. As an upper limit, it is preferably 160,000 or less, more preferably 150,000 or less, further preferably 140,000 or less, more preferably 130,000 or less, and may also be 120,000 or less, 110,000 or less. By setting it to below the aforementioned upper limit, there is a tendency that it is not easy to cause poor filling when the prepreg or resin composite sheet is laminated on the circuit substrate.
[0271] The monodispersity (Mw / Mn) represented by the ratio of the weight average molecular weight Mw to the number average molecular weight Mn is preferably 100 or less, more preferably 50 or less, and still more preferably 20 or less. The lower limit is more practically 1.1 or more, and may be 5 or more, 7 or more, and even 10 or more to satisfy the required performance.
[0272] The above-mentioned Mw and Mn are measured according to the description in the Examples described later.
[0273] When the resin composition of the present embodiment contains two or more polymers having a structural unit represented by formula (V), it is preferred that Mw, Mn, and Mw / Mn of the mixture satisfy the above ranges.
[0274] The equivalent of the vinyl group of the polymer having the structural unit shown in formula (V) is preferably 200 g / eq. or more, more preferably 230 g / eq. or more, further preferably 250 g / eq. or more, and may be 300 g / eq. or more, 350 g / eq. or more. In addition, the equivalent of the vinyl group is preferably 1200 g / eq. or less, more preferably 1000 g / eq. or less, and may be 800 g / eq. or less, 600 g / eq. or less, 500 g / eq. or less, 400 g / eq. or less, 350 g / eq. or less. By setting it to above the above lower limit, there is a tendency to improve the storage stability of the resin composition and to improve the fluidity of the resin composition. Therefore, there is a tendency to improve formability, and it is not easy to generate voids when forming prepregs, etc., and a more reliable printed circuit board can be obtained. On the other hand, by setting it to below the above upper limit, there is a tendency to improve the heat resistance of the obtained cured product.
[0275] In addition, for the polymer with the structural unit shown in formula (V) used in the present embodiment, it is preferred that the low dielectric properties of its cured product are excellent. For example, the relative dielectric constant (Dk) at 10GHz measured by the cavity resonance perturbation method of the cured product of the polymer with the structural unit shown in formula (V) used in the present embodiment is preferably less than 2.80, more preferably less than 2.60, further preferably less than 2.50, and more preferably less than 2.40. In addition, the lower limit of the aforementioned relative dielectric constant is, for example, more than 1.80 and more practical. In addition, the dielectric loss tangent (Df) at 10GHz measured by the cavity resonance perturbation method of the cured product of the polymer with the structural unit shown in formula (V) used in the present embodiment is preferably less than 0.0030, more preferably less than 0.0020, and more preferably less than 0.0010. In addition, the lower limit of the aforementioned dielectric loss tangent is, for example, more than 0.0001 and more practical.
[0276] The relative dielectric constant (Dk) and the dielectric loss tangent (Df) were measured by the following method.
[0277] 4.5 g of resin powder was spread on a stainless steel mold frame of 100 mm × 30 mm × 1.0 mm high, set in a vacuum press (produced by Kitagawa Seiki Co., Ltd.), maintained at 200°C, 220°C and 240°C for 1.5 hours, and pressed at a surface pressure of 1.9 MPa to produce a cured plate.
[0278] The cured plate was miniaturized to a width of 1.0 mm and dried at 120° C. for 60 minutes, and then the relative dielectric constant (Dk) and dielectric loss tangent (Df) after drying were measured at 10 GHz using a perturbation cavity resonator. The measurement temperature was 23° C.
[0279] As the perturbation method cavity resonator, Agilent 8722ES manufactured by Agilent Technologies was used.
[0280] For the polymer having a structural unit represented by formula (V) in this specification, reference can be made to the compounds and their synthesis reaction conditions described in paragraphs 0029 to 0058 of International Publication No. 2017 / 115813, the compounds and their synthesis reaction conditions described in paragraphs 0013 to 0058 of Japanese Patent Publication No. 2018-039995, and the compounds and their synthesis reaction conditions described in paragraphs 0008 to 0043 of Japanese Patent Publication No. 2018-168347. The synthesis reaction conditions thereof, the compounds and their synthesis reaction conditions described in paragraphs 0014 to 0042 of JP-A-2006-070136, the compounds and their synthesis reaction conditions described in paragraphs 0014 to 0061 of JP-A-2006-089683, the compounds and their synthesis reaction conditions described in paragraphs 0008 to 0036 of JP-A-2008-248001, and the like are incorporated into the present specification.
[0281] When the resin composition of the present embodiment includes a polymer with a structural unit shown in formula (V), for the content of the polymer with the structural unit shown in formula (V), when the resin solids in the resin composition is set to 100 mass parts, it is preferably more than 1 mass part, and preferably less than 70 mass parts. For the lower limit of the content of the polymer with the structural unit shown in formula (V), when the resin solids in the resin composition is set to 100 mass parts, it is more preferably more than 3 mass parts, more preferably more than 5 mass parts, and can also be more than 10 mass parts. By making the content of the polymer with the structural unit shown in formula (V) be more than the above-mentioned lower limit, low dielectric properties, particularly low relative dielectric constant, can be effectively achieved. On the other hand, for the upper limit of the content of the polymer with the structural unit shown in formula (V), when the resin solids in the resin composition is set to 100 mass parts, it is preferably less than 60 mass parts, more preferably less than 50 mass parts, more preferably less than 40 mass parts, more preferably less than 30 mass parts, and can also be less than 20 mass parts, less than 15 mass parts. By setting it to the said upper limit value or less, the metal foil peeling strength of the hardened|cured material obtained can be improved effectively.
[0282] The resin composition may contain only one polymer having a structural unit represented by formula (V), or two or more polymers thereof. When the resin composition contains two or more polymers, the total amount is preferably within the above range.
[0283] <<<Polyphenylene ether compound having a carbon-carbon unsaturated double bond at the terminal>>>
[0284] The resin composition of the present embodiment may contain a polyphenylene ether compound having (preferably containing two or more) carbon-carbon unsaturated double bonds at the terminal.
[0285] The polyphenylene ether compound having a carbon-carbon unsaturated double bond at the end is preferably a polyphenylene ether compound having two or more groups selected from the group consisting of (meth)acryloyl, maleimide and vinylbenzyl at the end. In addition, it is also preferably a polyphenylene ether compound having two or more groups shown in formula (Rx-1) and / or formula (Rx-2) described later at the end. By using these polyphenylene ether compounds, there is a tendency to more effectively improve the dielectric properties and low water absorption of printed circuit boards, etc.
[0286] The following describes their details.
[0287] Examples of the polyphenylene ether compound having a carbon-carbon unsaturated double bond at a terminal include compounds having a phenylene ether skeleton represented by the following formula (X1).
[0288]
[0289] (In formula (X1), R 24 , R 25 , R 26 and R 27 may be the same or different and represent an alkyl group, an aryl group, a halogen atom or a hydrogen atom having 6 or less carbon atoms.
[0290] The polyphenylene ether compound having a carbon-carbon unsaturated double bond at a terminal may further contain a repeating unit represented by formula (X2) and / or a repeating unit represented by formula (X3).
[0291]
[0292] (In formula (X2), R 28 , R 29 , R 30 , R 34 and R 35 R may be the same or different and represent an alkyl group having 6 or less carbon atoms or a phenyl group. 31 , R 32 and R 33 They may be the same or different and are a hydrogen atom, an alkyl group having 6 or less carbon atoms, or a phenyl group.)
[0293]
[0294] (In formula (X3), R 36 , R 37 , R 38 , R 39 , R 40 , R 41 , R 42 and R 43They may be the same or different and are a hydrogen atom, an alkyl group having 6 or less carbon atoms, or a phenyl group. -A- is a linear, branched, or cyclic divalent hydrocarbon group having 20 or less carbon atoms. )
[0295] The polyphenylene ether compound containing more than 2 carbon-carbon unsaturated double bonds at the end is preferably a modified polyphenylene ether compound (hereinafter, sometimes referred to as "modified polyphenylene ether compound (g)") in which a part or all of the terminal is functionalized by ethylenic unsaturated groups, more preferably a modified polyphenylene ether compound having more than 2 groups selected from the group consisting of (meth) acryloyl, maleimide, (meth) allyl and vinyl benzyl at the end, and further preferably a modified polyphenylene ether compound having more than 2 groups selected from the group consisting of (meth) acryloyl, maleimide and vinyl benzyl at the end. Alternatively, it is also preferred to have a modified polyphenylene ether compound having more than 2 groups shown in the formula (Rx-1) and / or formula (Rx-2) described later at the end. By adopting such a modified polyphenylene ether compound (g), the dielectric loss tangent (Df) of the cured product of the resin composition can be further reduced, and low water absorption and metal foil peeling strength can be improved. They can use 1 or more than 2 in combination.
[0296] Examples of the modified polyphenylene ether compound (g) include polyphenylene ether compounds represented by formula (OP).
[0297]
[0298] (In formula (OP), X represents an aromatic group, -(YO) n1 - represents a polyphenylene ether structure, n1 represents an integer of 1 to 100, and n2 represents an integer of 1 to 4. Rx is a group represented by formula (Rx-1) or formula (Rx-2).
[0299]
[0300] (In formula (Rx-1) and formula (Rx-2), R 1 , R 2 and R 3 Each independently represents a hydrogen atom, an alkyl group, an alkenyl group or an alkynyl group. * represents a bonding site with an oxygen atom. Mc each independently represents a hydrocarbon group having 1 to 12 carbon atoms. z represents an integer of 0 to 4. r represents an integer of 1 to 6.
[0301] When n1 and / or n2 are integers greater than 2, n1 structural units (YO) and / or n2 structural units may be the same as or different from each other. n2 is preferably 2 or greater, and more preferably 2.
[0302] In formula (Rx-1) and formula (Rx-2), R 1 , R 2 and R 3Each independently represents a hydrogen atom, an alkyl group, an alkenyl group or an alkynyl group.
[0303] R 1 It is preferably a hydrogen atom or an alkyl group, more preferably a hydrogen atom or a methyl group, and still more preferably a hydrogen atom.
[0304] R 2 and R 3 Each independently is preferably a hydrogen atom or an alkyl group, more preferably a hydrogen atom or a methyl group, and further preferably a hydrogen atom.
[0305] As R 1 , R 2 and R 3 The carbon number of the alkyl, alkenyl or alkynyl group is preferably 5 or less, more preferably 3 or less.
[0306] In the formula (Rx-1), r represents an integer of 1 to 6, preferably an integer of 1 to 5, more preferably an integer of 1 to 4, further preferably an integer of 1 to 3, further preferably 1 or 2, and even more preferably 1.
[0307] In formula (Rx-1), Mc each independently represents a hydrocarbon group having 1 to 12 carbon atoms, preferably a hydrocarbon group having 1 to 10 carbon atoms, more preferably a straight-chain or branched alkyl group having 1 to 10 carbon atoms, further preferably a methyl group, ethyl group, isopropyl group, isobutyl group, tert-butyl group, pentyl group, octyl group or nonyl group, and even more preferably a methyl group, ethyl group, isopropyl group, isobutyl group or tert-butyl group.
[0308] In the formula (Rx-1), z represents an integer of 0 to 4, preferably an integer of 0 to 3, more preferably an integer of 0 to 2, further preferably 0 or 1, and even more preferably 0.
[0309] A specific example of the group represented by the formula (Rx-1) is a vinylbenzyl group, and a specific example of the group represented by the formula (Rx-2) is a (meth)acryloyl group.
[0310] Examples of the modified polyphenylene ether compound (g) include compounds represented by formula (OP-1).
[0311]
[0312] (In formula (OP-1), X represents an aromatic group, -(YO)n2- represents a polyphenylene ether structure, and R 1 , R 2 and R 3 Each independently represents a hydrogen atom, an alkyl group, an alkenyl group or an alkynyl group, n1 represents an integer of 1 to 6, n2 represents an integer of 1 to 100, and n3 represents an integer of 1 to 4.)
[0313] When n2 is an integer greater than 2, and regarding n3, n2 structural units (YO) and / or n3 structural units may be the same or different. n3 is preferably 2 to 4, and more preferably 2.
[0314] The modified polyphenylene ether compound (g) in the present embodiment is preferably a compound represented by formula (OP-2).
[0315]
[0316] Here, -(OXO)- is preferably represented by Formula (OP-3) and / or Formula (OP-4).
[0317]
[0318] (In formula (OP-3), R 4 , R 5 , R 6 , R 10 and R 11 may be the same or different and are an alkyl group having 6 or less carbon atoms or a phenyl group. 7 , R 8 and R 9 They may be the same or different and are a hydrogen atom, an alkyl group having 6 or less carbon atoms, or a phenyl group.)
[0319]
[0320] (In formula (OP-4), R 12 , R 13 , R 14 , R 15 , R 16 , R 17 , R 18 and R 19 They may be the same or different and are a hydrogen atom, an alkyl group having 6 or less carbon atoms, or a phenyl group. -A- is a linear, branched, or cyclic divalent hydrocarbon group having 20 or less carbon atoms. )
[0321] In addition, -(YO)- is preferably represented by the formula (OP-5).
[0322]
[0323] (In formula (OP-5), R 20 , R 21 may be the same or different and are an alkyl group having 6 or less carbon atoms or a phenyl group. 22 , R 23 They may be the same or different and are a hydrogen atom, an alkyl group having 6 or less carbon atoms, or a phenyl group.)
[0324] By making R 20 and R21 Each independently being a group having one or more methyl and / or cyclohexyl groups, the rigidity of the obtained resin molecules is improved, and molecules with high rigidity have lower mobility than molecules with low rigidity, so the relaxation time during dielectric relaxation is increased, and the low dielectric properties (Dk and / or Df) are improved, which is preferred.
[0325] An example of the formula (OP-5) is the following structure.
[0326]
[0327] Regarding the polyphenylene ether compound having the above structure, reference can be made to the description of Japanese Patent Application Laid-Open No. 2019-194312, the contents of which are incorporated into this specification.
[0328] In formula (OP-2), a and b each independently represent an integer of 0 to 100, and at least one of a and b is an integer of 1 to 100. a and b each independently represent an integer of 0 to 50, more preferably an integer of 1 to 30, and preferably an integer of 1 to 10. When a and / or b is an integer of 2 or more, two or more -(YO)- may each independently be arranged in one structure, or may be arranged in blocks or randomly in two or more structures.
[0329] When a plurality of compounds represented by the formula (OP-2) are included, the average value of a is preferably 1<a<10, and the average value of b is preferably 1<b<10.
[0330] Examples of -A- in formula (OP-4) include, but are not limited to, divalent organic groups such as methylene, ethylidene, 1-methylethylidene, 1,1-propylidene, 1,4-phenylenebis(1-methylethylidene), 1,3-phenylenebis(1-methylethylidene), cyclohexylidene, phenylmethylene, naphthylmethylene, and 1-phenylethylidene.
[0331] Among the compounds represented by the above formula (OP-2), preferably, R 4 , R 5 , R 6 , R 10 , R 11 , R 20 and R 21 is an alkyl group with a carbon number of 3 or less, and R 7 , R 8 , R 9 , R 12 , R 13 , R 14 , R 15 , R 16 , R 17, R 18 , R 19 , R 22 and R 23 A polyphenylene ether compound in which -(OXO)- represented by formula (OP-3) or (OP-4) is formula (OP-9), formula (OP-10) and / or formula (OP-11), and -(YO)- represented by formula (OP-5) is formula (OP-12) or formula (OP-13). When a and / or b is an integer greater than 2, two or more -(YO)- are independently a structure in which two or more of formula (OP-12) and / or formula (OP-13) are arranged, or a structure in which formula (OP-12) and formula (OP-13) are arranged in blocks or randomly.
[0332]
[0333] (In formula (OP-10), R 44 , R 45 , R 46 and R 47 They may be the same or different and are hydrogen atoms or methyl groups. -B- is a linear, branched or cyclic divalent hydrocarbon group having 20 or less carbon atoms.
[0334] As specific examples of -B-, the same ones as the specific examples of -A- in formula (OP-4) can be given.
[0335]
[0336] (In formula (OP-11), -B- is a linear, branched or cyclic divalent hydrocarbon group having 20 or less carbon atoms.)
[0337] As specific examples of -B-, the same ones as the specific examples of -A- in formula (OP-4) can be given.
[0338]
[0339] As the modified polyphenylene ether compound (g) used in the present embodiment, a compound represented by formula (OP-14) and / or a compound represented by formula (OP-15) is more preferred, and a compound represented by formula (OP-15) is even more preferred.
[0340]
[0341] (In formula (OP-14), a and b each independently represent an integer of 0 to 100, and at least one of a and b is an integer of 1 to 100.)
[0342] a and b in formula (OP-14) have the same meanings as a and b in formula (OP-2) independently, and the preferred ranges are also the same.
[0343]
[0344] (In formula (OP-15), a and b each independently represent an integer of 0 to 100, and at least one of a and b is an integer of 1 to 100.)
[0345] a and b in formula (OP-15) have the same meanings as a and b in formula (OP-2) independently, and the preferred ranges are also the same.
[0346] The polyphenylene ether compound having a carbon-carbon unsaturated double bond at the end can be manufactured by a known method, or a commercially available product can be used. As a commercially available product, for example, as a modified polyphenylene ether compound having a methacryloyl group at the end, "SA9000" manufactured by SABIC Innovative Plastics can be cited. In addition, as a modified polyphenylene ether compound having a vinyl benzyl group at the end, "OPE-2St1200" and "OPE-2st2200" manufactured by Mitsubishi Gas Chemical Co., Ltd. can be cited. In addition, as a modified polyphenylene ether compound having a vinyl benzyl group at the end, a polyphenylene ether compound having a hydroxyl group at the end, such as "SA90" manufactured by SABIC Innovative Plastics, can be modified to a vinyl benzyl group using vinyl benzyl chloride or the like.
[0347] For details of other polyphenylene ether compounds having a carbon-carbon unsaturated double bond at the terminal, reference may be made to Japanese Patent Application Publication No. 2006-028111, Japanese Patent Application Publication No. 2018-131519, International Publication No. 2019-138992, and International Publication No. 2022-054303, and these contents are incorporated into this specification.
[0348] The polyphenylene ether compound (preferably a modified polyphenylene ether compound (g)) having a carbon-carbon unsaturated double bond at the terminal has a polystyrene-equivalent number average molecular weight of 500 or more and 3,000 or less based on the GPC (gel permeation chromatography) method. When the number average molecular weight is 500 or more, there is a tendency to further suppress stickiness when the resin composition of the present embodiment is made into a coating film. When the number average molecular weight is 3,000 or less, there is a tendency to further improve the solubility in a solvent.
[0349] In addition, the polyphenylene ether compound (preferably the modified polyphenylene ether compound (g)) having a carbon-carbon unsaturated double bond at the terminal has a polystyrene-equivalent weight average molecular weight of preferably 800 or more and 10,000 or less, more preferably 800 or more and 5,000 or less, based on GPC. By setting it to be above the aforementioned lower limit, there is a tendency that the relative dielectric constant (Dk) and dielectric loss tangent (Df) of the cured product of the resin composition become lower, and by setting it to be below the aforementioned upper limit, there is a tendency that the solubility, low viscosity and moldability of the resin composition in a solvent when preparing a varnish described later, etc., are further improved.
[0350] Furthermore, when it is a modified polyphenylene ether compound (g), the carbon-carbon unsaturated double bond equivalent at the end is preferably 400 to 5000g per 1 carbon-carbon unsaturated double bond, and more preferably 400 to 2500g. By being set to above the aforementioned lower limit, there is a tendency that the relative dielectric constant (Dk) and dielectric loss tangent (Df) of the cured product of the resin composition become lower. By being set to below the aforementioned upper limit, there is a tendency to further improve the solubility, low viscosity and formability of the resin composition in the solvent.
[0351] When the resin composition of the present embodiment is included in the polyphenylene ether compound with carbon-carbon unsaturated double bonds at the end, relative to the resin solids 100 mass parts in the resin composition, the lower limit of the content of the polyphenylene ether compound with carbon-carbon unsaturated double bonds at the end is preferably more than 1 mass part, more preferably more than 3 mass parts, more preferably more than 5 mass parts, more preferably more than 7 mass parts, more preferably more than 10 mass parts.By being set to more than the aforementioned lower limit, there is a tendency to further improve the low water absorption and low dielectric properties (Dk and / or Df) of the cured product obtained.In addition, relative to the resin solids 100 mass parts in the resin composition, the upper limit of the content of the polyphenylene ether compound with carbon-carbon unsaturated double bonds at the end is preferably less than 70 mass parts, more preferably less than 60 mass parts, more preferably less than 50 mass parts, more preferably less than 40 mass parts, more preferably less than 35 mass parts, more preferably less than 30 mass parts.By being set to less than the aforementioned upper limit, there is a tendency to further improve the heat resistance and chemical resistance of the cured product obtained.
[0352] The resin composition in the present embodiment may contain only one polyphenylene ether compound having a carbon-carbon unsaturated double bond at a terminal, or may contain two or more. When containing two or more, the total amount is preferably within the above range.
[0353] <<<Maleimide compounds>>>
[0354] The resin composition of the present embodiment may also contain a maleimide compound. In the resin composition of the present embodiment, if it is a compound having one or more (preferably two or more, more preferably 2 to 12, further preferably 2 to 6, further preferably 2 to 4, further preferably 2 or 3, further preferably 2) maleimide groups in one molecule, there is no particular limitation, and compounds commonly used in the field of printed circuit boards can be widely used.
[0355] In the present embodiment, the maleimide compound is preferably a compound shown in formula (M0) to formula (M5), more preferably a compound shown in formula (M0) to formula (M4), further preferably a compound shown in formula (M0), formula (M1) and formula (M3), more preferably a compound shown in formula (M1). If these maleimide compounds are used as printed circuit board materials (for example, metal foil laminated plates), etc., excellent heat resistance can be imparted. In particular, if the compound shown in formula (M1) is used, there is a tendency to more effectively achieve low dielectric properties.
[0356]
[0357] (In formula (M0), R 51 Each independently represents a hydrogen atom, an alkyl group having 1 to 8 carbon atoms or a phenyl group, and R 52 Each independently represents a hydrogen atom or a methyl group, and n1 represents an integer greater than 1.)
[0358] R 51 Each independently preferably is a hydrogen atom, a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a tert-butyl group, an n-pentyl group, or a phenyl group, more preferably is a hydrogen atom and a methyl group, and further preferably is a hydrogen atom.
[0359] R 52 Preferred is methyl.
[0360] n1 is preferably an integer of 1 to 10, more preferably an integer of 1 to 5, further preferably an integer of 1 to 3, further preferably 1 or 2, and even more preferably 1.
[0361] The compound represented by formula (M0) may be a single compound or a mixture of two or more compounds. Examples of the mixture include a mixture of compounds having different n1, a mixture of compounds having different n1, and a mixture of compounds having different n1. 51 and / or R 52 A mixture of compounds having different types of substituents, a mixture of compounds having different bonding positions (meta, para, or ortho) of the maleimide group and the oxygen atom relative to the benzene ring, and a mixture of compounds having two or more of the above different positions combined, etc. The same applies to the compounds represented by formulas (M1) to (M5).
[0362]
[0363] (In formula (M1), R M1 , R M2 , R M3 and R M4 Each independently represents a hydrogen atom or an organic group. M5 and R M6 Each independently represents a hydrogen atom or an alkyl group. M represents a divalent aromatic group. A is a 4- to 6-membered alicyclic group. M7 and R M8 Each is independently an alkyl group. mx is 1 or 2, and lx is 0 or 1. M9 and R M10 Each independently represents a hydrogen atom or an alkyl group. M11 , R M12 , R M13 , and R M14 Each independently represents a hydrogen atom or an organic group. M15 Each independently represents an alkyl group having 1 to 10 carbon atoms, an alkoxy group having 1 to 10 carbon atoms, an alkylthio group having 1 to 10 carbon atoms, an aryl group having 6 to 10 carbon atoms, an aryloxy group having 6 to 10 carbon atoms, an arylthio group having 6 to 10 carbon atoms, a halogen atom, a hydroxyl group or a mercapto group. px represents an integer of 0 to 3. nx represents an integer of 1 to 20.)
[0364] R in the formula M1 , R M2 , R M3 and R M4 Each independently represents a hydrogen atom or an organic group. The organic group here is preferably an alkyl group, more preferably an alkyl group having 1 to 12 carbon atoms, further preferably an alkyl group having 1 to 6 carbon atoms, still more preferably a methyl group, an ethyl group, a propyl group, or a butyl group, and particularly preferably a methyl group. M1 and R M3 Each is independently preferably an alkyl group, R M2 and R M4 Preferred is a hydrogen atom.
[0365] R M5 and R M6 Each independently represents a hydrogen atom or an alkyl group, and is preferably an alkyl group. Here, the alkyl group is preferably an alkyl group having 1 to 12 carbon atoms, more preferably an alkyl group having 1 to 6 carbon atoms, further preferably a methyl group, an ethyl group, a propyl group, and a butyl group, and particularly preferably a methyl group.
[0366] Ar M Ar represents a divalent aromatic group, preferably phenylene, naphthalene diyl, phenanthrene diyl, anthracene diyl, more preferably phenylene, and further preferably m-phenylene. MThe substituent is preferably an alkyl group, more preferably an alkyl group having 1 to 12 carbon atoms, further preferably an alkyl group having 1 to 6 carbon atoms, further preferably a methyl group, an ethyl group, a propyl group, or a butyl group, and particularly preferably a methyl group. M No substitution is preferred.
[0367] A is a 4- to 6-membered alicyclic group, more preferably a 5-membered alicyclic group (preferably a group condensed with a benzene ring to form an indane ring). M7 and R M8 Each independently represents an alkyl group, preferably an alkyl group having 1 to 6 carbon atoms, more preferably an alkyl group having 1 to 3 carbon atoms, and particularly preferably a methyl group.
[0368] mx is 1 or 2, preferably 2.
[0369] lx is 0 or 1, preferably 1.
[0370] R M9 and R M10 Each independently represents a hydrogen atom or an alkyl group, and an alkyl group is more preferred. The alkyl group herein is preferably an alkyl group having 1 to 12 carbon atoms, more preferably an alkyl group having 1 to 6 carbon atoms, further preferably a methyl group, an ethyl group, a propyl group, and a butyl group, and among these, a methyl group is particularly preferred.
[0371] R M11 , R M12 , R M13 and R M14 Each independently represents a hydrogen atom or an organic group. The organic group here is preferably an alkyl group, more preferably an alkyl group having 1 to 12 carbon atoms, further preferably an alkyl group having 1 to 6 carbon atoms, still more preferably a methyl group, an ethyl group, a propyl group, or a butyl group, and particularly preferably a methyl group. M12 and R M13 Each independently preferably an alkyl group, R M11 and R M14 A hydrogen atom is preferred.
[0372] R M15 Each independently represents an alkyl group having 1 to 10 carbon atoms, an alkoxy group having 1 to 10 carbon atoms, an alkylthio group having 1 to 10 carbon atoms, an aryl group having 6 to 10 carbon atoms, an aryloxy group having 6 to 10 carbon atoms, an arylthio group having 6 to 10 carbon atoms, a halogen atom, a hydroxyl group or a mercapto group, and is preferably an alkyl group having 1 to 4 carbon atoms, a cycloalkyl group having 3 to 6 carbon atoms or an aryl group having 6 to 10 carbon atoms.
[0373] px represents an integer of 0 to 3, preferably an integer of 0 to 2, more preferably 0 or 1, and further preferably 0.
[0374] nx represents an integer of 1 to 20. nx may be an integer of 10 or less.
[0375] It should be noted that the resin composition of the present embodiment may include only one compound belonging to the compound shown in the formula (M1) and at least a compound having different values of nx, or may include more than two kinds. When including more than two kinds, in order to make a low melting point (low softening point) and a person having low melt viscosity and excellent operability, the average value (average number of repeating units) n of nx in the compound shown in the formula (M1) in the resin composition is preferably more than 0.92, more preferably more than 0.95, further preferably more than 1.0, and more preferably more than 1.1. In addition, n is preferably less than 10.0, more preferably less than 8.0, further preferably less than 7.0, more preferably less than 6.0, and may also be less than 5.0. The same is true for formula (M1-1) etc. described later.
[0376] The compound represented by the formula (M1) is preferably a compound represented by the following formula (M1-1).
[0377]
[0378] (In formula (M1-1), R M21 , R M22 , R M23 and R M24 Each independently represents a hydrogen atom or an organic group. M25 and R M26 Each independently represents a hydrogen atom or an alkyl group. M27 , R M28 , R M29 and R M30 Each independently represents a hydrogen atom or an organic group. M31 and R M32 Each independently represents a hydrogen atom or an alkyl group. M33 , R M34 , R M35 and R M36 Each independently represents a hydrogen atom or an organic group. M37 , R M38 and R M39 Each independently represents a hydrogen atom or an alkyl group. nx represents an integer of 1 to 20.
[0379] R in the formula M21 , R M22 , R M23 and R M24 Each independently represents a hydrogen atom or an organic group. The organic group here is preferably an alkyl group, more preferably an alkyl group having 1 to 12 carbon atoms, further preferably an alkyl group having 1 to 6 carbon atoms, still more preferably a methyl group, an ethyl group, a propyl group, or a butyl group, and particularly preferably a methyl group. M21 and R M23 Preferably, alkyl, R M22 and R M24 A hydrogen atom is preferred.
[0380] R M25 and R M26 Each independently represents a hydrogen atom or an alkyl group, preferably an alkyl group. The alkyl group herein is preferably an alkyl group having 1 to 12 carbon atoms, more preferably an alkyl group having 1 to 6 carbon atoms, further preferably a methyl group, an ethyl group, a propyl group, or a butyl group, and particularly preferably a methyl group.
[0381] R M27 , R M28 , R M29 and R M30 Each independently represents a hydrogen atom or an organic group, preferably a hydrogen atom. The organic group here is preferably an alkyl group, more preferably an alkyl group having 1 to 12 carbon atoms, further preferably an alkyl group having 1 to 6 carbon atoms, further preferably a methyl group, an ethyl group, a propyl group, or a butyl group, and particularly preferably a methyl group.
[0382] R M31 and R M32 Each independently represents a hydrogen atom or an alkyl group, preferably an alkyl group. The alkyl group herein is preferably an alkyl group having 1 to 12 carbon atoms, more preferably an alkyl group having 1 to 6 carbon atoms, further preferably a methyl group, an ethyl group, a propyl group, or a butyl group, and particularly preferably a methyl group.
[0383] R M33 , R M34 , R M35 and R M36 Each independently represents a hydrogen atom or an organic group. The organic group here is preferably an alkyl group, more preferably an alkyl group having 1 to 12 carbon atoms, further preferably an alkyl group having 1 to 6 carbon atoms, further preferably a methyl group, an ethyl group, a propyl group, or a butyl group, and particularly preferably a methyl group.
[0384] R M33 and R M36 Preferably a hydrogen atom, R M34 and R M35 An alkyl group is preferred.
[0385] R M37 , R M38 , R M39 Each independently represents a hydrogen atom or an alkyl group, preferably an alkyl group. The alkyl group herein is preferably an alkyl group having 1 to 12 carbon atoms, more preferably an alkyl group having 1 to 6 carbon atoms, further preferably a methyl group, an ethyl group, a propyl group, or a butyl group, and particularly preferably a methyl group.
[0386] nx represents an integer of 1 to 20. nx may be an integer of 10 or less.
[0387] The compound represented by formula (M1-1) is preferably a compound represented by the following formula (M1-2).
[0388]
[0389] (In formula (M1-2), R M21 , R M22 , R M23 and R M24 Each independently represents a hydrogen atom or an organic group. M25 and R M26 Each independently represents a hydrogen atom or an alkyl group. M27 , R M28 , R M29 and R M30 Each independently represents a hydrogen atom or an organic group. M31 and R M32 Each independently represents a hydrogen atom or an alkyl group. M33 , R M34 , R M35 and R M36 Each independently represents a hydrogen atom or an organic group. M37 , R M38 and R M39 Each independently represents a hydrogen atom or an alkyl group. nx represents an integer of 1 to 20.
[0390] In formula (M1-2), R M21 , R M22 , R M23 , R M24 , R M25 , R M26 , R M27 , R M28 , R M29 , R M30 , R M31 , R M32 , R M33 , R M34 , R M35 , R M36 , R M37 , R M38 , R M39 and nx are respectively the same as R in formula (M1-1) M21 , R M22 , R M23 , R M24 , R M25 , R M26 , R M27 , R M28 , R M29 , R M30 , R M31 , R M32 , R M33 , R M34 , R M35 , R M36 , R M37 , RM38 , R M39 It has the same meaning as nx and has the same preferred range.
[0391] The compound represented by the formula (M1-1) is more preferably a compound represented by the following formula (M1-3), and even more preferably a compound represented by the following formula (M1-4).
[0392]
[0393] (In formula (M1-3), nx represents an integer of 1 to 20.)
[0394] nx may be an integer less than 10.
[0395]
[0396] (In formula (M1-4), nx represents an integer of 1 to 20.)
[0397] The molecular weight of the compound shown in formula (M1) is preferably 500 or more, more preferably 600 or more, and further preferably 700 or more. By setting it to above the aforementioned lower limit, there is a tendency that the low dielectric properties and low water absorption of the obtained solidified material are further improved. In addition, the molecular weight of the compound shown in formula (M1) is preferably 10000 or less, more preferably 9000 or less, further preferably 7000 or less, more preferably 5000 or less, and further preferably 4000 or less. By setting it to below the aforementioned upper limit, there is a tendency that the heat resistance and operability of the obtained solidified material are further improved.
[0398]
[0399] (In formula (M2), R 54 Each independently represents a hydrogen atom or a methyl group, and n4 represents an integer greater than 1.)
[0400] n4 is preferably an integer of 1 to 10, more preferably an integer of 1 to 5, further preferably an integer of 1 to 3, further preferably 1 or 2, and may be 1.
[0401] The compound represented by formula (M2) may be a mixture of compounds having different n4, preferably a mixture. In addition, as described in the case of the compound represented by formula (M0), it may be a mixture of compounds having different other parts.
[0402]
[0403] (In formula (M3), R 55 Each independently represents a hydrogen atom, an alkyl group having 1 to 8 carbon atoms, or a phenyl group, and n5 represents an integer of 1 to 10.
[0404] R 55 Each independently preferably is a hydrogen atom, a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a tert-butyl group, an n-pentyl group, or a phenyl group, more preferably is a hydrogen atom and a methyl group, and further preferably is a hydrogen atom.
[0405] n5 is preferably an integer of 1 to 5, more preferably an integer of 1 to 3, and even more preferably 1 or 2.
[0406] The compound represented by formula (M3) may be a mixture of compounds having different n5, preferably a mixture. In addition, as described in the case of the compound represented by formula (M0), it may be a mixture of compounds having different other parts.
[0407]
[0408] (In formula (M4), R 56 Each independently represents a hydrogen atom, a methyl group or an ethyl group, and R 57 Each independently represents a hydrogen atom or a methyl group. )
[0409]
[0410] (In formula (M5), R 58 Each independently represents a hydrogen atom, an alkyl group having 1 to 8 carbon atoms or a phenyl group, and R 59 Each independently represents a hydrogen atom or a methyl group, and n6 represents an integer greater than 1.)
[0411] R 58 Each independently preferably is a hydrogen atom, a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a tert-butyl group, an n-pentyl group, or a phenyl group, more preferably is a hydrogen atom and a methyl group, and further preferably is a hydrogen atom.
[0412] R 59 Preferred is methyl.
[0413] n6 is preferably an integer of 1 to 10, more preferably an integer of 1 to 5, further preferably an integer of 1 to 3, further preferably 1 or 2, and may be 1.
[0414] The compound represented by formula (M5) may be a mixture of compounds having different n6, preferably a mixture. In addition, as described in the case of the compound represented by formula (M0), it may be a mixture of compounds having different other parts.
[0415] In addition to the above, as maleimide compounds, reference may be made to the compounds described in paragraphs 0061 to 0066 of International Publication No. 2020 / 262577 and Japanese Patent No. 7160151, and the contents thereof are incorporated herein.
[0416] Maleimide compounds can be manufactured by known methods, or commercial products can be used. As commercial products, for example, as a compound represented by formula (M0), KI Chemical Industry Co., Ltd. "BMI-80" can be listed, as a compound represented by formula (M1), DIC Corporation "NE-X-9470S" can be listed, as a compound represented by formula (M2), DAIWAKASEI KOGYO, CO., LTD "BMI-2300" can be listed, as a compound represented by formula (M3), Nippon Kayaku Co., Ltd. "MIR-3000" can be listed, as a compound represented by formula (M4), KI Chemical Industry Co., Ltd. "BMI-70" can be listed, as a compound represented by formula (M5), Nippon Kayaku Co., Ltd. "MIR-5000" can be listed, and in addition, Nippon Kayaku Co., Ltd. "MIZ-001" can be listed, and Nippon Kayaku Co., Ltd. "NE-X-9500" can be listed.
[0417] In addition, examples of maleimide compounds other than the above include N-phenylmaleimide, oligomers of phenylmethanemaleimide, m-phenylene bismaleimide, 2,2-bis(4-(4-maleimidophenoxy)-phenyl)propane, 4-methyl-1,3-phenylene bismaleimide, 1,6-bismaleimido-(2,2,4-trimethyl)hexane, 4,4'-diphenyl ether bismaleimide, 4,4'-diphenyl sulfone bismaleimide, 1,3-bis(3-maleimidophenoxy)benzene, 1,3-bis(4-maleimidophenoxy)benzene, prepolymers thereof, and prepolymers of these maleimides and amines.
[0418] When the resin composition of the present embodiment includes a maleimide compound, the lower limit of the content of the maleimide compound is preferably more than 1 mass part relative to 100 mass parts of the resin solids in the resin composition, more preferably more than 5 mass parts, more preferably more than 10 mass parts, more preferably more than 20 mass parts, and more preferably more than 25 mass parts. By making the content of the maleimide compound more than 1 mass part, there is a tendency to improve the flame retardancy of the cured product obtained. In addition, the upper limit of the content of the maleimide compound is preferably less than 70 mass parts relative to 100 mass parts of the resin solids in the resin composition, more preferably less than 60 mass parts, more preferably less than 50 mass parts, and can also be less than 40 mass parts. By making the content of the maleimide compound less than 70 mass parts, there is a tendency to improve metal foil peel strength and low water absorption.
[0419] The resin composition in the present embodiment may contain only one maleimide compound or may contain two or more thereof. When containing two or more thereof, the total amount is preferably within the above range.
[0420] <<<Cyanate ester compounds>>>
[0421] The resin composition of the present embodiment may contain a cyanate compound.
[0422] The cyanate compound is not particularly limited as long as it is a compound containing one or more (preferably 2 or more, more preferably 2 to 12, further preferably 2 to 6, further preferably 2 to 4, further preferably 2 or 3, further preferably 2) cyanate groups (cyano groups) in one molecule, and a wide range of compounds commonly used in the field of printed circuit boards can be used. In addition, the cyanate compound is preferably a compound in which a cyanate group is directly bonded to an aromatic skeleton (aromatic ring).
[0423] As the cyanate compound, for example, at least one selected from the group consisting of phenol novolac type cyanate compounds, naphthol aralkyl type cyanate compounds (naphthol aralkyl type cyanate), naphthol ether type cyanate compounds, biphenyl aralkyl type cyanate compounds, xylene resin type cyanate compounds, trisphenol methane type cyanate compounds, adamantane skeleton type cyanate compounds, bisphenol M type cyanate compounds, bisphenol A type cyanate compounds and diallyl bisphenol A type cyanate compounds can be cited. Among them, from the viewpoint of further improving the low water absorption of the obtained cured product, at least one selected from the group consisting of phenol novolac type cyanate compounds, naphthol aralkyl type cyanate compounds, naphthol ether type cyanate compounds, xylene resin type cyanate compounds, bisphenol M type cyanate compounds, bisphenol A type cyanate compounds and diallyl bisphenol A type cyanate compounds is preferred, at least one selected from the group consisting of phenol novolac type cyanate compounds and naphthol aralkyl type cyanate compounds is more preferred, and naphthol aralkyl type cyanate compounds are further preferred. These cyanate compounds can be prepared by known methods, and commercial products can also be used. It should be noted that the functional group equivalent number of the cyanate compounds with a naphthol aralkyl skeleton, a naphthyl ether skeleton, a xylene skeleton, a triphenol methane skeleton or an adamantane skeleton is relatively large, and the unreacted cyanate group decreases, so the cured product of the resin composition using them has a tendency to be more excellent in low water absorption. In addition, mainly because they have an aromatic skeleton or an adamantane skeleton, there is a tendency to improve the plating adhesion.
[0424] The naphthol aralkyl type cyanate ester compound is more preferably a compound represented by the following formula (1).
[0425]
[0426] (In formula (1), R 3 Each independently represents a hydrogen atom or a methyl group, and n3 represents an integer greater than 1.)
[0427] In formula (1), R 3 Each independently represents a hydrogen atom or a methyl group, and among them, a hydrogen atom is preferred.
[0428] In formula (1), n3 is an integer of 1 or more, preferably an integer of 1-20, more preferably an integer of 1-10, and further preferably an integer of 1-6.
[0429] The novolac-type cyanate compound is not particularly limited, but is preferably a compound represented by the following formula (VII), for example.
[0430]
[0431] (In formula (VII), R 6Each independently represents a hydrogen atom or a methyl group, and n7 represents an integer greater than 1.)
[0432] In formula (VII), R 6 Each independently represents a hydrogen atom or a methyl group, and among them, a hydrogen atom is preferred.
[0433] In formula (VII), n7 is an integer of 1 or more, preferably an integer of 1-20, more preferably an integer of 1-10, and further preferably an integer of 1-6.
[0434] As the bisphenol A type cyanate ester compound, one or more selected from the group consisting of 2,2-bis(4-cyanophenyl)propane and a prepolymer of 2,2-bis(4-cyanophenyl)propane can be used.
[0435] The resin composition of the present embodiment preferably includes cyanate compounds within the scope of not damaging the effect of the present invention. When the resin composition of the present embodiment includes cyanate compounds, the lower limit of its content is preferably 0.1 mass parts or more relative to 100 mass parts of resin solids in the resin composition, more preferably 0.2 mass parts or more, further preferably 0.5 mass parts or more, according to purposes, it can also be 3 mass parts or more, 5 mass parts or more, 10 mass parts or more. By making the content of cyanate compounds be more than 0.1 mass parts, there is a tendency to improve the heat resistance, combustion resistance, chemical resistance, low relative dielectric constant, low dielectric loss tangent, and insulation of the cured product obtained. When the resin composition of the present embodiment includes cyanate compounds, the upper limit of the content of cyanate compounds is preferably 70 mass parts or less relative to 100 mass parts of resin solids in the resin composition, more preferably 50 mass parts or less, further preferably 40 mass parts or less, more preferably 30 mass parts or less, further preferably 20 mass parts or less, according to purposes, it can also be 10 mass parts or less, 5 mass parts or less, 3 mass parts or less.
[0436] The resin composition in the present embodiment may contain only one cyanate compound or two or more cyanate compounds. When two or more cyanate compounds are contained, the total amount is preferably within the above range.
[0437] <<<Epoxy compounds>>>
[0438] The resin composition of the present embodiment may contain an epoxy compound.
[0439] The epoxy compound is not particularly limited as long as it is a compound or resin having one or more epoxy groups (preferably 2 to 12, more preferably 2 to 6, further preferably 2 to 4, further preferably 2 or 3, further preferably 2) in one molecule, and a wide range of compounds commonly used in the field of printed wiring boards can be used.
[0440] Examples of the epoxy compound include bisphenol A epoxy resin, bisphenol E epoxy resin, bisphenol F epoxy resin, bisphenol S epoxy resin, phenol novolac epoxy resin, bisphenol A novolac epoxy resin, glycidyl ester epoxy resin, aralkyl novolac epoxy resin, biphenyl aralkyl epoxy resin, naphthyl ether epoxy resin, cresol novolac epoxy resin, polyfunctional phenol epoxy resin, naphthalene epoxy resin, anthracene epoxy resin, Type epoxy resin, naphthalene skeleton modified novolac type epoxy resin, phenol aralkyl type epoxy resin, naphthol aralkyl type epoxy resin, dicyclopentadiene type epoxy resin, biphenyl type epoxy resin, alicyclic epoxy resin, polyol type epoxy resin, phosphorus-containing epoxy resin, glycidyl amine, glycidyl ester, the compound formed by epoxidation of double bonds of butadiene, etc., the compound obtained by the reaction of hydroxyl-containing silicone resin and epichlorohydrin, etc. By using them, the formability and adhesion of resin combination can be improved. Among them, from the viewpoint of further improving flame retardancy and heat resistance, preferably biphenyl aralkyl type epoxy resin, naphthyl ether type epoxy resin, multifunctional phenol type epoxy resin, naphthalene type epoxy resin, more preferably biphenyl aralkyl type epoxy resin.
[0441] The resin composition of the present embodiment preferably includes epoxy compounds within the scope of not damaging the effect of the present invention. When the resin composition of the present embodiment includes epoxy compounds, its content is preferably 0.1 mass parts or more relative to 100 mass parts of resin solid components in the resin composition, more preferably 1 mass parts or more, and further preferably 2 mass parts or more. By making the content of epoxy compounds more than 0.1 mass parts, there is a tendency to improve metal foil peel strength and toughness. When the resin composition of the present embodiment includes epoxy compounds, the upper limit of the content of epoxy compounds is preferably less than 50 mass parts relative to 100 mass parts of resin solid components in the resin composition, more preferably less than 30 mass parts, further preferably less than 20 mass parts, more preferably less than 10 mass parts, and can also be less than 8 mass parts, less than 5 mass parts. By making the content of epoxy compounds less than 50 mass parts, there is a tendency to improve the electrical properties of the cured product obtained.
[0442] The resin composition in the present embodiment may contain only one epoxy compound or two or more epoxy compounds. When two or more epoxy compounds are contained, the total amount is preferably within the above range.
[0443] In addition, the resin composition in the present embodiment may be configured to be substantially free of epoxy compounds. Substantially free means that the content of epoxy compounds is less than 0.1 parts by mass, preferably less than 0.01 parts by mass, and further may be less than 0.001 parts by mass relative to 100 parts by mass of the resin solid content in the resin composition.
[0444] <<<Phenol compounds>>>
[0445] The resin composition of the present embodiment may contain a phenol compound.
[0446] The phenol compound is not particularly limited as long as it has one or more (preferably 2 to 12, more preferably 2 to 6, further preferably 2 to 4, further preferably 2 or 3, further preferably 2) phenolic hydroxyl groups in one molecule, and a wide range of compounds commonly used in the field of printed wiring boards can be used.
[0447] Examples of the phenolic compound include bisphenol A type phenolic resin, bisphenol E type phenolic resin, bisphenol F type phenolic resin, bisphenol S type phenolic resin, phenol novolac resin, bisphenol A novolac type phenolic resin, glycidyl ester type phenolic resin, aralkyl novolac phenolic resin, biphenyl aralkyl type phenolic resin, cresol novolac type phenolic resin, multifunctional phenolic resin, naphthol resin, naphthol novolac resin, multifunctional naphthol resin, anthracene type phenolic resin, naphthalene skeleton modified novolac type phenolic resin, phenol aralkyl type phenolic resin, naphthol aralkyl type phenolic resin, dicyclopentadiene type phenolic resin, biphenyl type phenolic resin, alicyclic phenolic resin, polyol type phenolic resin, phosphorus-containing phenolic resin, hydroxyl-containing silicone resins, and the like. Among them, at least one selected from the group consisting of biphenyl aralkyl phenol resins, naphthol aralkyl phenol resins, phosphorus-containing phenol resins and hydroxyl-containing silicone resins is preferred from the viewpoint of further improving the flame retardancy of the obtained cured product.
[0448] The resin composition of the present embodiment preferably contains a phenol compound within a range that does not impair the effects of the present invention. When the resin composition of the present embodiment contains a phenol compound, its content is preferably 0.1 parts by mass or more, and preferably 50 parts by mass or less, relative to 100 parts by mass of the resin solid content in the resin composition.
[0449] The resin composition in the present embodiment may contain only one phenol compound or two or more phenol compounds. When two or more phenol compounds are contained, the total amount is preferably within the above range.
[0450] The resin composition in the present embodiment may be configured to contain substantially no phenol compound. Substantially containing no phenol compound means that the content of the phenol compound is less than 0.1 parts by mass based on 100 parts by mass of the resin solid content in the resin composition.
[0451] <<<Oxetane resin>>>
[0452] The resin composition of the present embodiment may contain an oxetane resin.
[0453] The oxetane resin is not particularly limited as long as it is a compound having one or more (preferably 2 to 12, more preferably 2 to 6, further preferably 2 to 4, further preferably 2 or 3, further preferably 2) oxetane groups, and a wide variety of compounds commonly used in the field of printed wiring boards can be used.
[0454] Examples of the oxetane resin include oxetane, alkyloxetane (e.g., 2-methyloxetane, 2,2-dimethyloxetane, 3-methyloxetane, 3,3-dimethyloxetane, etc.), 3-methyl-3-methoxymethyloxetane, 3,3-bis(trifluoromethyl)oxetane, 2-chloromethyloxetane, 3,3-bis(chloromethyl)oxetane, biphenyl-type oxetane, OXT-101 (manufactured by TOAGOSEI CO., LTD.), and OXT-121 (manufactured by TOAGOSEI CO., LTD.).
[0455] The resin composition of the present embodiment preferably includes oxetane resin within the scope of not damaging the effect of the present invention. When the resin composition of the present embodiment includes oxetane resin, its content is preferably more than 0.1 mass parts relative to 100 mass parts of resin solids in the resin composition, more preferably more than 1 mass parts, and more preferably more than 2 mass parts. By making the content of oxetane resin more than 0.1 mass parts, there is a tendency to improve metal foil peel strength and toughness. When the resin composition of the present embodiment includes oxetane resin, the upper limit of the content of oxetane resin is preferably less than 50 mass parts relative to 100 mass parts of resin solids in the resin composition, more preferably less than 30 mass parts, more preferably less than 20 mass parts, more preferably less than 10 mass parts, and can also be less than 8 mass parts. By making the content of oxetane resin less than 50 mass parts, there is a tendency to improve the electrical properties of the cured product obtained.
[0456] The resin composition in the present embodiment may contain only one oxetane resin or two or more oxetane resins. When two or more oxetane resins are contained, the total amount is preferably within the above range.
[0457] The resin composition in the present embodiment may be configured to contain substantially no oxetane resin. Substantially containing no oxetane resin means that the content of the oxetane resin is less than 0.1 parts by mass based on 100 parts by mass of the resin solid content in the resin composition.
[0458] <<<Benzoxazine compounds>>>
[0459] The resin composition of the present embodiment may contain a benzoxazine compound.
[0460] The benzoxazine compound is not particularly limited as long as it is a compound having two or more (preferably 2 to 12, more preferably 2 to 6, further preferably 2 to 4, further preferably 2 or 3, further preferably 2) dihydrobenzoxazine rings in one molecule, and a wide range of compounds commonly used in the field of printed circuit boards can be used.
[0461] Examples of the benzoxazine compound include bisphenol A type benzoxazine BA-BXZ (manufactured by KONISHI CHEMICAL IND CO., LTD.), bisphenol F type benzoxazine BF-BXZ (manufactured by KONISHI CHEMICAL IND CO., LTD.), and bisphenol S type benzoxazine BS-BXZ (manufactured by KONISHI CHEMICAL IND CO., LTD.).
[0462] The resin composition of the present embodiment preferably contains a benzoxazine compound within a range that does not impair the effects of the present invention. When the resin composition of the present embodiment contains a benzoxazine compound, its content is preferably 0.1 parts by mass or more and preferably 50 parts by mass or less relative to 100 parts by mass of the resin solid content in the resin composition.
[0463] The resin composition of the present embodiment may contain only one benzoxazine compound or two or more benzoxazine compounds. When two or more benzoxazine compounds are contained, the total amount is preferably within the above range.
[0464] The resin composition in the present embodiment may be configured to contain substantially no benzoxazine compound. Substantially containing no benzoxazine compound means that the content of the benzoxazine compound is less than 0.1 parts by mass based on 100 parts by mass of the resin solid content in the resin composition.
[0465] <<Compounds containing a (meth)allyl group>>
[0466] The resin composition of the present embodiment preferably contains a compound containing a (meth)allyl group, and more preferably contains a compound containing an allyl group.
[0467] The compound containing a (meth)allyl group is preferably a compound containing two or more (meth)allyl groups, and more preferably a compound containing two or more allyl groups.
[0468] The compound containing a (meth)allyl group is preferably at least one selected from the group consisting of an allyl isocyanurate compound, an allyl-substituted nadic imide compound, an allyl compound having a glycoluril structure, and diallyl phthalate. It is more preferred that the compound contains at least one selected from the group consisting of an allyl isocyanurate compound, an allyl-substituted nadic imide compound, and an allyl compound having a glycoluril structure. It is further preferred that the compound contains an allyl-substituted nadic imide compound, and even more preferred that the compound contains an alkenyl-substituted nadic imide compound.
[0469] The alkenyl-substituted nadic acid imide compound is not particularly limited as long as it is a compound having one or more alkenyl-substituted nadic acid imide groups in the molecule. Among them, the compound represented by formula (AN-1) is preferred. By using such an alkenyl-substituted nadic acid imide compound, there is a tendency that the thermal expansion coefficient of the obtained cured product is lower and the heat resistance is further improved.
[0470]
[0471] (In formula (AN-1), R1 each independently represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms, and R2 represents an alkylene group having 1 to 6 carbon atoms, a phenylene group, a biphenylene group, a naphthylene group, a group represented by formula (AN-2), or a group represented by formula (AN-3).)
[0472]
[0473] (In formula (AN-2), R3 represents methylene, isopropylidene, -C(=O)-, -O-, -S- or -S(=O)2-.)
[0474]
[0475] (In formula (AN-3), R4 each independently represents an alkylene group having 1 to 4 carbon atoms or a cycloalkylene group having 5 to 8 carbon atoms.)
[0476] Among the compounds represented by formula (AN-1), the compounds represented by formula (AN-4) and (AN-5) are preferred. By using such alkenyl-substituted nadic imide compounds, the thermal expansion coefficient of the obtained cured product tends to be lower and the heat resistance is further improved.
[0477]
[0478] Other alkenyl-substituted nadic acid imide compounds may also be commercially available. The commercially available products are not particularly limited, and examples thereof include BANI-M (manufactured by Maruzen Petrochemical Co., Ltd., a compound represented by formula (AN-4)), BANI-X (manufactured by Maruzen Petrochemical Co., Ltd., a compound represented by formula (AN-5)), and the like.
[0479] The resin composition of the present embodiment preferably contains a compound containing a (meth)allyl group (preferably an alkenyl-substituted nadic imide compound) within a range that does not impair the effects of the present invention. When the resin composition of the present embodiment contains a compound containing a (meth)allyl group (preferably an alkenyl-substituted nadic imide compound), its content is preferably 0.1 parts by mass or more relative to 100 parts by mass of the resin solid content in the resin composition, and is preferably 50 parts by mass or less.
[0480] The resin composition in the present embodiment may contain only one (meth)allyl group-containing compound (preferably an alkenyl-substituted nadic imide compound), or may contain two or more thereof. When containing two or more thereof, the total amount is preferably within the above range.
[0481] In addition, the resin composition in the present embodiment may be a composition that substantially does not contain an alkenyl-substituted nadic imide compound (and further, a compound containing a (meth)allyl group). Substantially containing no alkenyl-substituted nadic imide compound (and further, a compound containing a (meth)allyl group) means that the content of the alkenyl-substituted nadic imide compound (and further, a compound containing a (meth)allyl group) is less than 0.1 parts by mass relative to 100 parts by mass of the resin solid content in the resin composition.
[0482] The content (total amount) of the thermosetting resin in the resin combination of the present embodiment is preferably more than 3 mass parts relative to 100 mass parts of resin solids, more preferably more than 5 mass parts, further preferably more than 10 mass parts, more preferably more than 20 mass parts, further preferably more than 30 mass parts, further preferably more than 40 mass parts, and can also be more than 50 mass parts.By being set to more than the aforementioned lower limit, heat resistance, plating adhesion, low thermal expansion etc. have a tendency to be more improved.In addition, relative to 100 mass parts of resin solids, the upper limit of the content of thermosetting resin is preferably less than 95 mass parts, more preferably less than 90 mass parts, further preferably less than 85 mass parts, more preferably less than 75 mass parts, further preferably less than 70 mass parts, and can also be less than 65 mass parts.By being set to less than the aforementioned upper limit, low dielectric properties, low water absorption have a tendency to be more improved.
[0483] The resin composition of the present embodiment may contain only one thermosetting resin or two or more thermosetting resins. When two or more thermosetting resins are contained, the total amount is preferably within the above range.
[0484] <<Inorganic fillers>>
[0485] The resin composition of the present embodiment may not contain an inorganic filler, or may contain an inorganic filler.
[0486] By including inorganic fillers, the dielectric properties (low dielectric constant, low dielectric loss tangent, etc.), flame retardancy, low thermal expansion and other physical properties of the resin composition and its cured product can be further improved. In addition, by reducing the content of inorganic fillers, the peeling between the resin composition layer and the metal foil, the peeling and ridges of the interface between the resin composition layer and the circuit substrate can be more effectively suppressed.
[0487] In addition, for the inorganic filler used in the present embodiment, it is more preferred that the low dielectric properties are excellent. For example, for the inorganic filler used in the present embodiment, the relative dielectric constant (Dk) measured by the cavity resonance perturbation method is preferably 8.0 or less, more preferably 6.0 or less, and further preferably 4.0 or less. In addition, the lower limit of the relative dielectric constant is, for example, more than 2.0, which is more practical. In addition, for the inorganic filler used in the present embodiment, the dielectric loss tangent (Df) measured by the cavity resonance perturbation method is preferably less than 0.05, more preferably less than 0.01. In addition, the lower limit of the dielectric loss tangent is, for example, more than 0.0001, which is more practical.
[0488] The average particle size (D50) of the inorganic filler is not particularly limited, but is preferably 0.1 μm or more, more preferably 0.5 μm or more. In terms of dispersibility, the average particle size (D50) of the inorganic filler is preferably 5 μm or less, more preferably 3 μm or less.
[0489] It should be noted that the average particle size (D50) refers to the value when the volume of the smallest particles reaches 50% of the total volume, measured by a particle size distribution measuring device such as a laser diffraction / scattering method, in which a predetermined amount of powder is added to a dispersion medium. When the dispersion medium herein includes a solvent, it refers to the solvent.
[0490] The inorganic filler used in the present embodiment is not particularly limited in type, and inorganic fillers commonly used in the art can be suitably used. Specifically, for example, natural silica, fused silica, synthetic silica, amorphous silica, aerosil, hollow silica and other silicas, aluminum oxide, white carbon, titanium white, titanium oxide, zinc oxide, magnesium oxide, zirconium oxide and other metal oxides, zinc borate, zinc stannate, forsterite, barium titanate, strontium titanate, calcium titanate and other composite oxides, boron nitride, aggregated boron nitride, silicon nitride, aluminum nitride and other nitrides, aluminum hydroxide, aluminum hydroxide heat-treated products (aluminum hydroxide is added to the heat treatment to reduce a portion of the crystal water), boehmite, metal hydroxides such as magnesium hydroxide (including hydrates), molybdenum compounds such as molybdenum oxide and zinc molybdate, barium sulfate, clay, kaolin, talc, calcined clay, calcined kaolin, calcined talc, mica, E-glass, A-glass, NE-glass, C-glass, L-glass, D-glass, S-glass, M-glass G20, glass staple fibers (including glass micropowders such as E-glass, T-glass, D-glass, S-glass, and Q-glass), hollow glass, spherical glass, etc.
[0491] In the present embodiment, inorganic filler preferably comprises more than one selected from the group consisting of silicon dioxide, aluminum hydroxide, aluminum nitride, boron nitride, forsterite, titanium oxide, barium titanate, strontium titanate and calcium titanate, and from the viewpoint of low dielectric properties, more preferably comprises more than one selected from the group consisting of silicon dioxide and aluminum hydroxide, and further preferably comprises silicon dioxide. By using these inorganic fillers, the heat resistance, dielectric properties, thermal expansion properties, dimensional stability, flame retardancy and other properties of the cured product of resin combination are further improved.
[0492] The content of the inorganic filler in the resin combination of the present embodiment can be appropriately set according to the desired characteristics, is not particularly limited, and is more than 0 mass parts relative to 100 mass parts of the resin solids in the resin combination, preferably more than 10 mass parts, more preferably more than 20 mass parts. By being set to more than the aforementioned lower limit, low thermal expansion, low dielectric loss tangent have a tendency to be more improved. In addition, relative to 100 mass parts of resin solids, the upper limit of the content of the inorganic filler is preferably less than 250 mass parts, more preferably less than 200 mass parts, further preferably less than 180 mass parts, more preferably less than 150 mass parts, further preferably less than 120 mass parts, can also be less than 100 mass parts, less than 80 mass parts, less than 60 mass parts. By being set to less than the aforementioned upper limit, the peeling, the protuberance at the interface of the resin combination layer and the circuit substrate can be more effectively suppressed, and the formability has a tendency to be more improved.
[0493] In the resin composition of the present embodiment, as an example of a preferred embodiment, the content of the inorganic filler is 10% by mass to 70% by mass (preferably 15% by mass to 65% by mass) of the components excluding the solvent.
[0494] The resin composition of the present embodiment may contain only one inorganic filler, or may contain two or more inorganic fillers. When containing two or more inorganic fillers, the total amount is preferably within the above range.
[0495] The resin composition of the present embodiment may further contain a silane coupling agent. By containing a silane coupling agent, there is a tendency that the dispersibility of the inorganic filler and the bonding strength between the resin component and the inorganic filler are further improved.
[0496] There is no particular limitation on the silane coupling agent, and examples thereof include silane coupling agents commonly used in surface treatment of inorganic substances, such as aminosilane compounds (e.g., γ-aminopropyl triethoxysilane, N-β-(aminoethyl)-γ-aminopropyl trimethoxysilane, etc.), epoxysilane compounds (e.g., γ-glycidyloxypropyl trimethoxysilane, etc.), vinylsilane compounds (e.g., vinyl trimethoxysilane, etc.), styryl silane compounds (e.g., styryl trimethoxysilane, etc.), acrylic silane compounds (e.g., γ-acryloxypropyl trimethoxysilane, etc.), cationic silane compounds (e.g., N-β-(N-vinylbenzylaminoethyl)-γ-aminopropyl trimethoxysilane hydrochloride, etc.), phenyl silane compounds, etc. The silane coupling agent can be used alone or in combination of two or more. Among these, the silane coupling agent is preferably an epoxysilane compound. As an epoxysilane-based compound, "KBM-403", "KBM-303", "KBM-402", "KBE-403" etc. are mentioned, for example, the product of Shin-Etsu Chemical Co., Ltd.
[0497] The content of the silane coupling agent is not particularly limited, but may be 0.1 to 5.0 parts by mass based on 100 parts by mass of the resin solid content.
[0498] The resin composition of this embodiment may contain an organic filler, which includes styrene-type, butadiene-type, acrylic-type rubber powders, core-shell-type rubber powders, silicone resin powders, silicone rubber powders, silicone composite powders, fluororesin fillers, and the like.
[0499] In this embodiment, it is preferred that the organic filler is substantially free of content, which means that the content of the organic filler is 10% by mass or less of the content of the inorganic filler, preferably 5% by mass or less, more preferably 3% by mass or less, and even more preferably 1% by mass or less.
[0500] <<Monomer or oligomer having an ethylenically unsaturated group>>
[0501] In the resin composition of the present embodiment, in order to improve the curability of thermosetting, low dielectric properties and active energy ray (such as ultraviolet light curability, etc.), monomers or oligomers with ethylenically unsaturated groups can also be used in combination. The oligomer or monomer with ethylenically unsaturated groups used in the present embodiment is not particularly limited as long as it is an oligomer or monomer with more than one ethylenically unsaturated group in one molecule, for example, monomers or oligomers with (meth) acryloyl, vinyl, etc. can be cited.
[0502] In the present specification, a compound that is a monomer or oligomer having an ethylenically unsaturated group and is also a polyphenylene ether compound having a carbon-carbon unsaturated double bond at a terminal is referred to as a polyphenylene ether compound having a carbon-carbon unsaturated double bond at a terminal.
[0503] In the resin composition of the present embodiment, as a monomer or oligomer having an ethylenically unsaturated group, a low molecular weight vinyl compound having a molecular weight of less than 1000 and containing an ethylenically unsaturated group (hereinafter sometimes referred to as a "low molecular weight vinyl compound") may also be included. By mixing the low molecular weight vinyl compound, the moisture absorption and heat resistance of the obtained cured product tends to be further improved.
[0504] In addition, the low molecular weight vinyl compound used in the present embodiment is preferably composed only of atoms selected from the group consisting of carbon atoms, hydrogen atoms, oxygen atoms, nitrogen atoms and silicon atoms, more preferably composed only of atoms selected from the group consisting of carbon atoms, hydrogen atoms, oxygen atoms and silicon atoms, and further preferably composed only of atoms selected from the group consisting of carbon atoms, hydrogen atoms and oxygen atoms.
[0505] The low molecular weight vinyl compound used in this embodiment may or may not have a polar group. The low molecular weight vinyl compound used in this embodiment is preferably one without a polar group. Examples of the polar group include amino, carboxyl, hydroxyl, and nitro groups.
[0506] In the present embodiment, the molecular weight of low molecular weight vinyl compound is preferably more than 70, more preferably more than 80, further preferably more than 90.By being set to more than the aforementioned lower limit, there is the tendency that can suppress the volatilization of low molecular weight vinyl compound from the resin combination of the present embodiment, its cured product etc..The upper limit of the molecular weight of low molecular weight vinyl compound is preferably less than 500, more preferably less than 400, further preferably less than 300, more preferably less than 200, also can be less than 150.By being set to below the aforementioned upper limit, the effect of the reactivity of the polymer with the structural unit shown in formula (V) is improved more.
[0507] When the resin composition of the present embodiment contains two or more low molecular weight vinyl compounds, the average molecular weight of the low molecular weight vinyl compounds is preferably within the above range, and the molecular weight of each compound is more preferably within the above preferred range.
[0508] In the present embodiment, the boiling point of the low molecular weight vinyl compound is preferably above 110°C, more preferably above 115°C, and further preferably above 120°C. By setting it to above the aforementioned lower limit, the volatilization of the low molecular weight vinyl compound when the resin composition is thermally cured can be suppressed, and the vinyl and low molecular weight vinyl compounds possessed by the polymer having the structural unit shown in formula (V) can be more effectively reacted. The boiling point of the low molecular weight vinyl compound is preferably below 300°C, more preferably below 250°C, and further preferably below 200°C. By setting it to below the aforementioned upper limit, it can be difficult to remain in the cured product in the form of a residual solvent.
[0509] When the resin composition of the present embodiment contains two or more low-molecular vinyl compounds, the average value of the boiling points may be within the above range, but the boiling points of the individual compounds are preferably within the above preferred range.
[0510] Examples of the low molecular weight vinyl compound include: (meth)acrylate compounds, aromatic vinyl compounds (preferably styrene compounds), saturated fatty acid vinyl compounds, cyanide vinyl compounds, ethylenically unsaturated carboxylic acids, ethylenically unsaturated carboxylic acid anhydrides, ethylenically unsaturated dicarboxylic acid monoalkyl esters, ethylenically unsaturated carboxylic acid amides, vinyl silane compounds (e.g., vinyltrialkoxysilanes, etc.), acrylic silane compounds (e.g., acrylictrialkoxysilanes, etc.), methacrylic silane compounds (e.g., methacrylictrialkoxysilanes, etc.), styrenesilane compounds (e.g., styryltrialkoxysilanes, etc.), and the like.
[0511] The first embodiment of the low molecular weight vinyl compound is at least one selected from the group consisting of (meth)acrylate compounds, aromatic vinyl compounds, saturated fatty acid vinyl compounds, cyanide vinyl compounds, ethylenically unsaturated carboxylic acids, ethylenically unsaturated carboxylic acid anhydrides, ethylenically unsaturated dicarboxylic acid monoalkyl esters and ethylenically unsaturated carboxylic acid amides.
[0512] The second embodiment of the low molecular weight vinyl compound is at least one selected from the group consisting of (meth)acrylate compounds, aromatic vinyl compounds, saturated fatty acid vinyl compounds, vinyl silane compounds, acrylic silane compounds, methacrylic silane compounds, and styryl silane compounds, preferably aromatic vinyl compounds and / or vinyl silane compounds.
[0513] Specific examples of the low molecular weight vinyl compound include methylstyrene, ethylvinylbenzene, vinyltrimethoxysilane, and vinyltriethoxysilane.
[0514] In the resin composition of the present embodiment, the monomer or oligomer having an ethylenically unsaturated group is preferably a methylstyrene monomer and / or a styrene oligomer. The details of the styrene oligomer can be referred to in paragraphs 0065 to 0067 of International Publication No. 2019 / 230945, and the contents thereof are introduced into this specification. As a methylstyrene monomer, for example, 4-methylstyrene can be cited.
[0515] For details of other monomers or oligomers having an ethylenically unsaturated group, reference may be made to paragraphs 0069 to 0087 of International Publication No. 2017 / 135168, the contents of which are incorporated herein by reference.
[0516] When the resin combination of the present embodiment includes the monomer or oligomer with ethylenically unsaturated groups, its content is preferably more than 0.5 mass parts relative to 100 mass parts of resin solids, more preferably more than 1 mass parts, further preferably more than 2 mass parts, more preferably more than 3 mass parts.By being set to more than the aforementioned lower limit, low dielectric properties have a tendency to be further improved.In addition, relative to 100 mass parts of resin solids, the upper limit value of the content of the monomer or oligomer with ethylenically unsaturated groups is preferably less than 25 mass parts, more preferably less than 20 mass parts, more preferably less than 10 mass parts.By being set to less than the aforementioned upper limit, heat resistance has a tendency to be further improved.
[0517] The resin composition of the present embodiment may contain only one monomer or oligomer having an ethylenically unsaturated group, or may contain two or more monomers or oligomers. When two or more monomers or oligomers are contained, the total amount is preferably within the above range.
[0518] <<Elastomer>>
[0519] The resin composition of the present embodiment may contain an elastomer.
[0520] In the present embodiment, there is no particular limitation on the elastomer, and examples thereof include at least one selected from the group consisting of polyisoprene, polybutadiene, styrene butadiene, butyl rubber, ethylene propylene rubber, styrene butadiene ethylene, styrene butadiene styrene, styrene isoprene styrene, styrene ethylene butylene styrene, styrene propylene styrene, styrene ethylene propylene styrene, fluororubber, silicone rubber, their hydrides, their alkyl compounds, and their copolymers.
[0521] In addition, it may be a thermoplastic elastomer or a thermosetting elastomer, but is preferably a thermoplastic elastomer.
[0522] The number average molecular weight of the elastomer used in this embodiment is preferably 50,000 or more. By setting the number average molecular weight to 50,000 or more, there is a tendency that the low dielectric properties of the obtained cured product are more excellent. The aforementioned number average molecular weight is preferably 60,000 or more, more preferably 70,000 or more, and further preferably 80,000 or more. The upper limit of the number average molecular weight of the aforementioned elastomer is preferably 400,000 or less, more preferably 350,000 or less, and further preferably 300,000 or less. By setting it below the aforementioned upper limit, there is a tendency to further improve the solubility of the elastomer component in the resin composition.
[0523] When the resin composition of the present embodiment contains two or more elastomers, it is preferred that the number average molecular weight of the mixture thereof satisfy the above range.
[0524] In the present embodiment, the elastomer is preferably a thermoplastic elastomer containing styrene monomer units and conjugated diene monomer units (hereinafter referred to as "thermoplastic elastomer (E)"). By using such a thermoplastic elastomer (E), the obtained cured product has more excellent low dielectric properties.
[0525] The thermoplastic elastomer (E) contains styrene monomer units. By containing styrene monomer units, the solubility of the thermoplastic elastomer (E) in the resin composition can be improved. As styrene monomers, styrene, α-methylstyrene, p-methylstyrene, divinylbenzene (vinyl styrene), N,N-dimethyl-p-aminoethylstyrene, N,N-diethyl-p-aminoethylstyrene, etc. can be exemplified. Among them, from the viewpoint of availability and productivity, it is preferred to select one or more of the group consisting of styrene, α-methylstyrene and p-methylstyrene. Among them, styrene is particularly preferred.
[0526] The content of the styrene monomer unit in the thermoplastic elastomer (E) is preferably in the range of 10 to 50% by mass of all monomer units, more preferably in the range of 13 to 45% by mass, and further preferably in the range of 15 to 40% by mass. If the content of the styrene monomer unit is 50% by mass or less, the adhesion and adhesiveness to the substrate etc. become better. In addition, if it is 10% by mass or more, there is a tendency that excessive adhesion can be suppressed, residual adhesive and stop marks are not easily generated, and the easy peelability of the bonding surfaces becomes good, so it is preferred.
[0527] The thermoplastic elastomer (E) may contain only one type of styrene monomer unit, or may contain two or more types. When containing two or more types, the total amount is preferably within the above range.
[0528] It should be noted that the method for measuring the content of the styrene monomer unit in the thermoplastic elastomer (E) can refer to the description of International Publication No. 2017 / 126469, and the content thereof is incorporated herein. The same applies to the conjugated diene monomer unit described later.
[0529] The thermoplastic elastomer (E) contains conjugated diene monomer units. By containing conjugated diene monomer units, the solubility of the thermoplastic elastomer (E) in the resin composition is improved. The conjugated diene monomer is not particularly limited as long as it is a diene having one pair of conjugated double bonds. As conjugated diene monomers, for example: 1,3-butadiene, 2-methyl-1,3-butadiene (isoprene), 2,3-dimethyl-1,3-butadiene, 1,3-pentadiene, 2-methyl-1,3-pentadiene, 1,3-hexadiene, farnesene, preferably 1,3-butadiene and / or isoprene, more preferably 1,3-butadiene.
[0530] The thermoplastic elastomer (E) may contain only one type of conjugated diene monomer unit, or may contain two or more types.
[0531] In the thermoplastic elastomer (E), the mass ratio of the styrene monomer unit to the conjugated diene monomer unit is preferably in the range of styrene monomer unit / conjugated diene monomer unit=5 / 95 to 80 / 20, more preferably in the range of 7 / 93 to 77 / 23, and further preferably in the range of 10 / 90 to 70 / 30. If the mass ratio of the styrene monomer unit to the conjugated diene monomer unit is in the range of 5 / 95 to 80 / 20, excessive adhesion can be suppressed and high adhesion can be maintained, and the easy peelability of the adhesive surfaces becomes good.
[0532] In the thermoplastic elastomer (E), all, part, or no conjugated diene bonds of the thermoplastic elastomer may be hydrogenated.
[0533] The thermoplastic elastomer (E) may or may not contain other monomer units in addition to the styrene monomer units and the conjugated diene monomer units. Examples of other monomer units include aromatic vinyl compound units other than the styrene monomer units.
[0534] In the thermoplastic elastomer (E), the total content of the styrene monomer units and the conjugated diene monomer units is preferably 90% by mass or more, more preferably 95% by mass or more, further preferably 97% by mass or more, and even more preferably 99% by mass or more of all monomer units.
[0535] The thermoplastic elastomer (E) may contain only one type of each of the styrene monomer unit and the conjugated diene monomer unit, or may contain two or more types. When containing two or more types, the total amount is preferably within the above range.
[0536] The thermoplastic elastomer (E) may be a block polymer or a random polymer. The conjugated diene monomer unit may be a hydrogenated elastomer, an unhydrogenated elastomer, or a partially hydrogenated elastomer.
[0537] In one embodiment of the present embodiment, the thermoplastic elastomer (E) is a hydrogenated elastomer. Here, the hydrogenated elastomer refers to, for example, a thermoplastic elastomer in which the double bonds based on the conjugated diene monomer units are hydrogenated, and includes, in addition to a hydrogenation rate of 100%, a hydrogenation rate of 80% or more. The hydrogenation rate in the hydrogenated elastomer is preferably 85% or more, more preferably 90% or more, and further preferably 95% or more. In the present embodiment, the hydrogenation rate is 1 The measurement results of H-NMR spectrum measurement were calculated.
[0538] In one embodiment of the present embodiment, the thermoplastic elastomer (E) is an unhydrogenated elastomer. Here, the unhydrogenated elastomer is a concept including an elastomer in which the proportion of double bonds based on conjugated diene monomer units in the elastomer that are hydrogenated, that is, a hydrogenation rate of 20% or less. The hydrogenation rate in the unhydrogenated elastomer is preferably 15% or less, more preferably 10% or less, and further preferably 5% or less.
[0539] On the other hand, the partially hydrogenated elastomer refers to a thermoplastic elastomer in which a part of the double bonds based on the conjugated diene monomer units are hydrogenated, and generally refers to an elastomer having a hydrogenation rate of less than 80% and more than 20%.
[0540] The thermoplastic elastomer (E) may also have an acidic functional group and / or a basic functional group. Examples of the basic functional group include an amino group, an imino group, a nitrile group, a pyridyl group, a quinoline group, and an amide group. Examples of the acidic functional group include a carboxyl group, an acid anhydride group, a phenolic hydroxyl group, a phosphoric acid group, and a sulfonic acid group.
[0541] Examples of commercially available products of the thermoplastic elastomer (E) used in the present embodiment include SEPTON (registered trademark) 2104 manufactured by Kuraray Co., Ltd., SOE (registered trademark) S1606, S1613, S1609, S1605 manufactured by Asahi Kasei Corporation, TUFTEC M1943, M1913, M1911, TUFTEC MP10, and DYNARON (registered trademark) 9901P and TR2250 manufactured by JSR Corporation.
[0542] When the resin composition of the present embodiment includes an elastomer (preferably a thermoplastic elastomer (E)), its content is preferably more than 1 mass part relative to 100 mass parts of resin solids, more preferably more than 5 mass parts, further preferably more than 8 mass parts, more preferably more than 10 mass parts, according to the purpose, more preferably more than 15 mass parts, and more preferably more than 20 mass parts. By being set to more than the aforementioned lower limit, low dielectric properties have a tendency to be further improved. In addition, the upper limit of the content of the aforementioned elastomer is preferably less than 45 mass parts relative to 100 mass parts of resin solids, more preferably less than 40 mass parts, more preferably less than 35 mass parts, more preferably less than 30 mass parts, and can also be less than 25 mass parts. By being set to less than the aforementioned upper limit, there is a tendency for heat resistance to be further improved.
[0543] The resin composition of the present embodiment may contain only one type of elastomer, or may contain two or more types. When containing two or more types, the total amount is preferably within the above range.
[0544] <<Active ester compounds>>
[0545] The resin composition of the present embodiment may contain an active ester compound.
[0546] The active ester compound is not particularly limited, and examples thereof include compounds having two or more (preferably 2 to 12, more preferably 2 to 6, further preferably 2 to 4, further preferably 2 or 3, further preferably 2) active ester groups in one molecule.
[0547] The active ester compound may also be a straight chain, branched chain or cyclic compound. Among these, from the viewpoint of further improving the heat resistance of the obtained cured product, it is preferred that the active ester compound is obtained by reacting a carboxylic acid compound and / or a thiocarboxylic acid compound with a hydroxy compound and / or a thiol compound, more preferably, the active ester compound is obtained by reacting a carboxylic acid compound with one or more compounds selected from the group consisting of a phenol compound, a naphthol compound and a thiol compound, further preferably, an aromatic compound having two or more active ester groups in one molecule obtained by reacting a carboxylic acid compound with an aromatic compound having a phenolic hydroxyl group, and particularly preferably, an aromatic compound having two or more active ester groups in one molecule obtained by reacting a compound having two or more carboxylic acids in one molecule with an aromatic compound having a phenolic hydroxyl group.
[0548] Examples of the carboxylic acid compound include at least one selected from the group consisting of benzoic acid, acetic acid, succinic acid, maleic acid, itaconic acid, phthalic acid, isophthalic acid, terephthalic acid and pyromellitic acid. Among these, from the viewpoint of further improving the heat resistance of the obtained cured product, at least one selected from the group consisting of succinic acid, maleic acid, itaconic acid, phthalic acid, isophthalic acid and terephthalic acid is preferred, and at least one selected from the group consisting of isophthalic acid and terephthalic acid is more preferred.
[0549] Examples of the thiocarboxylic acid compound include one or more selected from thioacetic acid and thiobenzoic acid.
[0550] Examples of the phenol compound or naphthol compound include hydroquinone, resorcinol, bisphenol A, bisphenol F, bisphenol S, phenolphthalein, methylated bisphenol A, methylated bisphenol F, methylated bisphenol S, phenol, o-cresol, m-cresol, p-cresol, catechol, α-naphthol, β-naphthol, 1,5-dihydroxynaphthalene, 1,6-dihydroxynaphthalene, 2,6-dihydroxynaphthalene, dihydroxybenzophenone, trihydroxybenzophenone, tetrahydroxybenzophenone, phloroglucinol, pyrogallol, At least one selected from the group consisting of dicyclopentadienyl diphenol and phenol novolac, preferably bisphenol A, bisphenol F, bisphenol S, methylated bisphenol A, methylated bisphenol F, methylated bisphenol S, catechol, α-naphthol, β-naphthol, 1,5-dihydroxynaphthalene, 1,6-dihydroxynaphthalene, 2,6-dihydroxynaphthalene, dihydroxybenzophenone, trihydroxybenzophenone, tetrahydroxybenzophenone, m-benzophenone, 1,2-dihydroxynaphthalene, 1,3-dihydroxybenzophenone, 1,4-dihydroxybenzophenone, 1,6-dihydroxynaphthalene ... pyrogallol, pyrogallol, dicyclopentadienyl diphenol, phenol novolac, more preferably one or more selected from the group consisting of catechol, 1,5-dihydroxynaphthalene, 1,6-dihydroxynaphthalene, 2,6-dihydroxynaphthalene, dihydroxybenzophenone, trihydroxybenzophenone, tetrahydroxybenzophenone, phloroglucinol, pyrogallol, dicyclopentadienyl diphenol and phenol novolac, further preferably one or more selected from the group consisting of 1,5-dihydroxynaphthalene, 1,6-dihydroxynaphthalene, 2,6-dihydroxynaphthalene , dihydroxybenzophenone, trihydroxybenzophenone, tetrahydroxybenzophenone, dicyclopentadienyl diphenol and phenol novolac consisting of one or more, particularly preferably selected from the group consisting of dihydroxybenzophenone, trihydroxybenzophenone, tetrahydroxybenzophenone, dicyclopentadienyl diphenol and phenol novolac consisting of one or more (preferably selected from the group consisting of dicyclopentadienyl diphenol and phenol novolac consisting of one or more, more preferably dicyclopentadienyl diphenol).
[0551] Examples of the thiol compound include one or more selected from the group consisting of benzenedithiol and triazine dimethiol.
[0552] In addition, as the active ester compound, from the viewpoint of further improving the compatibility with the epoxy compound, preferably a compound having two or more carboxylic acids and containing an aliphatic chain in one molecule, and from the viewpoint of further improving the heat resistance, preferably a compound having an aromatic ring. As a more specific active ester compound, the active ester compounds described in Japanese Patent Laid-Open No. 2004-277460 can be cited.
[0553] Active ester compound can use commercially available products, and also can be prepared by known methods.As commercially available products, compounds (for example: EXB9451, EXB9460, EXB9460S, HPC-8000-65T (all DIC Co., Ltd. system) etc.) comprising dicyclopentadienyl diphenol structure, acetylated products (for example: DC808 (Mitsubishi Chemical Co., Ltd. system)) of phenol novolac and benzoylated products (for example: YLH1026, YLH1030, YLH1048 (all Mitsubishi Chemical Co., Ltd. system)) of phenol novolac can be listed, for the storage stability of varnish, the viewpoint that the low thermal expansion of (cured product) is further improved when the resin composition is cured, preferably EXB9460S.
[0554] The active ester compound can be prepared by a known method, for example, by a condensation reaction of a carboxylic acid compound and a hydroxy compound. As a specific example, the following method can be mentioned: (a) a carboxylic acid compound or a halide thereof, (b) a hydroxy compound, and (c) an aromatic monohydroxy compound are reacted in a ratio of 0.05 to 0.75 moles of phenolic hydroxyl groups of (b) and 0.25 to 0.95 moles of (c) to 1 mole of carboxyl groups or acyl halide groups of (a).
[0555] The active ester compound is preferably contained in a range that does not impair the effects of the present invention. When the resin composition of the present embodiment contains an active ester compound, the amount is preferably 0.1 parts by mass or more and preferably 50 parts by mass or less per 100 parts by mass of the resin solid content in the resin composition.
[0556] The resin composition in the present embodiment may contain only one active ester compound or two or more thereof. When containing two or more thereof, the total amount is preferably within the above range.
[0557] In addition, the resin composition in the present embodiment may be configured to be substantially free of active ester compounds. Substantially free means that the content of active ester compounds may be less than 1 part by mass, preferably less than 0.1 part by mass, and more preferably less than 0.01 part by mass relative to 100 parts by mass of the resin solid content in the resin composition.
[0558] <<Flame retardant>>
[0559] The resin composition of the present embodiment may contain a flame retardant. Examples of the flame retardant include phosphorus-based flame retardants, halogen-based flame retardants, inorganic-based flame retardants, and silicone-based flame retardants, and phosphorus-based flame retardants are preferred.
[0560] As the flame retardant, known ones can be used, and examples thereof include halogen flame retardants such as brominated epoxy resin, brominated polycarbonate, brominated polystyrene, brominated styrene, bromophthalimide, tetrabromobisphenol A, pentabromobenzyl (meth)acrylate, pentabromotoluene, tribromophenol, hexabromobenzene, decabromodiphenyl ether, bis-1,2-pentabromophenylethane, chlorinated polystyrene, and chlorinated paraffin; red phosphorus, tricresyl phosphate, triphenyl phosphate, cresyl diphenyl phosphate, tri(dimethyl phthalate), and the like. Phosphorus-based flame retardants such as 2,4-dimethylphenyl phosphate, 1,3-phenylenebis(2,6-di(xylyl)phosphate), 10-(2,5-dihydroxyphenyl)-10H-9-oxa-10-phosphaphenanthrene-10-oxide; inorganic flame retardants such as aluminum hydroxide, magnesium hydroxide, some boehmite, boehmite, zinc borate, antimony trioxide; silicone flame retardants such as silicone rubber and silicone resin.
[0561] In the present embodiment, among these, 1,3-phenylenebis(2,6-di(xylyl)phosphate) is preferred because it does not impair the low dielectric properties.
[0562] When the resin composition of the present embodiment includes a flame retardant, its content is preferably 1 mass part or more, more preferably 5 mass parts or more relative to 100 mass parts of the resin solid content in the resin composition. In addition, the lower limit of the content of the aforementioned flame retardant is preferably 25 mass parts or less, more preferably 20 mass parts or less.
[0563] The flame retardant may be used alone or in combination of two or more. When two or more flame retardants are used, the total amount is within the above range.
[0564] <Dispersant>
[0565] The resin composition of the present embodiment may also include a dispersant. The dispersant may be suitably used for coating applications, and its type is not particularly limited. The dispersant preferably uses a copolymer-based wetting dispersant, and specific examples thereof include: DISPERBYK (registered trademark) -110, 111, 161, 180, 2009, 2152, 2155, BYK (registered trademark) -W996, W9010, W903, W940, etc. manufactured by BYK Japan KK.
[0566] When the resin composition of the present embodiment includes a dispersant, the lower limit of its content is preferably 0.01 mass parts or more relative to 100 mass parts of the resin solid components in the resin composition, more preferably 0.1 mass parts or more, and also can be 0.3 mass parts or more. In addition, the upper limit of the content of the aforementioned dispersant is preferably 10 mass parts or less relative to 100 mass parts of the resin solid components in the resin composition, more preferably 5 mass parts or less, and further preferably 3 mass parts or less.
[0567] The dispersants may be used alone or in combination of two or more. When two or more are used, the total amount is within the above range.
[0568] <<Curing accelerator>>
[0569] The resin composition of this embodiment may further include a curing accelerator. The curing accelerator is not particularly limited, and examples thereof include imidazoles such as 2-ethyl-4-methylimidazole and triphenylimidazole; organic peroxides such as benzoyl peroxide, lauroyl peroxide, acetyl peroxide, p-chlorobenzoyl peroxide, and di-tert-butyl diperoxyphthalate; azo compounds such as azobisisobutyronitrile; N,N-dimethylbenzylamine, N,N-dimethylaniline, N,N-dimethyltoluidine, 2-N-ethylanilinoethanol, tri-n-butylamine, pyridine, quinoline, N-methylmorpholine, triethanolamine, triethylamine, Tertiary amines such as diamine, tetramethylbutylene diamine, and N-methylpiperidine; phenols such as phenol, xylenol, cresol, resorcinol, and catechol; organic metal salts such as lead naphthenate, lead stearate, zinc naphthenate, zinc octoate, manganese octoate, tin oleate, dibutyltin maleate, manganese naphthenate, cobalt naphthenate, and ferric acetylacetonate; these organic metal salts dissolved in hydroxyl-containing compounds such as phenol and bisphenol; inorganic metal salts such as tin chloride, zinc chloride, and aluminum chloride; organic tin compounds such as dioctyltin oxide, other alkyl tins, and alkyl tin oxides, etc.
[0570] Preferred curing accelerators are imidazoles and organic metal salts, and more preferably, a combination of imidazoles and organic metal salts is used.
[0571] The resin composition of the present embodiment may be a composition that substantially does not contain an organic peroxide (e.g., an organic peroxide having a molecular weight of 30 to 500). Substantially free means that the content is less than 0.1 parts by mass, preferably less than 0.01 parts by mass, relative to 100 parts by mass of the resin solid content contained in the resin composition of the present embodiment. By setting the content in such a range, a cured product with better performance can be obtained.
[0572] The resin composition of the present embodiment may be a composition that is substantially free of azo compounds (e.g., azo compounds having a molecular weight of 30 to 500). Substantially free means that the content is less than 0.1 parts by mass, preferably less than 0.01 parts by mass, relative to 100 parts by mass of the resin solid content contained in the resin composition of the present embodiment. By setting the content in such a range, a cured product with various better properties can be obtained.
[0573] When the resin composition of the present embodiment includes a curing accelerator, the lower limit of its content is preferably 0.005 mass parts or more relative to 100 mass parts of the resin solids in the resin composition, more preferably 0.01 mass parts or more, and further preferably 0.1 mass parts or more. In addition, the upper limit of the content of the aforementioned curing accelerator is preferably 10 mass parts or less relative to 100 mass parts of the resin solids in the resin composition, more preferably 5 mass parts or less, and further preferably 2 mass parts or less.
[0574] The curing accelerator may be used alone or in combination of two or more. When two or more are used, the total amount is within the above range.
[0575] <<Solvent>>
[0576] The resin composition of the present embodiment may also include a solvent, preferably an organic solvent. When including a solvent, the resin composition of the present embodiment is preferably a form (solution or varnish) that can dissolve in a solvent or is compatible with a solvent in at least a portion of the above-mentioned various resin solid components, preferably all of them. If the solvent is a polar organic solvent or a non-polar organic solvent that can dissolve or be compatible with at least a portion of the above-mentioned various resin solid components, preferably all of them, there is no particular restriction. As a polar organic solvent, for example, ketones (such as acetone, methyl ethyl ketone, methyl isobutyl ketone, etc.), cellosolves (such as propylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, etc.), esters (such as ethyl lactate, methyl acetate, ethyl acetate, butyl acetate, isoamyl acetate, ethyl lactate, methyl methoxypropionate, methyl hydroxyisobutyrate, etc.), amides (such as dimethoxyacetamide, dimethylformamide, etc.), as a non-polar organic solvent, aromatic hydrocarbons (such as toluene, xylene, etc.) can be listed.
[0577] The solvent may be used alone or in combination of two or more. When two or more solvents are used, the total amount is within the above range.
[0578] <<Ultraviolet light absorber>>
[0579] The resin composition of the present embodiment may contain an ultraviolet absorber.
[0580] The type of ultraviolet absorber is not particularly limited. Examples of the ultraviolet absorber include benzotriazole ultraviolet absorbers, benzophenone ultraviolet absorbers, triazine ultraviolet absorbers, cyclic imino ester ultraviolet absorbers, cyanoacrylate ultraviolet absorbers, conjugated diene ultraviolet absorbers, methyl dibenzoyl ultraviolet absorbers, coumarin ultraviolet absorbers, salicylate ultraviolet absorbers, acrylonitrile ultraviolet absorbers and benzodithiazole ultraviolet absorbers, preferably coumarin ultraviolet absorbers.
[0581] Examples of the benzotriazole ultraviolet absorber include 2-(2-hydroxy-5-methylphenyl)benzotriazole, 2-(2-hydroxy-5-tert-octylphenyl)benzotriazole, 2-(2-hydroxy-3,5-diisopropylphenyl)phenylbenzotriazole, 2-(2-hydroxy-3-tert-butyl-5-methylphenyl)-5-chlorobenzotriazole, 2,2'-methylenebis[4-(1,1,3,3-tetramethylbutyl)-6-(2N-benzotriazol-2-yl)phenol], 2-(2-hydroxy-3,5-di-tert-butylphenyl)benzotriazole, and 2-(2-hydroxy-3,5-di-tert-butylphenyl)benzotriazole. 2-(2-hydroxy-3,5-di-tert-pentylphenyl)benzotriazole, 2-(2-hydroxy-5-tert-octylphenyl)benzotriazole, 2-(2-hydroxy-5-tert-butylphenyl)benzotriazole, 2-(2-hydroxy-4-octyloxyphenyl)benzotriazole, 2,2'-methylenebis(4-isopropylphenyl-6-benzotriazolephenyl), 2,2'-p-phenylenebis(1,3-benzoxazine-4-one), 2-[2-hydroxy-3-(3,4,5,6-tetrahydrophthalimidemethyl)-5-methylphenyl]benzotriazole, etc.
[0582] Examples of the benzophenone-based ultraviolet absorber include 2,4-dihydroxybenzophenone, 2-hydroxy-4-methoxybenzophenone, 2-hydroxy-4-octyloxybenzophenone, 2-hydroxy-4-benzyloxybenzophenone, 2-hydroxy-4-methoxy-5-sulfonyloxybenzophenone, 2-hydroxy-4-methoxy-5-sulfonyloxytrihydride benzophenone, and 2-hydroxy-4-methoxy-5-sulfoxytrihydride benzophenone. reitobenzophenone), 2,2'-dihydroxy-4-methoxybenzophenone, 2,2',4,4'-tetrahydroxybenzophenone, 2,2'-dihydroxy-4,4'-dimethoxybenzophenone, 2,2'-dihydroxy-4,4'-dimethoxy-5-sodiumsulfoxybenzophenone, bis(5-benzoyl-4-hydroxy-2-methoxyphenyl)methane, 2-hydroxy-4-n-dodecyloxybenzophenone, 2-hydroxy-4-methoxy-2'-carboxybenzophenone, etc.
[0583] Examples of the triazine ultraviolet absorber include 2-(4,6-diphenyl-1,3,5-triazin-2-yl)-5-[(hexyl)oxy]-phenol and 2-(4,6-bis(2,4-dimethylphenyl)-1,3,5-triazin-2-yl)-5-[(octyl)oxy]-phenol.
[0584] Examples of the cyclic iminoester ultraviolet absorber include 2,2'-bis(3,1-benzoxazine-4-one), 2,2'-p-phenylenebis(3,1-benzoxazine-4-one), 2,2'-m-phenylenebis(3,1-benzoxazine-4-one), 2,2'-(4,4'-diphenylene)bis(3,1-benzoxazine-4-one), 2,2'-(2,6-naphthalene)bis( 3,1-benzoxazine-4-one), 2,2'-(1,5-naphthalene)bis(3,1-benzoxazine-4-one), 2,2'-(2-methyl-p-phenylene)bis(3,1-benzoxazine-4-one), 2,2'-(2-nitro-p-phenylene)bis(3,1-benzoxazine-4-one) and 2,2'-(2-chloro-p-phenylene)bis(3,1-benzoxazine-4-one).
[0585] Examples of the cyanoacrylate ultraviolet absorber include 1,3-bis-[(2'-cyano-3',3'-diphenylacryloyl)oxy]-2,2-bis[(2-cyano-3,3-diphenylacryloyl)oxy]methyl)propane and 1,3-bis-[(2-cyano-3,3-diphenylacryloyl)oxy]benzene.
[0586] Examples of the coumarin-based ultraviolet absorber include 7-(diethylamino)coumarin, coumarin (7-diethylamino-4-methylcoumarin, 7-hydroxy-4-methylcoumarin), ketocoumarin, and carbonylbiscoumarin.
[0587] In addition to the above, reference may be made to paragraphs 0065 to 0077 of Japanese Patent Application Laid-Open No. 2022-000700 and paragraphs 0019 to 0032 of Japanese Patent Application Laid-Open No. 2020-189783, the contents of which are incorporated into this specification.
[0588] When the resin combination of the present embodiment includes ultraviolet light absorber, its content is preferably greater than 0 mass parts relative to resin solids 100 mass parts, more preferably more than 0.1 mass parts, more preferably more than 0.2 mass parts, more preferably more than 0.3 mass parts, more preferably more than 0.4 mass parts. In addition, the content of ultraviolet light absorber is preferably less than 3.0 mass parts relative to resin solids 100 mass parts, more preferably less than 2.5 mass parts, more preferably less than 2.0 mass parts, more preferably less than 1.5 mass parts, more preferably less than 1.0 mass parts, more preferably less than 0.8 mass parts. By being set to below the aforementioned upper limit, there is a tendency to further reduce the dielectric loss tangent of the cured product obtained.
[0589] The resin composition of the present embodiment may contain only one type of ultraviolet absorber, or may contain two or more types. When containing two or more types, the total amount is preferably within the above range.
[0590] <<Non-metallic organic pigments>>
[0591] The resin composition of the present embodiment may contain a non-metallic organic dye.
[0592] As non-metallic organic pigment, can illustrate cyanine pigment, triphenylmethane pigment, anthraquinone pigment, xanthene pigment, azo pigment, benzopyran pigment, indigo pigment, quinoline pigment, perinone pigment and perylene pigment, preferably anthraquinone pigment and / or perinone pigment.The details of these non-metallic organic pigments can be referred to the record of paragraph 0031 of the record of Japanese Unexamined Patent Publication No. 02-089683, Japanese Unexamined Patent Publication No. 2011-102384, these contents are introduced into this specification sheets.
[0593] When the resin combination of present embodiment comprises non-metallic organic pigment, its content is preferably greater than 0 mass parts relative to resin solids 100 mass parts, more preferably more than 0.2 mass parts, more preferably more than 0.3 mass parts, more preferably more than 0.4 mass parts, more preferably more than 0.45 mass parts.In addition, the content of non-metallic organic pigment is preferably below 2.0 mass parts relative to resin solids 100 mass parts, more preferably below 1.75 mass parts, more preferably below 1.5 mass parts, more preferably below 1.25 mass parts, more preferably below 1.0 mass parts.By being set to below the aforementioned upper limit, there is the tendency that the dielectric loss tangent of the cured product obtained that can be further reduced and the glass transition temperature improves more.
[0594] The resin composition of the present embodiment may contain only one non-metallic organic dye, or may contain two or more. When containing two or more, the total amount is preferably within the above range.
[0595] The resin combination of the present embodiment can be a composition that is substantially free of carbon black and then substantially free of conductive substances.Substantially free of carbon black and then substantially free of conductive substances refers to that the content of carbon black (and then conductive substances) is less than 10% by mass of the content of the non-metallic organic pigment included in the resin combination, preferably below 5% by mass, more preferably below 1% by mass, further preferably below 0.1% by mass.By being set to such a composition, the insulating property of the resin combination or cured product obtained can be higher.
[0596] <<Other ingredients>>
[0597] The resin composition of the present embodiment may contain, in addition to the above-mentioned components, various polymer compounds and various additives such as thermoplastic resins and oligomers thereof other than elastomers. Examples of additives include antioxidants, photopolymerization initiators, fluorescent whitening agents, photosensitizers, dyes, pigments, thickeners, flow regulators, lubricants, defoamers, leveling agents, brighteners, polymerization inhibitors, etc. These additives may be used alone or in combination of two or more.
[0598] The resin composition of the present embodiment can be a composition that does not substantially contain a polymerization initiator. Substantially free means that the content of the polymerization initiator is less than 0.1 mass part relative to 100 mass parts of the resin solids contained in the resin composition of the present embodiment, and is preferably less than 0.01 mass part. By setting it to such a range, various cured products with better performance can be obtained.
[0599] The dielectric loss tangent (Df) when the resin composition of the present embodiment is preferably made into a cured product is low. Specifically, the dielectric loss tangent (Df) of 10GHz measured by the cavity resonance perturbation method is preferably less than 0.1, more preferably less than 0.01, further preferably less than 0.003, and more preferably less than 0.001. The lower limit of dielectric loss tangent (Df) is not particularly limited, and for example, more than 0.0001 is more practical.
[0600] The relative dielectric constant (Dk) of the resin composition of the present embodiment is preferably low when the cured product is made. Specifically, the relative dielectric constant (Dk) of 10GHz measured by the cavity resonance perturbation method is preferably 7 or less, more preferably 3 or less, and further preferably 2.5 or less. The lower limit of the relative dielectric constant (Dk) is not particularly limited, and for example, more than 1 is more practical.
[0601] The dielectric properties of the cured product of the resin composition were measured by the following method.
[0602] When the resin composition contains a solvent, the solvent is evaporated to obtain a resin composition powder. The resin composition powder is filled into a mold with a single side of 100 mm and a thickness of 0.8 mm, and a copper foil (3EC-M2S-VLP, manufactured by Mitsui Mining and Smelting Co., Ltd.) with a thickness of 12 μm is placed on both sides. 2 , vacuum pressing was performed at 220°C for 120 minutes, and then the copper foil on both sides was removed by etching to obtain a cured board with a single side of 100 mm and a thickness of 0.8 mm.
[0603] The obtained cured plate was processed into a size of 1.0 mm×100 mm, dried at 120° C. for 60 minutes, and then the relative dielectric constant (Dk) and dielectric loss tangent (Df) after drying were measured at 10 GHz using a perturbation cavity resonator. The measurement temperature was set at 23° C.
[0604] As the perturbation method cavity resonator, Agilent 8722ES manufactured by Agilent Technologies can be used.
[0605] <Resin composite sheet>
[0606] The resin composite sheet of the present embodiment is used to manufacture a metal foil-clad laminate by a method using a vacuum lamination device and including the following steps, wherein the metal foil-clad laminate is formed by laminating a resin composite sheet on the surface of a circuit substrate A, the resin composite sheet comprises a metal foil and a resin composition layer arranged on a single side of the aforementioned metal foil, the circuit substrate A comprises an insulating layer and a conductor circuit layer, the aforementioned resin composition comprises a thermosetting resin, and the content of the inorganic filler is 0 to 250 parts by weight relative to 100 parts by weight of the resin solid component contained in the aforementioned resin composition.
[0607] Step 1: a step of reducing the content of water and / or solvent contained in the circuit substrate A to obtain the circuit substrate B;
[0608] Step 2: a step of arranging a resin composite sheet including a metal foil and a resin composition layer arranged on one side of the metal foil on at least one surface of a circuit substrate B in such a manner that the resin composition layer side is in contact with the circuit substrate B, and applying pressure from the metal foil side under heating and reduced pressure or vacuum to obtain a laminated substrate D in which the resin composite sheet is laminated on at least one surface of the circuit substrate B;
[0609] Step 3: A step of obtaining a laminated substrate E by heating and pressing the metal foil side surface of the laminated substrate D obtained in step 2 using a pressing metal plate or a laminating metal roll to smooth the surface of the resin composition layer of the laminated substrate D.
[0610] That is, the resin composite sheet in the present embodiment is preferably the resin composite sheet C used in the method for producing the metal-clad laminated plate. Therefore, the details of the resin composite sheet C are also the same as those described in the method for producing the metal-clad laminated plate. In addition, the method for producing the metal-clad laminated plate is the same as those described in the method for producing the metal-clad laminated plate.
[0611] <Manufacturing method of printed circuit board>
[0612] The method for producing a printed wiring board according to the present embodiment includes the method for producing a metal foil-clad laminate according to the present embodiment.
[0613] For details (features) of the method for producing a printed wiring board according to the present embodiment, reference can be made to the matters described in the section "Method for producing a metal-clad laminate according to the present embodiment".
[0614] In addition, for details of the printed circuit board, reference can be made to the description in paragraph 0101 of Japanese Patent Application Laid-Open No. 2022-99579, the contents of which are incorporated into this specification.
[0615] <Method for manufacturing semiconductor device>
[0616] The method for manufacturing a semiconductor device according to the present embodiment includes the method for manufacturing a metal foil-clad laminate according to the present embodiment.
[0617] For details (features) of the method for manufacturing the semiconductor device of the present embodiment, reference can be made to the matters described in the section "Method for manufacturing the metal-clad laminate of the present embodiment".
[0618] In addition, for details of the semiconductor device, reference can be made to paragraphs 0102 to 0104 of Japanese Patent Application Laid-Open No. 2022-99579 and paragraph 0115 of Japanese Patent Application Laid-Open No. 2022-089837, the contents of which are incorporated into this specification.
[0619] Example
[0620] The present invention will be described in more detail below by giving examples. The materials, usage amounts, ratios, processing contents, processing steps, etc. shown in the following examples may be appropriately changed without departing from the gist of the present invention. Therefore, the scope of the present invention is not limited to the specific examples shown below.
[0621] If the measuring equipment used in the examples is difficult to obtain due to discontinuation of production, other equipment with equivalent performance may be used for measurement.
[0622] In the following examples, the heating temperature and the pressurizing pressure were set to the set temperature / set pressure of the equipment.
[0623] <Measurement of weight average molecular weight and number average molecular weight>
[0624] The weight average molecular weight (Mw) and number average molecular weight (Mn) of each resin and compound were measured by gel permeation chromatography (GPC). A liquid delivery pump (LC-20AD manufactured by Shimadzu Corporation), a differential refractive index detector (RID-20A manufactured by Shimadzu Corporation), and a GPC column (GPC KF-801, 802, 803, 804 manufactured by Showa Denko K.K.) were used, tetrahydrofuran was used as the solvent, and the flow rate was 1.0 mL / min, the column temperature was 40°C, and a calibration curve prepared from monodisperse polystyrene was used.
[0625] <Synthesis Example 1 Synthesis of Naphthol Aralkyl Cyanate Compound (SNCN)>
[0626] 300 g (1.28 mol in terms of OH group) of 1-naphthol aralkyl resin (manufactured by Nippon Steel & Sumikin Chemical Co., Ltd.) and 194.6 g (1.92 mol) of triethylamine (1.5 mol per 1 mol of hydroxyl group) were dissolved in 1800 g of dichloromethane to prepare Solution 1.
[0627] 125.9 g (2.05 mol) of cyanogen chloride (1.6 mol per 1 mol of hydroxyl groups), 293.8 g of dichloromethane, 194.5 g (1.92 mol) of 36% hydrochloric acid (1.5 mol per 1 mol of hydroxyl groups), and 1205.9 g of water were added to solution 1 over 30 minutes while stirring, keeping the liquid temperature between -2°C and -0.5°C. After the addition of solution 1, stirring was performed at the same temperature for 30 minutes, and then a solution (solution 2) obtained by dissolving 65 g (0.64 mol) of triethylamine (0.5 mol per 1 mol of hydroxyl groups) in 65 g of dichloromethane was added over 10 minutes. After the addition of solution 2, stirring was performed at the same temperature for 30 minutes to terminate the reaction.
[0628] After that, the reaction solution was allowed to stand to separate the organic phase and the aqueous phase. The obtained organic phase was washed five times with 1300 g of water. The conductivity of the waste water after the fifth water washing was 5 μS / cm, confirming that the removable ionic compounds were sufficiently removed by water washing.
[0629] The organic phase after washing was concentrated under reduced pressure and finally concentrated to dryness at 90°C for 1 hour to obtain 331 g of the target naphthol aralkyl cyanate compound (SNCN) (orange viscous substance). The weight average molecular weight of the obtained SNCN was 600. In addition, the IR spectrum of SNCN showed 2250 cm -1 The absorption of the cyanate group was not shown.
[0630] <Synthesis Example 2 Synthesis of modified polyphenylene ether compound>
[0631] <<Synthesis of bifunctional phenylene ether oligomer>>
[0632] 9.36 g (42.1 mmol) of CuBr2, 1.81 g (10.5 mmol) of N,N'-di(tert-butyl)ethylenediamine, 67.77 g (671.0 mmol) of n-butyldimethylamine, and 2,600 g of toluene were placed in a 12 L vertical reactor equipped with a stirring device, a thermometer, an air inlet pipe, and a baffle. The mixture was stirred at a reaction temperature of 40°C, and nitrogen and air were mixed and adjusted to an oxygen concentration of 8% by volume. The mixture was heated at a flow rate of 5.2 L / min. While bubbling, a mixed solution of 129.32 g (0.48 mol) of 2,2',3,3',5,5'-hexamethyl-(1,1'-biphenol)-4,4'-diol, 878.4 g (7.2 mol) of 2,6-dimethylphenol, 1.22 g (7.2 mmol) of N,N'-di(tert-butyl)ethylenediamine, and 26.35 g (260.9 mmol) of n-butyldimethylamine, which had been dissolved in 2,300 g of methanol, was added dropwise over 230 minutes and stirred. After the addition was completed, 1,500 g of water in which 48.06 g (126.4 mmol) of tetrasodium ethylenediaminetetraacetate was dissolved was added to stop the reaction. The aqueous layer and the organic layer were separated, and the organic layer was washed with a 1N hydrochloric acid aqueous solution and then washed with pure water. The obtained solution was concentrated to 50% by mass using an evaporator to obtain 1981 g of a toluene solution of a bifunctional phenylene ether oligomer (resin "A"). The number average molecular weight of resin "A" based on polystyrene conversion by GPC method was 1,975, the weight average molecular weight based on polystyrene conversion by GPC method was 3,514, and the hydroxyl equivalent was 990.
[0633] <<Synthesis of Modified Polyphenylene Ether Compounds>>
[0634] 833.4 g of a toluene solution of resin "A", 76.7 g of vinylbenzyl chloride (AGC Seimi Chemical Co., Ltd., "CMS-P"), 1,600 g of dichloromethane, 6.2 g of benzyldimethylamine, 199.5 g of pure water, and 83.6 g of a 30.5% by mass NaOH aqueous solution were added to a reactor equipped with a stirring device, a thermometer, and a reflux tube, and stirred at a reaction temperature of 40°C. After stirring for 24 hours, the organic layer was washed with a 1N hydrochloric acid aqueous solution and then washed with pure water. The obtained solution was concentrated with an evaporator, added dropwise to methanol for solidification, and the solid was recovered by filtration and vacuum dried to obtain 450.1 g of a modified polyphenylene ether compound. The number average molecular weight of the modified polyphenylene ether compound based on the polystyrene conversion of the GPC method was 2,250, the weight average molecular weight based on the polystyrene conversion of the GPC method was 3,920, and the vinyl equivalent was 1189 g / vinyl.
[0635] <Synthesis Example 3 Synthesis of a polymer (va) having a structural unit represented by formula (V)>
[0636] 2.25 mol (292.9 g) of divinylbenzene, 1.32 mol (172.0 g) of ethylvinylbenzene, 11.43 mol (1190.3 g) of styrene, and 15.0 mol (1532.0 g) of n-propyl acetate were placed in a reactor, and 600 mmol of a diethyl ether complex of boron trifluoride was added at 70° C. to react for 4 hours. After the polymerization reaction was stopped by an aqueous sodium bicarbonate solution, the oil layer was washed three times with pure water, and decompression and devolatilization were performed at 60° C. to recover a polymer (va) having a structural unit represented by formula (V). The obtained polymer (va) having a structural unit represented by formula (V) was weighed, and 860.8 g of a polymer (va) having a structural unit represented by formula (V) was confirmed.
[0637] <Example 1>
[0638] 30 parts by mass of a maleimide compound (NE-X-9470S, manufactured by DIC Corporation), 1 part by mass of a maleimide compound (MIR-3000-70MT, manufactured by Nippon Kayaku Co., Ltd.), 1 part by mass of the naphthol aralkyl type cyanate ester compound (SNCN) obtained in the above Synthesis Example 1, 15 parts by mass of the modified polyphenylene ether compound obtained in the above Synthesis Example 2, 15 parts by mass of a phosphorus flame retardant (PX-200, manufactured by DAIHACHI CHEMICAL INDUSTRY CO., LTD.), 25 parts by mass of a styrene-based thermoplastic elastomer (SBS, TR2250, Mn115000, manufactured by JSR Corporation), 10 parts by mass of the polymer (va) having a structural unit represented by the formula (V) obtained in the above Synthesis Example 3, 3 parts by mass of 4-methylstyrene (boiling point 175° C.), silica (average particle size (D50, the same hereinafter) 1.1 μm, ADMATECHS COMPANY LIMITED (SC4500SQ classified product), 20 parts by mass of silica (average particle size 0.7 μm, SFP-130MC, manufactured by Denka Co., Ltd.), 0.005 parts by mass of manganese octoate, 0.6 parts by mass of TPIZ (2,4,5-triphenylimidazole, catalyst), and 0.25 parts by mass of imidazole catalyst (2E4MZ, manufactured by Shikoku Chemical Industry Co., Ltd.) were dissolved and mixed in methyl ethyl ketone (solvent) to obtain a varnish. It should be noted that the above-mentioned amounts represent the solid content.
[0639] Maleimide compound (NE-X-9470S)
[0640]
[0641] n is an integer from 1 to 20.
[0642] The obtained varnish is applied to the ultra-thin copper foil surface of an ultra-thin copper foil with a carrier copper foil (carrier copper foil thickness 12 μm, ultra-thin copper foil thickness 1.5 μm, MT-FL, manufactured by Mitsui Mining & Smelting Co., Ltd.) so that the thickness of the dried resin composition layer becomes 30 μm, and the solvent is removed by drying at 150° C. for 5 minutes to obtain a resin composite sheet C consisting of a resin composition layer and an ultra-thin copper foil with a carrier copper foil.
[0643] By patterning a copper-clad laminate CCL-HL832NS (T / T0.8mmt, LC, trade name) manufactured by Mitsubishi Gas Chemical Co., Ltd., a circuit board A having L (pattern width) / S (gap between patterns) = 40 / 40 (μm) was obtained. The size of the obtained circuit board A was 515×415 mm, the average thickness of the portion provided with the conductor circuit was 10 μm, and the thickness of the insulating layer was 800 μm.
[0644] Then, the circuit board A was dried by heating at 130° C. for 2 hours using a dryer manufactured by ESPEC CORP. to obtain a dried circuit board B (step 1). Immediately after the circuit board B was dried, two pieces of the aforementioned resin composite sheets C having a size of 520×420 mm were prepared and arranged on both sides of the aforementioned circuit board so that the resin composition layer side was in contact with the circuit board.
[0645] The object to be processed with the resin composite sheets arranged on both sides of the circuit board B was put into a vacuum laminator manufactured by Nikko-Materials Co., Ltd., and after vacuuming for 30 seconds, the temperature was 150°C and the pressure was 10 kgf / cm 2 The laminated substrate D was obtained by vacuum rubber pressing for 30 seconds under the conditions of 150°C and 10 kgf / cm 2 Under the conditions of , a flat pressing is performed using a pressing metal plate for 60 seconds (step 3) to obtain a laminated substrate E.
[0646] Then, the obtained laminated substrate E was heated at 150° C. for 1 hour using a drying machine manufactured by ESPEC CORP., and then heated to 220° C. for 2 hours to obtain a cured substrate F (step 4). The mass reduction rate of the laminated substrate before and after the heating in step 4 (heating at 150° C. for 1 hour and heating at 220° C. for 2 hours) was 0.1 mass %.
[0647] After being taken out from the dryer and naturally cooled to about room temperature, the carrier copper foil was peeled off from the obtained cured substrate F, and the state of the surface was visually checked. As a result, no local peeling (lifting) occurred.
[0648] <Example 2>
[0649] In Example 1, the drying of the circuit substrate A was changed to using a vacuum dryer manufactured by Yamato Scientific Co., Ltd., and the circuit substrate A having a size of 515×415 mm was dried by heating at a temperature of 130° C. for 1 hour under vacuum. Then, a cured substrate F was prepared by the same method as in Example 1. The carrier copper foil was peeled off from the obtained cured substrate F, and the state of the surface was visually confirmed. As a result, no local peeling (protrusion) occurred.
[0650] <Example 3>
[0651] In Example 1, the drying of the circuit board A was changed to using a dryer manufactured by ESPEC CORP., and the circuit board A having a size of 515×415 mm was dried at 150° C. for 1 hour under a nitrogen atmosphere. Then, a cured substrate F was prepared by the same method as in Example 1. The carrier copper foil was peeled off from the obtained cured substrate F, and the state of the surface was visually confirmed. As a result, no local peeling (protrusion) occurred.
[0652] <Example 4>
[0653] 15 parts by mass of the naphthol aralkyl type cyanate compound (SNCN) obtained in the above Synthesis Example 1, 35 parts by mass of a maleimide compound (BMI-80, manufactured by KI Chemical Industry Co., Ltd., 2,2-bis(4-(4-maleimidephenoxy)phenyl)propane)), 25 parts by mass of the modified polyphenylene ether compound obtained in the above Synthesis Example 2, 15 parts by mass of a phosphorus flame retardant (PX-200, manufactured by DAIHACHI CHEMICAL INDUSTRY CO., LTD., 1,3-phenylenebis(2,6-di(xylyl)phosphate)), 5 parts by mass of a styrene oligomer (Kristalex 3085, manufactured by Eastman Chemical Co., Ltd.), 5 parts by mass of a styrene-based thermoplastic elastomer (SEPS, manufactured by Kuraray Co., Ltd., SEPTON2104), 5 parts by mass of silica (average particle size 1.1 μm, manufactured by ADMATECHS COMPANY LIMITED SC4500SQ (classified product), 62.5 parts by mass of silica (average particle size 0.7 μm, SFP-130MC, manufactured by Denka Co., Ltd.), 1.0 part by mass of a wetting and dispersing agent (DISPERBYK-161, manufactured by BYK Japan KK), 3.0 parts by mass of a silane coupling agent (KBM-403, manufactured by Shin-Etsu Chemical Co., Ltd.), 0.4 part by mass of a wetting and dispersing agent (DISPERBYK-2009, manufactured by BYK Japan KK), 0.5 part by mass of an ultraviolet absorber (HR-1, manufactured by CHUOSYNTHETIC CHEMICAL CO., LTD.), 0.5 part by mass of a non-metallic organic dye (Kayaset Black AN, manufactured by Nippon Kayaku Co., Ltd.), 0.005 part by mass of manganese octoate, and 0.9 part by mass of triphenylimidazole were dissolved in methyl ethyl ketone and mixed to obtain a varnish. It should be noted that the above-mentioned amounts of addition represent the solid content.
[0654] The obtained varnish is applied to the ultra-thin copper foil surface of an ultra-thin copper foil with a carrier copper foil (carrier copper foil thickness 12 μm, ultra-thin copper foil thickness 1.5 μm, MT-FL, manufactured by Mitsui Mining and Smelting Co., Ltd.) so that the thickness of the dried resin composition layer becomes 30 μm, and the solvent is removed by drying at 150° C. for 5 minutes, thereby obtaining a resin composite sheet C consisting of a resin composition layer and an ultra-thin copper foil with a carrier copper foil.
[0655] The same circuit substrate A as that used in Example 1 was heated at 130° C. for 4 hours using a dryer manufactured by ESPEC CORP. to dry the circuit substrate A having a size of 515×415 mm. Thereafter, a cured substrate F was prepared by the same method as in Example 1. The carrier copper foil was peeled off from the obtained cured substrate F, and the state of the surface was visually confirmed. As a result, no local peeling (protrusion) occurred.
[0656] <Comparative Example 1>
[0657] Two resin composite sheets of 520×420 mm in size consisting of a resin composition layer and an ultra-thin copper foil with a carrier copper foil were prepared in the same manner as in Example 1. Then, they were placed on both sides of a circuit substrate (not dried, 515×415 mm in size) similar to the circuit substrate used in Example 1, with the resin composition layer side in contact with the circuit substrate.
[0658] The object to be processed with the resin composite sheets arranged on both sides of the circuit board was placed in a vacuum laminator manufactured by Nikko-Materials Co., Ltd., and after vacuuming for 30 seconds, the temperature was 150°C and the pressure was 10 kgf / cm 2 The rubber was then vacuum pressed for 30 seconds at 150°C and 10 kgf / cm 2 The laminated substrate was obtained by flat pressing for 60 seconds using a pressing metal plate.
[0659] Then, the obtained laminated substrate was heated at 150° C. for 1 hour using a drying machine manufactured by ESPEC CORP., and then heated to 220° C. for 2 hours to obtain a cured substrate. The mass reduction rate of the laminated substrate before and after the heating in step 4 (heating at 150° C. for 1 hour and heating at 220° C. for 2 hours) was 0.08 mass %.
[0660] The substrate was taken out from the dryer and naturally cooled to about room temperature, and then the carrier copper foil was peeled off from the obtained cured substrate. The surface state was visually checked and it was found that partial peeling (protrusion) occurred.
[0661] <Comparative Example 2>
[0662] Two resin composite sheets of 520×420 mm in size consisting of a resin composition layer and an ultra-thin copper foil with a carrier copper foil were prepared in the same manner as in Example 1. Then, they were placed on both sides of a circuit substrate (not dried, 515×415 mm in size) similar to the circuit substrate used in Example 1, with the resin composition layer side in contact with the circuit substrate.
[0663] The object to be processed in which the resin composite sheets were arranged on both sides of the circuit substrate was subjected to a multi-stage vacuum press manufactured by Kitagawa Seiki Co., Ltd. at a laminate temperature of 220°C and a surface pressure of 30 kgf / cm 2 The vacuum pressing step takes about 3 hours from heating to natural cooling.
[0664] After the obtained cured substrate was taken out from the press, the carrier copper foil was peeled off from the cured substrate, and the state of the surface was visually checked. As a result, no local peeling (lifting) occurred.
[0665] [Table 1]
[0666]
[0667] <Observation of Example 1>
[0668] The flatness of the substrate after peeling the carrier copper foil from the cured substrate F obtained in Example 1 was visually evaluated.
[0669] In addition, for the glass transition temperature of the resin composition layer, two resin composite sheets prepared by the method described in Example 1 are arranged in such a manner that the resin composition layers are in contact with each other, vacuum lamination / thermal curing is performed in the same manner as in Example 1, the carrier copper foil is peeled off, and then the ultra-thin copper foil is etched, and the obtained cured plate is measured as a sample. The glass transition temperature is measured according to the description in paragraph 0142 of Japanese Patent Publication No. 2022-099579.
[0670] <Reference Example 1>
[0671] In Example 1, the ultra-thin copper foil with a carrier copper foil in the resin composite sheet was changed to a PET film (manufactured by UNITIKAL T.) having a thickness of 38 μm, and the same procedures were followed to obtain a laminated substrate.
[0672] When the laminated substrate is heated at 220° C. (200° C. or higher), the PET film adheres to the resin, and therefore the PET film cannot be removed after heating.
[0673] Here, after the PET film was removed from the laminated substrate, heating was performed at 220° C. in the same manner as in Example 1. As a result, the flatness of the cured substrate after the resin was cured was impaired.
[0674] In addition, the presence or absence of swelling (peeling) between the PET film and the resin composition layer was checked.
[0675] In addition, the glass transition temperature of the cured substrate was measured in the same manner as in the above <Observation of Example 1>.
[0676] <Reference Example 2>
[0677] In Reference Example 1, the PET film was not removed, and the heating temperature of the laminated substrate was changed to less than 200° C. to obtain a cured substrate, which was then evaluated as follows.
[0678] The swelling (peeling) between the PET film and the resin composition layer was confirmed.
[0679] In addition, the glass transition temperature of the cured substrate was measured in the same manner as in the above <Observation of Example 1>.
[0680] As a result, the resin composition is not sufficiently cured, and the glass transition temperature of the obtained cured substrate becomes low.
[0681] Table 2 shows the results of Reference Examples 1 and 2 together with the result of Example 1.
[0682] [Table 2]
[0683]
[0684] Industrial Applicability
[0685] The method for producing a metal-clad laminate of the present invention is excellent in mass productivity and can provide a metal-clad laminate in which separation between the resin composition layer and the metal foil is suppressed.
[0686] Furthermore, in the printed wiring board described in Patent Document 1, according to the manufacturing method, the adhesive film is cured to form an insulating layer, and then copper foil is laminated and necessary processing is performed to form a conductor circuit layer, thereby manufacturing a multilayer printed wiring board. However, the present invention can omit such a step.
[0687] Therefore, the method for producing a metal foil-clad laminate of the present invention is extremely useful.
[0688] Description of Reference Numerals
[0689] 11 Insulation layer
[0690] 12 Conductor circuit layer
[0691] 13. Resin composition layer
[0692] 14 metal foil
[0693] 15 Carrier
Claims
1. A method for producing a metal-clad laminated plate using a vacuum laminating device, wherein the metal-clad laminated plate is formed by laminating a resin composite sheet C on a surface of a circuit substrate A, wherein the resin composite sheet C comprises a metal foil and a resin composition layer disposed on one side of the metal foil, and the circuit substrate A comprises an insulating layer and a conductor circuit layer. The method for manufacturing the metal foil-clad laminate comprises the following steps: Step 1: a step of reducing the content of water and / or solvent contained in the circuit substrate A to obtain the circuit substrate B; Step 2: a step of arranging a resin composite sheet C comprising a metal foil and a resin composition layer arranged on one side of the metal foil on at least one surface of a circuit substrate B in such a manner that the resin composition layer side contacts the circuit substrate B, and applying pressure from the surface on the metal foil side under heating and reduced pressure or vacuum to obtain a laminated substrate D in which the resin composite sheet C is laminated on at least one surface of the circuit substrate B; Step 3: A step of obtaining a laminated substrate E by heating and pressing the metal foil side surface of the laminated substrate D obtained in step 2 using a pressing metal plate or a laminating metal roll to smooth the surface of the resin composition layer of the laminated substrate D.
2. The method for producing a metal foil-clad laminate according to claim 1, further comprising the following step after step 3: Step 4: a step of heating the laminated substrate E obtained in the step 3 to cure the resin composition layer, thereby obtaining a cured substrate F.
3. The method for producing a metal foil-clad laminate according to claim 2, wherein: The mass reduction rate of the laminated substrate E due to heating in the step 4 is 1.0 mass % or less. 4 . The method for producing a metal foil-clad laminate according to claim 2 , comprising repeating steps 2 to 4 on the cured substrate F.
5. The method for producing a metal foil-clad laminate according to claim 2 or 3, wherein: The heating in the step 4 is performed at 100 to 250°C.
6. The method for producing a metal foil-clad laminate according to claim 2 or 3, wherein: The heating in the step 4 is performed by stepwise temperature increase in two or more stages.
7. The method for producing a metal foil-clad laminate according to claim 2 or 3, wherein: The heating in the step 4 is performed at 100 to 180°C and then at a temperature higher than 180°C and lower than 250°C. 8 . The method for producing a metal foil-clad laminate according to claim 1 , further comprising an operation of making the circuit board B obtained in the step 1 less likely to absorb moisture. 9 . The method for producing a metal foil-clad laminate according to claim 1 or 2, comprising performing the step 2 immediately after the step 1.
10. The method for producing a metal foil-clad laminate according to claim 1 or 2, wherein: The circuit board B obtained in the step 1 is stored in an atmosphere that is less likely to absorb moisture, and then the step 2 is performed.
11. The method for producing a metal foil-clad laminate according to claim 1 or 2, comprising: In the above step 1, the circuit board B in which the water content contained in the circuit board A is reduced is obtained.
12. The method for producing a metal foil-clad laminate according to claim 1 or 2, wherein: The heating in the step 1 is performed at 30 to 200°C.
13. The method for producing a metal foil-clad laminate according to claim 1 or 2, wherein: The heating in step 2 is performed at a temperature of 80 to 190°C and a pressure of 3 to 30 kgf / cm 2 Next proceed.
14. The method for producing a metal foil-clad laminate according to claim 1 or 2, wherein: The heating in step 3 is performed at a temperature of 80 to 190°C and a pressure of 3 to 30 kgf / cm 2 Next proceed.
15. The method for producing a metal foil-clad laminate according to claim 1 or 2, wherein: The metal foil is copper foil.
16. The method for producing a metal foil-clad laminate according to claim 1 or 2, wherein: The resin composite sheet C includes a carrier substrate, the metal foil, and the resin composition layer in this order.
17. The method for producing a metal foil-clad laminate according to claim 1 or 2, wherein: The resin composition includes a thermosetting resin, and a content of the inorganic filler is 0 to 250 parts by mass based on 100 parts by mass of a resin solid content included in the resin composition.
18. A resin composition for producing a metal-clad laminate by a method using a vacuum laminating device and comprising the following steps, wherein the metal-clad laminate is formed by laminating a resin composite sheet C on a surface of a circuit substrate A, the resin composite sheet C comprising a metal foil and a resin composition layer disposed on one side of the metal foil, and the circuit substrate A comprising an insulating layer and a conductor circuit layer, The resin composition includes a thermosetting resin, and the content of the inorganic filler is 0 to 250 parts by mass relative to 100 parts by mass of the resin solid content included in the resin composition; Step 1: a step of reducing the content of water and / or solvent contained in the circuit substrate A to obtain the circuit substrate B; Step 2: a step of arranging a resin composite sheet C comprising a metal foil and a resin composition layer arranged on one side of the metal foil on at least one surface of a circuit substrate B in such a manner that the resin composition layer side contacts the circuit substrate B, and applying pressure from the surface on the metal foil side under heating and reduced pressure or vacuum to obtain a laminated substrate D in which the resin composite sheet C is laminated on at least one surface of the circuit substrate B; Step 3: A step of obtaining a laminated substrate E by heating and pressing the metal foil side surface of the laminated substrate D obtained in step 2 using a pressing metal plate or a laminating metal roll to smooth the surface of the resin composition layer of the laminated substrate D.
19. The resin composition according to claim 18, wherein The thermosetting resin comprises at least one selected from the group consisting of a polymer having a structural unit represented by formula (V), a polyphenylene ether compound having a carbon-carbon unsaturated double bond at a terminal, a maleimide compound, a cyanate compound, an epoxy compound, a phenol compound, an oxetane resin, a benzoxazine compound, and an alkenyl-substituted nadic imide compound, In formula (V), Ar represents an aromatic hydrocarbon linking group; * represents a bonding position.
20. The resin composition according to claim 18 or 19, wherein The resin composition comprises an inorganic filler material, The inorganic filling material includes silicon dioxide.
21. The resin composition according to claim 18 or 19, wherein The resin composition comprises an inorganic filler material, The inorganic filler has an average particle size D50 of 0.1 μm or more and 5 μm or less.
22. A resin composite sheet for producing a metal foil-clad laminate by a method using a vacuum laminating apparatus and comprising the following steps: The metal foil-clad laminate is formed by laminating a resin composite sheet on the surface of a circuit substrate A, wherein the resin composite sheet comprises a metal foil and a resin composition layer disposed on one side of the metal foil, and the circuit substrate A comprises an insulating layer and a conductor circuit layer. The resin composition includes a thermosetting resin, and the content of the inorganic filler is 0 to 250 parts by mass relative to 100 parts by mass of the resin solid content included in the resin composition; Step 1: a step of reducing the content of water and / or solvent contained in the circuit substrate A to obtain the circuit substrate B; Step 2: a step of arranging a resin composite sheet including a metal foil and a resin composition layer arranged on one side of the metal foil on at least one surface of a circuit substrate B in such a manner that the resin composition layer side is in contact with the circuit substrate B, and applying pressure from the surface on the metal foil side under heating and reduced pressure or vacuum to obtain a laminated substrate D in which the resin composite sheet is laminated on at least one surface of the circuit substrate B; Step 3: A step of obtaining a laminated substrate E by heating and pressing the metal foil side surface of the laminated substrate D obtained in step 2 using a pressing metal plate or a laminating metal roll to smooth the surface of the resin composition layer of the laminated substrate D.
23. The resin composite sheet according to claim 22, wherein: The resin composite sheet includes a carrier substrate, the metal foil, and the resin composition layer in this order.
24. The resin composite sheet according to claim 22 or 23, wherein: The metal foil is copper foil.
25. The resin composite sheet according to claim 22 or 23, wherein The thermosetting resin comprises at least one selected from the group consisting of a polymer having a structural unit represented by formula (V), a polyphenylene ether compound having a carbon-carbon unsaturated double bond at a terminal, a maleimide compound, a cyanate compound, an epoxy compound, a phenol compound, an oxetane resin, a benzoxazine compound, and an alkenyl-substituted nadic imide compound, In formula (V), Ar represents an aromatic hydrocarbon linking group; * represents a bonding position.
26. The resin composite sheet according to claim 22 or 23, wherein The resin composition comprises an inorganic filler material, The inorganic filling material includes silicon dioxide.
27. The resin composite sheet according to claim 22 or 23, wherein The resin composition comprises an inorganic filler material, The inorganic filler has an average particle size D50 of 0.1 μm or more and 5 μm or less.
28. A method for producing a printed wiring board, comprising the method for producing a metal foil-clad laminate according to claim 1 or 2.
29. A method for manufacturing a semiconductor device, comprising the method for manufacturing a metal foil-clad laminate according to claim 1 or 2.
Citation Information
Patent Citations
Surface treatment of copper foil for printed circuit
JP1983015950B2
Positioning apparatus for automatically positioning patient
JP1988130058A
Information recording medium and recording method using the same
JP1990089683A
Control method of engine provided with supercharger
JP1991260327A
Epoxy resin composition, and sheet, preperg-like material, sheet with metal foil, laminated sheet, electrical insulating material and resist material obtained therefrom
JP2004277460A